Overflow metabolism drives high-rate carbon, nitrogen and phosphorus sequestration in an enriched aerobic microbial community - Dilani D. Jayathilaka; Md Iqbal Hossain; Linda L. Blackall; Ka Yu Cheng; Ranjan Sarukkalige; Maneesha P. Ginige (Water Research, 2026)

Delayed flooding after green manure incorporation enhances microbial necromass formation and stabilization in paddy soils - Zhengbo Ma; Danna Chang; Qingxu Ma; Haoran Fu; Jinxin Sun; Ting Liang; Cheng Cai; Sheng Tang; Guopeng Zhou; Davey L. Jones; Wolfgang Wanek; Qing Zhang; et al. (Soil Biology and Biochemistry, 2026)

Rice leaf pathogen infection alters the spectral–biochemical relationships revealed by radiative transfer model inversion - Long Tian; Susan L. Ustin; Yuanyuan Kong; Bowen Xue; Pablo J. Zarco-Tejada; Chongya Jiang; Xia Yao; Yufang Jin; Yan Zhu; Weixing Cao; Tao Cheng (Remote Sensing of Environment, 2026)

Diterpenoids from the flower buds of Daphne genkwa induced the pyroptosis of HCT-116 cells by inhibiting STAT3 phosphorylation - Zuijie Cheng; Juan Wu; Xiaolan Chen; Hongyou Li; Zhengxiang Tong; Xin Chen; Rongtao Li; Norelle L. Daly; Yao Bai; Xuanqin Chen (Phytochemistry, 2026)

Geochronological and geochemical insights into Neoproterozoic granitoids of the Guibei region, western Jiangnan Orogen, China: Implications for petrogenesis and tectonic evolution - Youyue Lu; Jingya Cao; Liyan Ma; Jianming Fu; Alexander L. Peace; Xiaoyong Yang; Jiaxi Zhou; Shunbo Cheng; Kun Li; Bang An (Journal of Asian Earth Sciences, 2026)

Minutes-long soft X-ray prompt emission from a compact object merger - An Li; Chen-Wei Wang; Niccolò Passaleva; Jie An; Bin-Bin Zhang; Eleonora Troja; Yi-Han Iris Yin; Yuan Liu; Shao-Lin Xiong; Li-Ping Xin; Yi-Xuan Shao; Jun Yang; et al. (Science Bulletin, 2026)

Crimean speleothems reveal 50,000 years of climate variability and contrasting controls across the Black Sea region - Yidong Li; Christoph Spötl; Jonathan L. Baker; Sophie F. Warken; Sergey Tokarev; Gennady Amelichev; Hai Cheng; Aaron Mielke; Gabriella Koltai; Yuri Dublyansky (Quaternary Science Reviews, 2026)

Internal water and organic matter increase calcite clumped isotope reactivity - Zeyang Sun; Jingxiang Cheng; Sarbajit Banerjee; Ethan L. Grossman (Geochimica et Cosmochimica Acta, 2026)

Proteomic comparison of human neural cell-derived extracellular vesicles and parental cells from Alzheimer’s disease and cognitively normal individuals - Jia-Yan Xin; Jie Liu; Hao-Min Dong; Hai-Lun Yu; Zhong-Song Xiao; Jian-Ni Hu; Qiu Jiang; Yu-Peng Zhu; Lin Feng; Yun Feng; Yu-Juan Jia; Zi-Yu Yuan; et al. (Science China Life Sciences, 2026)

Supervised and few-shot learning for classifying MRI sequences and acquisition planes in hypopharyngeal cancer using metadata and imaging - Cheyu Hsu; Yuju L. Cheng; Chunhao Chang; Reyna Quita; Rouyi Chen; Weichung Wang (Next Research, 2026)

Not the same plastics: Comparing abundance and composition of marine macro-litter in mangroves and beaches in Southeast Asia - Jenny Fong; Ashwini Suresh Kumar; Cheng Ling Lim; Muhammad Reza Cordova; Pham T. Hoa; Deo Florence L. Onda; Kim John N. Balboa; Norchel Corcia F. Gomez; Mochamad Riza Iskandar; Muhammad Taufik Kaisupy; Swietenia Puspa Lestari; Pham Ngoc; et al. (Journal of Environmental Management, 2026)

Assembloid-like odontogenic-angiogenic microspheroids promote dental-pulp regeneration via CX26-CFOS signaling - Haokun He; Zhenni Liu; Siwen Xiao; Shuiqing Yu; Ling Chen; Shuguang Cheng; Richard T. Jaspers; Sujuan Zeng; Qing Zhang; Janak L. Pathak (Chemical Engineering Journal, 2026)

Microbial Functional Gene Abundance‐Integrated Modeling of Global Methane Sinks in Upland Soils Under Future Climate Change - Wensheng Xiao; Xiaoqi Zhou; Li Cheng; Paul L. E. Bodelier; Gangsheng Wang; Zhifeng Yang; Jizhong Zhou (Global Change Biology, 2026)
Methanotrophs are key microbial regulators of soil methane (CH 4 ) sinks, but the global impact of their functional gene abundance on CH 4 oxidation remains unquantified. This gap limits the integration of key functional genes abundance parameters (e.g., pmoA ) into soil CH 4 sink model. We integrated meta‐analysis, machine learning, and process‐based modeling to assess the relationship between pmoA gene abundance and soil CH 4 uptake. Our developed Functional Gene Abundance‐Based Methanotrophy Model (FGA‐MeMo) incorporates pmoA as a proxy for CH 4 oxidation capacity, significantly improving model simulations. FGA‐MeMo estimates global upland soil CH 4 uptake at 45.74 ± 0.26 Tg year −1 , which is 56%–58% higher than MeMo model. Under SSP5‐8.5 scenario, this increases to 64.68 ± 0.35 Tg year −1 by 2100, with mid‐ and high‐latitude regions showing enhanced CH 4 oxidation due to greater pmoA abundance. These findings highlight the importance of integrating microbial functional genes into Earth system models for improved CH 4 cycle predictions.

Long-term N fertilization altered viral community composition and increased functional potentials of phosphorus cycling by causing soil acidification - Shuxun Cheng; Zhongmin Dai; Dan He; Ran Xue; Kankan Zhao; Jorge L. Mazza Rodrigues; Lucas W. Mendes; Scott X. Chang; Jianming Xu (Soil Biology and Biochemistry, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

The Sedimentary Geochemistry and Paleoenvironments Project Phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Neuromuscular control mechanism during posture-cognition dual task in mild cognitive impairment: a concurrent fNIRS-sEMG-COP study - Ruochen Fu; Jinjin Ma; Yao Zu; Yingying Fang; Yan Li; Arnold Y. L. Wong; Xue Cheng; Yan Leng; Jiajia Yang; Chuhuai Wang; Qiuhua Yu (GeroScience, 2026)

Activation of mosquito and human transient receptor potential ankyrin 1 (TRPA1) channels by the natural drimane sesquiterpene cinnamodial - Tae Lee; Jayce Liu; Yeaeun Park; Harinantenaina L. Rakotondraibe; Xiaolin Cheng; Peter M. Piermarini (Pesticide Biochemistry and Physiology, 2026)

Effects of oxygen-fuel velocity ratio on soot formation and flame structure in CH4-CO2-O2 inverse diffusion flames - Teng Hu; Keyu Cheng; Huajie Lyu; Jun Wan; William L. Roberts; Chenghang Zheng; Peng Liu; Xiang Gao (Fuel, 2026)

Opportunistic bacteria enhancing inorganic phosphorus level in post-wildfire tropical forest peatlands - Pengfei Gao; Xiaoyu Cheng; Wen Tian; Hongmei Wang; Xiaoyan Liu; Olli H. Tuovinen; Thomas E.L. Smith; Stephanie L. Evers (Applied Soil Ecology, 2026)

The SPoRC Stock Assessment Package: A Generalized Next‐Generation Platform to Assess Spatial, Age and Sex‐Structured Populations - Matthew LH. Cheng; Daniel R. Goethel; Curry J. Cunningham; Peter‐John F. Hulson; James N. Ianelli; Kristen L. Omori (Fish and Fisheries, 2026)
Fisheries managers increasingly rely on stock assessment models to provide sustainable management advice, which must balance complex and competing objectives. Although assessment models necessitate simplifying assumptions, there is increasing recognition to improve the integration of realistic biological and fishery dynamics. While ongoing and future development of increasingly complex stock assessments requires increased capacity (i.e., time, training, and personnel), there are concerns that the growing demand for assessment advice cannot be adequately fulfilled under current resources. To address these needs, we present the Stochastic Population over Regional Components (SPoRC) model, a modern integrated analysis platform that is generalized, modular and developed in a user‐friendly programming language (R with Template Model Builder, RTMB). Development of SPoRC emphasized consideration of age, sex, and spatial dynamics at the outset, while ensuring the ability to integrate diverse data sources (e.g., catch, abundance indices, age/length compositions and tagging). Moreover, state‐space specification of time‐varying processes through random effects and robust simulation capabilities were primary design features. Here, we highlight SPoRC's utility in cohesively implementing single‐and multi‐region applications, its ability to estimate time‐varying processes as random effects, and the potential to conduct closed‐loop simulations for evaluating the robustness of management procedures. By developing a generalized assessment platform in a user‐friendly R package, we suggest that SPoRC reduces barriers to implementation of next‐generation stock assessment models and facilitates team‐based model development, which will ultimately help improve the capacity to implement stock assessments globally.

The global proliferation of aquatic, benthic Microcoleus: Taxonomy, distribution, toxin production, ecology, and future directions - Laura T. Kelly; Daniel G. Beach; Joanna R. Blaszczak; Keith Bouma-Gregson; Sydney M. Brown; Haowu Cheng; Janette L. Davidson; Jutta Fastner; Marcus Francis; Andrea Garcia Jimenez; Laurel Genzoli; Ramesh Goel; et al. (Water Research, 2026)

The evolution of the cave's entrance of Bruniquel and consequences for its accessibility by early Homo neanderthalensis - K. Génuite; S. Verheyden; H. Camus; C. Burlet; M. Boudadi-Maligne; L. Bruxelles; H. Cheng; D. Cochard; S. Delaby; E. Fabre; C. Ferrier; C. Lézin; et al. (Quaternary Science Reviews, 2026)

Corrigendum to “Ammonium-coordinated exchanger (ACE) functionalized silica sorbents for recovering/removing aqueous anionic contaminants” [J. Environ. Chem. Eng. 13 (2025) 1–13/119727] - Walter Chris Wilfong; Qiuming Wang; Fan Shi; Chin-Min Cheng; William Garber; Karen Johnson; Phillip Tinker; Gita Bhandari; Bret Howard; McMahan L. Gray (Journal of Environmental Chemical Engineering, 2026)

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

Independent and combined associations of maternal one-carbon nutrition biomarkers and dietary patterns with epigenetic age acceleration: Evidence from the Boston Birth Cohort - Nusrat Jabin; Guoying Wang; Xiumei Hong; Serena Rusk; Tina L. Cheng; Xiaobin Wang (GeroScience, 2026)

Solvent-based synthesis and characterization of sodium thiophosphate catholytes for nonaqueous redox flow batteries - Ernesto C. Zuleta S.; Vaidyanathan Sethuraman; Michelle L. Lehmann; Gabriel Goenaga; Guang Yang; Lei Cheng; Ethan C. Self (Chemical Engineering Journal, 2026)

From digital decision-support to policy implementation: An operational framework for agri-environmental schemes - A.C. Wartenberg; C. Cheng; C. Marples; H. Dettmann; K. Hemminger; F. Ghafarian; L. Schaan; M. Scoville; S.D. Bellingrath-Kimura (Biological Conservation, 2026)

Improvements in vibroseis source technology towards low frequencies - Ming-tao Nie; Zhou-hong Wei; Yong-fei Qi; Yang Liu; Yong-an Xu; Cheng-kuan Zhou; Sheng-kui Cong; Hai Ling; Gene-L. Wei (Applied Geophysics, 2026)

Insight into Face Identity Recognition Ability: A Systematic Review and Meta-analysis - Kadie Cheng; Romina Palermo; Simone Favelle; Rose Ferguson; Megan L. Willis (Neuropsychology Review, 2026)
This review estimated the strength of the relationship between self-reported and objectively measured face identity recognition ability and examined potential moderators of this relationship. CINAHL, Medline, PsycInfo, Scopus, and ProQuest Dissertation and Theses databases were searched on April 16, 2025, for two concepts: insight and face recognition. Studies were included if they were written in English, comprised adult samples, included an objective face recognition task and a measure of self-reported face recognition ability, and reported the relationship between the two. Forty-four studies ( N = 11,074) comprising 141 effect sizes were included in a random effects meta-analysis with robust variance estimation, which revealed a significant, positive relationship between self-reported and objective face recognition ability of medium strength ( r = .26, 95% CI [.22, .30]). Moderator analyses revealed a stronger effect size for samples comprising a combination of neurotypicals and developmental prosopagnosics ( r = .64, 95% CI [.47, .80]) compared to studies comprising only neurotypicals ( r = .27, 95% CI [.22, .32]), developmental prosopagnosics ( r = .15, CI [−.04, .35]), or super-recognisers ( r = .16, 95% CI [.05, .28]). A stronger effect size was observed for face memory tasks ( r = .30, 95% CI [.26, .34]) compared to face perception tasks ( r = . 21, 95% CI [.15, .28]). Considerable heterogeneity was evident between studies comprising neurotypical samples, which may be attributable to methodological differences in exclusion criteria and participant characteristics related to face recognition ability, which were generally poorly reported across studies. Collectively, findings indicate people have modest insight into their face recognition ability, and self-report measures offer limited utility for identifying face recognition difficulties.

A fast powerful X-ray transient from possible tidal disruption of a white dwarf - Dongyue Li; Wenda Zhang; Jun Yang; Jin-Hong Chen; Weimin Yuan; Huaqing Cheng; Fan Xu; Xinwen Shu; Rong-Feng Shen; Ning Jiang; Jiazheng Zhu; Chang Zhou; et al. (Science Bulletin, 2026)

The Sedimentary geochemistry and paleoenvironments project phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Identifying Headwater Streams across the Conterminous United States - Charles R. Lane; Ellen D’Amico; Jay R. Christensen; Heather E. Golden; Frederick Y. Cheng; John C. Hammond; Admin Husic; Kristin L. Jaeger; C. Nathan Jones; Christa A. Kelleher; Li Li; D. Tyler Mahoney; et al. (Ecosystems, 2026)

Sulphur wheel: A neglected driver for the coupling of multi-element cycles in soil - Tianzhuo Cheng; Yingfan Wang; Davey L. Jones; Roland Bol; Wolfgang Wanek; Yongchao Liang; Qingxu Ma (Biology and Fertility of Soils, 2026)

Lentipes ptasan , a new species of sicydiine goby (Teleostei: Gobioidei) from the Western Pacific, with a redescription of L. mindanaoensis - Wei‐Cheng Jhuang; Cleto L. Nañola; Xiao Fei Li; Te‐Yu Liao (Journal of Fish Biology, 2026)
Lentipes ptasan sp. nov. is described based on specimens collected from Taiwan and Mindanao Island. It is a large‐sized Lentipes species distinguished by several male‐specific characteristics, including an upper lip protruding beyond snout obviously, fewer premaxillary tricuspid teeth, two black lines running from the front of the eye through the nostrils to the tip of the snout, a wide brown longitudinal band at the base of the anal fin, and the distinctive nuptial coloration featuring a brown vertical band extending from back to belly on the middle of the body. The complex distribution of Lentipes species and their genetic differentiation may be influenced by sexual selection, historical biogeographic events and contemporary ecological processes. However, due to the recent divergence of Lentipes species, 11 out of 14 species could not be distinguished by the cytochrome oxidase subunit I gene. Furthermore, Lentipes mindanaoensis is redescribed, with L. adelphizonus treated as its junior synonym.

Soil Invertebrate Body Size Groups and Effect Magnitude Jointly Influence Global Soil CO 2 Emissions - Cheng Liu; Catherine L. Parr; Benoit Guénard; Xiaoyu Cen; Hua Chai; Mingxu Li; Zhiwei Zhong; Shenliang Zhao; Jie Li; Nianpeng He (Global Change Biology, 2026)
Soil invertebrates represent vital components of belowground biodiversity and play pivotal roles in regulating key carbon (C) cycling processes, particularly soil respiration. Despite the recognised effects of invertebrates on soil respiration, previous studies suffer from a major blind spot: a lack of global‐scale interpretations of inferred associations describing how these organisms mediate C release. In this study, we integrated 556 datasets spanning 90 publications to systematically assess the global patterns and inferred associations by which soil invertebrates influence soil respiration. The results revealed that soil invertebrates, on average, enhanced soil respiration by 52%. Across climatic zones, the magnitude of this positive effect tended to decline from tropical to temperate regions. When classified by body size, among the large‐bodied soil invertebrates, ants and termites increased soil respiration by 60% and 62%, respectively, whereas earthworms stimulated it by 47%. In contrast, small‐to‐medium‐bodied soil invertebrates exerted no significant effect. Across ecosystem types, soil invertebrates stimulated soil respiration more strongly in forest ecosystems, with an increase of 55%, compared to a 44% increase in grassland ecosystems. The pathways through which soil invertebrates influence respiration varied markedly among body‐size groups and ecosystem types. Overall, soil invertebrates primarily influenced soil microbial biomass C, fungal biomass and bacterial biomass, as well as soil organic N, soil organic C and soil pH, which in turn were closely associated with soil respiration. These findings underscore the key role of soil invertebrates in influencing soil CO 2 emissions and provide insights essential for improving Earth system models under ongoing climate change.

WABAD : A world annotated bird acoustic dataset for passive acoustic monitoring - Cristian Pérez‐Granados; Jon Morant; Kevin F. A. Darras; Oscar H. Marín‐Gómez; Irene Mendoza; Miguel A. Muñoz‐Mohedano; Eduardo Santamaría‐García; Giulia Bastianelli; Alba Márquez‐Rodríguez; Michał Budka; Gerard Bota; José M. De la Peña‐Rubio; et al. (Ecology, 2026)
Under the current global biodiversity crisis, there is a need for automated and noninvasive monitoring techniques that can gather large amounts of data cost‐effectively at various ecological scales, from local to large spatial scales. These data can then be analyzed to inform stakeholders and decision‐makers. One such technique is passive acoustic monitoring, which is commonly coupled with automatic identification of animal species based on their sound. Automated sound analyses usually require the training of sound detection and identification algorithms. These algorithms are based on annotated acoustic datasets which mark the occurrence of sounds of species inside sound recordings. However, compiling large annotated acoustic datasets is time‐consuming and requires experts, and therefore, they normally cover reduced spatial, temporal, and taxonomic scales. This data paper presents WABAD, the World Annotated Bird Acoustic Dataset for passive acoustic monitoring. WABAD is designed to provide the public, the research community, and conservation managers with a novel and globally representative annotated acoustic dataset. This database includes 5047 min of audio files annotated to species‐level by local experts with the start and end time and the upper and lower frequencies of each identified bird vocalization in the recordings. The database has a wide taxonomic and spatial coverage, including information on 91,931 vocalizations from 1192 bird species recorded at 72 recording sites in 29 recording locations (mainly countries) and distributed across 13 biomes. WABAD can be used, for example, for developing and/or validating automatic species detection algorithms, answering ecological questions, such as assessing geographical variations on bird vocalizations, or comparing acoustic diversity indices with species‐based diversity indices. The dataset is published under a Creative Commons Attribution 4.0 International license that permits redistribution and reuse on the condition that the original work is properly credited.

Spatial and temporal variations in the distribution of eastern Australian post-orogenic granites and related mineral deposits: metallogenic and tectonic significance - D. L. Huston; Y. Cheng; S. L. Jones; D. C. Champion; M. D. Norman; M. W. Agnew; A. Cross; V. C. Bennett; R. A. Creaser (Australian Journal of Earth Sciences, 2026)

Correlation of optical properties with particle size, morphology, and polymorph of fine- and nano-particle formulations of titanium dioxide powders - Schuyler P. Lockwood; Zezhen Cheng; Valentina Sola; Nurun Nahar Lata; Tanya L. Myers; Timothy J. Johnson; Mark E. Bowden; Alla Zelenyuk (Journal of Aerosol Science, 2026)

A whole-rock geochemistry-based semi-quantitative proxy for magmatic oxygen fugacity - Ze Liu; Oliver Jagoutz; Hervé Rezeau; Hong-Luo L. Zhang; Benjamin Klein; Zoe Molitor; Xu-Yang Meng; Di-Cheng Zhu (Earth and Planetary Science Letters, 2026)

Retraction Note to: Degradation of βII-Spectrin Protein by Calpain-2 and Caspase-3 Under Neurotoxic and Traumatic Brain Injury Conditions - Firas H. Kobeissy; Ming Cheng Liu; Zhihui Yang; Zhiqun Zhang; Wenrong Zheng; Olena Glushakova; Stefania Mondello; John Anagli; Ronald L. Hayes; Kevin K. W. Wang (Molecular Neurobiology, 2026)

Mesenchymal cell-derived extracellular vesicles ameliorate age-related deficits in working memory and in vivo MRI measures of white matter structure and function in rhesus monkeys - Evan C. Mackie; Chia-Hsin Cheng; Maya N. Alibrio; Christine Rutledge; Hongqi Xin; Michael Chopp; Ryan P. McCann; Douglas L. Rosene; Qiong Yang; Ella Zeldich; Maria Medalla; Bang-Bon Koo; et al. (GeroScience, 2025)
Aging humans and non-human primates both exhibit a similar pattern of cognitive decline beginning in middle age that is characterized by progressive impairments in rule learning, executive function, and working and recognition memory—functions often associated with dysfunction of prefrontal and medial temporal lobe regions. The heterogeneity and inter-subject variability in aging and age-related cognitive impairments present challenges for developing effective therapeutics and can be attributed to differing degrees of cortical white matter (WM) damage and alterations to local and long-range prefrontal and temporal networks. A promising therapeutic that has been shown to be efficacious in mitigating WM damage and improving cognitive function in rodent models is mesenchymal cell-derived extracellular vesicles (MSC-EVs). In the present study, late middle-aged rhesus monkeys were systemically administered monkey-derived MSC-EVs every 2 weeks for 18 months. We demonstrate that MSC-EV treatment improves spatial working memory and decreases the frequency of perseverative responses with largely no effects on recognition memory. These cognitive improvements were associated with increases in MRI diffusion measures of WM structural integrity over time as well as preservation of inter-network functional connectivity as measured by resting-state functional MRI. These findings suggest that MSC-EV treatment can slow or reverse age-related cognitive decline while strengthening WM integrity and improving functional connectivity in late middle-aged rhesus monkeys.

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Reliable identification of flood-borne deposits in speleothems using magnetic microscopy - Samuel L. Piascik; Roger R. Fu; Nicolás M. Stríkis; Ricardo I.F. Trindade; Julio Cauhy Rodrigues; Francisco W. Cruz; Gelson F. Souza-Junior; Andrea Borsato; Vitor Azevedo; Plinio Jaqueto; Isabel Tamara Pedron; Perri Thaler; et al. (Quaternary Science Reviews, 2025)

Ammonium-coordinated exchanger (ACE) functionalized silica sorbents for recovering/removing aqueous anionic contaminants - Walter Chris Wilfong; Qiuming Wang; Fan Shi; Chin-Min Cheng; William Garber; Karen Johnson; Phillip Tinker; Gita Bhandari; Bret Howard; McMahan L. Gray (Journal of Environmental Chemical Engineering, 2025)

The coupling between monsoon rainfall and Sea Surface Temperature in the subtropical South Atlantic during the Last Glacial Period - Lucas C. Vasconcelos; Francisco W. Cruz; Juan Pablo Bernal; Marília C. Campos; Patrícia Piacsek; José L. Campos; Haiwei Zhang; Nicolás Stríkis; Mathias Vuille; Giselle Utida; Christian Millo; R. Lawrence Edward; et al. (Global and Planetary Change, 2025)

Microbial, genetic, and urban drivers of ant invasions - Wei-Jiun Lin; Po-Wei Hsu; Edward L Vargo; Chin-Cheng Scotty Yang (Current Opinion in Insect Science, 2025)

Aqueous lead removal using biochar-pumice filter derived from avocado seed, aspen bedding and palm tree frond - V. Igberase; J. Parsons; C.-L. Cheng; J. Kim; J. J. Kang (International Journal of Environmental Science and Technology, 2025)

Evaluation of multimodel averaging approaches for ensembling evapotranspiration and yield simulations from maize models - Viveka Nand; Zhiming Qi; Liwang Ma; Matthew J. Helmers; Chandra A. Madramootoo; Ward N. Smith; Tiequan Zhang; Tobias K.D. Weber; Elizabeth Pattey; Ziwei Li; Jiaxin Wang; Virginia L. Jin; et al. (Journal of Hydrology, 2025)

Bottom‐Up Interactions in State‐Space Age‐Structured Models Using Mass‐Balance Dynamics - James T. Thorson; Kerim Y. Aydin; Matthew L. H. Cheng; Beatriz S. Dias; David G. Kimmel; Kasper Kristensen (Fish and Fisheries, 2025)
Age‐structured models are used worldwide to regulate fisheries. These models typically ignore top‐down interactions (predation affecting natural mortality) and bottom‐up interactions (consumption affecting individual growth, reproduction, or survival), whereas multispecies catch‐at‐age models often incorporate top‐down but not bottom‐up interactions. While Ecopath‐with‐Ecosim (EwE) incorporates both top‐down and bottom‐up interactions along with age‐structured dynamics, it is not typically fitted to age‐composition data. We extend Ecostate (a state‐space version of EwE) to incorporate age‐structured dynamics while fitting to age‐structured data and use this to illustrate how to add bottom‐up interactions to age‐structured models. Specifically, we add age‐structured dynamics and likelihood components for age‐composition and weight‐at‐age data while estimating residual variation in larval survival (recruitment deviations) and consumption (weight‐at‐age deviations). As a demonstration, we fit the model to biomass and age‐composition data for two commercial species (Alaska pollock and sablefish) in the Gulf of Alaska, including population dynamics for their major prey, while not fitting weight‐at‐age data so that it can be used for out‐of‐sample evaluation of model performance. The model can be viewed as a multispecies age‐structured model (e.g., estimating adult mortality rates, survey catchability and selectivity, and recruitment variation) and as a mass‐balance ecosystem model (e.g., estimating trophic position and weight‐at‐age based on forage consumption). The predicted weight‐at‐age is weakly correlated with independent measurements for pollock and sablefish but was improved when we incorporated forage biomass indices. We recommend that age‐structured models routinely explore the link between prey consumption and resulting size‐at‐age, whether using coupled predator–prey dynamics or simplifications that treat prey abundance as fixed data.

Age differences in what-if thinking from midlife onwards: Prefrontal contribution and implications for emotional health in late life - Riccardo M. Galli; Friederike Thams; Bernd Löwe; Bastian Cheng; Götz Thomalla; Max Bieder; Elina L. Petersen; Christian Büchel; Stefanie Brassen (GeroScience, 2025)

Authigenic CaCO3 precipitation contributes to the stabilization of algal-derived organic carbon in karst lake - Yingxun Du; Cheng Zhao; Xuexin Han; Shilin An; Zhendu Mao; Fan Xun; Ding He; Yongdong Zhang; Muhua Feng; Wenlei Luo; Qinglong L. Wu; Peng Xing (Water Research, 2025)

Visualizing the pre-visual: Rice blast infection signals revealed - Long Tian; Susan L. Ustin; Bowen Xue; Pablo J. Zarco-Tejada; Yufang Jin; Xia Yao; Yan Zhu; Weixing Cao; Tao Cheng (Remote Sensing of Environment, 2025)

Functional MTTP and apoB for VLDL secretion in chicken ovaries support small follicle development under heat stress - Petnamnueng Dettipponpong; Mei-Ying Sin; Yu-Hui Chen; Chuen-Yu Cheng; San-Yuan Huang; Rosemary L. Walzem; Ling-Chu Chang; Shuen-Ei Chen (Journal of Thermal Biology, 2025)

Technical Considerations of Pharmacokinetic Assays for LNP-mRNA Drug Products by RT-qPCR - Jason Pennucci; Amanda Hays; Wendy Adamowicz; Mitra Azadeh; Mohamed Benhammadi; Enric Bertran Portabella; MingLai Cheng; Kelly Colletti; Sanjay L. Dholakiya; Rajitha Doddareddy; Lara Duchstein; Jennifer Durham; et al. (The AAPS Journal, 2025)
Lipid nanoparticle-messenger RNA (LNP-mRNA) drug products are a growing class of drug modalities. The unique composition of these drug products requires multiple measurements to account for the different components of these drug modalities. Pharmacokinetic (PK) measurements include measurement of the encapsulated mRNA and components of the LNP in circulation to understand the effectiveness of the therapeutic mRNA. The PK measurements can utilize many different platforms including PCR. Current regulatory guidance documents for bioanalytical method validation are specific to ligand binding and chromatographic assay methods and difficult to interpret for use with molecular workflows. The purpose of this paper is to provide information on considerations for validation of regulated reverse transcription quantitative PCR (RT-qPCR) assays that are used to support the pharmacokinetic analysis of LNP-mRNA drug products. Graphical Abstract

P30-01 Application of 3Rs Strategies for Existing Chemicals Substances Standard Registration in Taiwan: Case study of Silicon carbide - S.-N. Chen; O. Lautan; Y.-Y. Chen; Y.-L. Yeh; Y.-H. Cheng; C.-C. Tseng; T.-N. Li; Z.-Y. Chen; R.-J. Chen; Y.-J. Wang (Toxicology Letters, 2025)

Dithiothreitol oxidative potential (OP) of PM2.5 in Beijing: Quantitative contribution of metals to OP and its prediction based on machine learning models - Yusheng Ma; Mengshuang Sheng; Jing Shang; Rui Tang; Jiong Cao; Yuhan Liu; Chenyu Liang; Yu Kuang; Yan Zheng; Zhen Cheng; Rico K.Y. Cheung; Robin L. Modini; et al. (Journal of Hazardous Materials, 2025)

Intrinsic Functional Connectivity Associated with γ‑Aminobutyric Acid and Glutamate/Glutamine in the Lateral Prefrontal Cortex and Internalizing Psychopathology in Adolescents - Kai Wang; Harry R. Smolker; Mark S. Brown; Hannah R. Snyder; Yu Cheng; Benjamin L. Hankin; Marie T. Banich (Neuroscience Bulletin, 2025)

Panmictic Panacea? Demonstrating Good Practices for Developing Spatial Stock Assessments Through Application to Alaska Sablefish ( Anoplopoma fimbria ) - Matthew L. H. Cheng; Craig A. Marsh; Daniel R. Goethel; Peter‐John F. Hulson; Katy Echave; Benjamin C. Williams; Aaron M. Berger; Curry J. Cunningham (Fish and Fisheries, 2025)
Marine species and associated fisheries demonstrate complex spatial dynamics driven by biological, ecosystem and socioeconomic factors and integrating these spatial dynamics into stock assessment models can improve fishery management advice. While preliminary good practices for developing spatial stock assessment models have been proposed, comprehensive demonstrations applying these practices remain limited. Drawing on these good practices, we provide an end‐to‐end demonstration of developing a spatial stock assessment using Alaska sablefish ( Anoplopoma fimbria ). Our demonstration emphasises the utility of high‐resolution data analysis and conceptual models for informing key model structure decisions, the joint development of spatial and spatially‐aggregated models to enhance understanding of population dynamics, and the need for further guidance on integrating tagging data and diagnostic tools in spatial assessments. Spatial models highlighted regional differences in sablefish biomass, recruitment and age structure, but total population estimates generally aligned with outputs from spatially aggregated models. Moreover, the spatial model identified ontogenetic movement patterns for this highly mobile species. Overall, the spatially aggregated model for Alaska sablefish is likely adequate for management advice, but periodic spatial model updates could offer insights into spatial dynamics and regional depletion levels. Thus, we recommend concomitant use of both models: spatially aggregated models for informing population‐wide status, and spatial models for informing spatial fishery dynamics and local depletion. The sablefish application represents one of the first implementations of a spatial stock assessment using recently proposed good practices, serving as a valuable guide for future practitioners by underscoring critical decision points and analyses to address them when developing spatial stock assessments.

Gross pathology and epidemiological features of mule deerpox virus infections in farmed white-tailed deer (Odocoileus virginianus) in Florida - An-Chi Cheng; Pedro H.O. Viadanna; Tracey L. Moquin; Laura Roldan; John A. Lednicky; Samantha M. Wisely; Kuttichantran Subramaniam; Juan M. Campos Krauer (Veterinary Microbiology, 2025)

Strategies for enhancing landscape thermal comfort in traffic squares under extreme heat - L. Dong; J. Li; X. Cheng; Y. Luo (International Journal of Environmental Science and Technology, 2025)

Estimating carbon sink potential of urban green space plants using light response curves: a case study of native plants in Chongqing - L. Dong; Y. Wang; X. Cheng; Y. Luo (International Journal of Environmental Science and Technology, 2025)

Coding odor modality in piriform cortex efficiently with low-dimensional subspaces: a shared covariance decoding approach - Delaney M. Selb; Andrea K. Barreiro; Shree Hari Gautam; Woodrow L. Shew; Cheng Ly (Biological Cybernetics, 2025)

Unexpected Sr enrichment in karst lacustrine sediments associated with warming and rapid socio-economic development - Xiang Gu; Peng Xing; Cheng Zhao; Xiaotong Han; Di Xu; Qinglong L. Wu; Fengchang Wu (Journal of Cleaner Production, 2025)

Fast arc retreat in the eastern Mediterranean: constraints from late Campanian forearc deposits (Donousa, Greece) - S. O. Martha; P. Xypolias; C. Cheng; W. Dörr; A. Gerdes; D. C. Hezel; M. Kutzschbach; L. Millonig; H. Schmeling; H. R. Marschall; W. Müller; G. Zulauf (International Journal of Earth Sciences, 2025)
The island of Donousa consists of a variegated metasedimentary sequence cut by arc-type granitoid dykes. Detrital zircon U–Pb ages and the presence of volcanic and ultramafic detritus suggest that the protoliths of the metasedimentary rocks were deposited in a Campanian forearc basin later than 76 Ma. D1 stacking of the forearc deposits occurred at upper crustal levels (P max = 0.4 GPa) with staurolite present as a stable phase. The subsequent isobaric heating led to growth of andalusite followed by D2 extension in the stability field of sillimanite, K-feldspar and high-quartz ( P = 0.3 GPa, T = 660 °C). Based on U–Pb ages of garnet (74.6 + 2.3/ − 2.5 Ma) and zircon (74.0 ± 0.8 Ma), separated from an early monzogranite dyke, the timing of forearc deposition, Buchan metamorphism, D2 extension and dyke emplacement is constrained to a maximum period of 2.6 m.y. in the late Campanian. Cooling below T = ca. 600 °C occurred during the Maastrichtian (71.3 + 0.6/ − 1.3 Ma, U–Pb on titanite) and was followed by D3 folding under greenschist facies conditions. A younger generation of Danian granitoid dykes (64.1 + 0.9/ − 1.4 Ma, U–Pb on titanite; 60 ± 4 Ma, Rb–Sr on muscovite) intruded at higher structural levels and was associated with a pervasive fluid-assisted overprint. The sequence of forearc deposition, burying, Buchan metamorphism, extension, and igneous dyking within < 2.6 m.y. is strong evidence for fast (ca. 4 cm a −1 ) trenchward arc retreat that was probably related to late Campanian subduction accretion and magmatic flare-up. Graphical abstract

Developing an integrated CO2 capture and mineralization process with lower energy consumption - K. H. Tham; T. Seah; Q. Y. Kouk; W. Goh; S. Cheng; C. Wang; J. Bu; L. Tao (International Journal of Energy and Water Resources, 2025)

Interannual variability and trends of gross primary production and transpiration in savannas and grasslands from 2000 to 2021 - Cheng Meng; Xiangming Xiao; Li Pan; Baihong Pan; Russell L. Scott; Pradeep Wagle; Chenchen Zhang; Yuan Yao; Yuanwei Qin (Frontiers of Earth Science, 2025)

Extreme Drought Decreases the Stability of Above‐ but Not Below‐Ground Productivity Across Eurasian Steppes - Yingjie Yan; Chong Xu; Yann Hautier; Hongqiang Wang; Yuguang Ke; Honghui Wu; Jinsong Wang; Changjin Cheng; Xiaoan Zuo; Wentao Luo; Melinda D. Smith; Alan K. Knapp; et al. (Global Change Biology, 2025)
Ecological stability plays a crucial role in determining the sustainability of ecosystem functioning and nature's contribution to people. Although the disruptive effects of extreme drought on ecosystem structure and functions are widely recognized, their effect on the stability of above‐ and belowground productivity remains understudied. We assessed the effects of drought on ecosystem stability using a 3‐year drought experiment established in six Eurasian steppe grasslands. The treatments imposed included ambient precipitation, chronic drought (66% reduction in precipitation throughout the growing season), and intense drought (complete exclusion of precipitation for two months during the growing season). We found that drought, irrespective of how it was imposed, reduced the stability of aboveground net primary productivity (ANPP) but had little impact on belowground net primary productivity (BNPP) stability. Reduced ANPP stability under drought was primarily attributed to changes in subordinate species stability, with mean annual precipitation (MAP) and its variability, historical drought frequency, and the aridity index (AI) also influencing responses to extreme drought. In contrast, BNPP stability was not related to any community factor investigated, but it was influenced by MAP variability and AI. Our findings that above‐ and belowground productivity stability in grasslands are differentially sensitive to multi‐year extreme drought under both common (MAP and AI) as well as unique drivers (plant community changes) highlight the complexity of predicting carbon cycle dynamics as hydrological extremes become more severe.

Cross-cultural evidence that intergroup conflict heightens preferences for dominant leaders: A 25-country study - Lasse Laustsen; Xiaotian Sheng; M. Ghufran Ahmad; Laith Al-Shawaf; Benjamin Banai; Irena Pavela Banai; Michael Barlev; Nicolas Bastardoz; Alexander Bor; Joey T. Cheng; Anna Chmielińska; Alexandra Cook; et al. (Evolution and Human Behavior, 2025)

Systematics and evolutionary history of raft and nursery‐web spiders (Araneae: Dolomedidae and Pisauridae) - Kuang‐Ping Yu; Ren‐Chung Cheng; Charles R. Haddad; Akio Tanikawa; Brogan L. Pett; Luis N. Piacentini; Ho Yin Yip; Yuya Suzuki; Arnaud Henrard; Christina J. Painting; Cor J. Vink; Eileen A. Hebets; et al. (Zoologica Scripta, 2025)
Pisauridae are a global and heterogeneous assemblage of spider genera with diverse morphologies and lifestyles. So far, the monophyly of Pisauridae and the inclusion of fishing spiders ( Dolomedes ) in this family have not been thoroughly tested. Here, we amend the systematics and classification of these lineages within a UCE phylogenomic framework and through a detailed morphological reappraisal. For estimations of their evolutionary age, we perform and compare outcomes from two divergence estimation approaches, an a posteriori likelihood, and an a priori Bayesian. Phylogenies reject the monophyly of both Pisauridae and Dolomedes : (1) Focal Clade I groups true Pisauridae genera including Pisaura ; (2) Focal Clade II contains Blandinia and is sister to Trechaleidae and Lycosidae; (3) Focal Clade III groups Dolomedes , Megadolomedes , and Ornodolomedes , and is sister to Blandinia , Trechaleidae, and Lycosidae. We therefore propose to delimit Pisauridae by removing Dolomedidae rank resurrected (including Dolomedes , Bradystichus , Megadolomedes , Caledomedes , Mangromedes , Ornodolomedes , and Tasmomedes ) and Blandinia incertae sedis . Likelihood and Bayesian time calibration approaches yield comparable divergence estimations: Pisauridae origin is estimated at 29–40 Ma; Blandinia 21–34 Ma; Dolomedidae 10–17 Ma; Dolomedes 9–16 Ma. Reconstructions suggest that the evolution of terrestrial and web‐building lifestyles from semi‐aquatic ancestors in Pisauridae coincided with cooling and drying climates during the mid‐Miocene, but this was not the case in the few recent cases of terrestrialization in Dolomedes species. This historic reconstruction illustrates how climatic changes, or rapid radiation, can drive lifestyle diversification.

Misspecifying Sex‐Structured Dynamics in Stock Assessment Models - Matthew L. H. Cheng; Daniel R. Goethel; Peter‐John F. Hulson; Michael J. Wilberg; Craig Marsh; Curry J. Cunningham (Fish and Fisheries, 2025)
Sex‐specific variation in population demography and life‐history traits (e.g., growth, natural mortality) is common in many fish populations. Differences in these processes by sex can dictate population dynamics and influence how harvesters interact with the resource. Across various fisheries management systems, stock assessment models (SAMs), which mathematically represent population age and/or size structure, are widely utilised to estimate fish population status and provide sustainable harvest recommendations. However, few studies have examined the implications of alternative modelling assumptions when incorporating sex‐specific dynamics in SAMs. For instance, the impacts of simultaneously ignoring sex‐specific variations in growth, selectivity, and natural mortality on SAM performance have not been explored. In this study, a simulation‐estimation framework was developed for a sexually dimorphic fish population to: (1) assess the consequences of ignoring sexual dimorphism (i.e., growth, natural mortality, and selectivity) and the benefits of using sex‐specific catch data to inform the estimation of these processes, (2) evaluate the implications of incorrect modelling assumptions regarding sex ratio at birth, and (3) develop advice for parameterising observation likelihoods to describe sex‐specific composition data. Correctly parameterising sex‐specific variation in life‐history traits led to more robust population estimates and catch advice. Conversely, SAMs ignoring these variations yielded biased estimates of biomass and harvest recommendations. Collectively, our results underscore that oversimplified assumptions about sex‐specific variations in SAMs can lead to poor management advice. Moreover, results emphasise the need for routine collection of sex‐specific data to support the development of biologically realistic models.

Dissimilatory nitrate reduction pathways drive high nitrous oxide emissions and nitrogen retention under the flash drought in the largest freshwater lake in China - Rui Su; Dayong Zhao; Xiaomin Zhang; Hongjie Zhang; Junxiang Cheng; Ligang Xu; Qinglong L. Wu; Jin Zeng (Water Research, 2025)

Predictability and applicability evaluation of winter temperatures in China based on Eurasian Arctic sea ice concentrations in autumn - Y. Ma; L. Zhao; J.-S. Wang; Q. Wu; X. Li; Q. Li; W. Cheng; T. Yu; L. Sun (Polar Science, 2025)

GRANDlib: A simulation pipeline for the Giant Radio Array for Neutrino Detection (GRAND) - R. Alves Batista; A. Benoit-Lévy; T. Bister; M. Bohacova; M. Bustamante; W. Carvalho; Y. Chen; L. Cheng; S. Chiche; J.M. Colley; P. Correa; N. Cucu Laurenciu; et al. (Computer Physics Communications, 2025)

Impact thermal and calcium oxide pretreatment on the anaerobic digestion of food waste: performance and carbon emissions - Y. Liu; L. Tian; W. Qiu; W. Sun; C. Pan; G. Fan; Q. Cheng (International Journal of Environmental Science and Technology, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

A high-resolution multiproxy speleothem record of Eastern China hydroclimate variation during last glacial maximum - Shuyu Xue; Hongbin Zhang; Michael L. Griffiths; Chengfei He; Yitao Liu; Junhua Huang; Hai Cheng; Wei Guo; Shitou Wu; Jianzong Zhou; Youfeng Ning; Lin Chen; et al. (Quaternary Science Reviews, 2025)

Thermodynamic analysis of the effect of palm stearin on fully hydrogenated soybean oil coatings in granular micronutrient premixes - Y.K. Kiki Chan; Fletcher Han; Yu-Ling Cheng; Levente L. Diosady (Food Chemistry, 2025)

Epilimnetic oligotrophication increases contribution of oxic methane production to atmospheric methane flux from stratified lakes - Fan Xun; Muhua Feng; Cheng Zhao; Wenlei Luo; Xiaotong Han; Zhen Ci; Yifan Yin; Rong Wang; Qinglong L. Wu; Hans-Peter Grossart; Peng Xing (Water Research, 2025)

Methylparaben changes the community composition, structure, and assembly processes of free-living bacteria, phytoplankton, and zooplankton - Man Wang; Shengxing Wang; Huabing Li; Zhendu Mao; Yiwei Lu; Yunshan Cheng; Xiaotong Han; Yujing Wang; Yanru Liu; Shiqiang Wan; Li-Jun Zhou; Qinglong L. Wu (Environmental Research, 2024)

North Atlantic Heat Transport Convergence Derived from a Regional Energy Budget Using Different Ocean Heat Content Estimates - B. Meyssignac; S. Fourest; Michael Mayer; G. C. Johnson; F. M. Calafat; M. Ablain; T. Boyer; L. Cheng; D. Desbruyères; G. Forget; D. Giglio; M. Kuusela; et al. (Surveys in Geophysics, 2024)
This study uses an oceanic energy budget to estimate the ocean heat transport convergence in the North Atlantic during 2005–2018. The horizontal convergence of the ocean heat transport is estimated using ocean heat content tendency primarily derived from satellite altimetry combined with space gravimetry. The net surface energy fluxes are inferred from mass-corrected divergence of atmospheric energy transport and tendency of the ECMWF ERA5 reanalysis combined with top-of-the-atmosphere radiative fluxes from the clouds and the Earth’s radiant energy system project. The indirectly estimated horizontal convergence of the ocean heat transport is integrated between the rapid climate change-meridional overturning circulation and heatflux array (RAPID) section at 26.5°N (operating since 2004) and the overturning in the subpolar north atlantic program (OSNAP) section, situated at 53°–60°N (operating since 2014). This is to validate the ocean heat transport convergence estimate against an independent estimate derived from RAPID and OSNAP in-situ measurements. The mean ocean energy budget of the North Atlantic is closed to within ± 0.25 PW between RAPID and OSNAP sections. The mean oceanic heat transport convergence between these sections is 0.58 ± 0.25 PW, which agrees well with observed section transports. Interannual variability of the inferred oceanic heat transport convergence is also in reasonable agreement with the interannual variability observed at RAPID and OSNAP, with a correlation of 0.54 between annual time series. The correlation increases to 0.67 for biannual time series. Other estimates of the ocean energy budget based on ocean heat content tendency derived from various methods give similar results. Despite a large spread, the correlation is always significant meaning the results are robust against the method to estimate the ocean heat content tendency.

Integrating HRMAS-NMR Data and Machine Learning-Assisted Profiling of Metabolite Fluxes to Classify Low- and High-Grade Gliomas - Safia Firdous; Zubair Nawaz; Rizwan Abid; Leo L. Cheng; Syed Ghulam Musharraf; Saima Sadaf (Interdisciplinary Sciences: Computational Life Sciences, 2024)

Pre-treatments to reduce metabolism in adult green-lipped mussel, Perna canaliculus, in preparation for live transportation - M. C. F. Cheng; L. N. Zamora; N. L. C. Ragg; A. J. R. Hickey; B. J. Dunphy (Aquaculture International, 2024)
Improved sustainability of aquaculture can be achieved by reducing product wastage post-harvest. Aquaculture of the green-lipped mussel, Perna canaliculus , is an important industry for New Zealand, which increasingly exports to live markets. Live transport can keep mussels fresh, but mussels could also be susceptible to handling stresses. To remedy this, pre-treatments that make mussels metabolically depressed, and thus potentially less sensitive to external stressors, were explored. As indicators of depressed metabolism, heart rate (HR), inferred cardiac output (PCO), and relative gaping magnitude (RGM) were simultaneously monitored in mussels experiencing different temperatures, dissolved oxygen levels and anaesthetic (MgCl 2 ) concentrations to compare their efficacy in inducing suppressed metabolism of adult P. canaliculus . We found complex interactions between HR, PCO, and RGM in response to these conditions; however, overall, these response variables were significantly correlated. Mussels showed depressed HR and PCO by up to 100% at 4 °C within 2 h, with correspondingly decreased RGM of up to 48%. Similarly, mussels immersed in 40 g L −1 MgCl 2 suppressed HR by up to 97%, accompanied by up to 76% decrease in PCO, and a slight increase in RGM (11%) after 2 h. While responses were variable, low DO levels suppressed HR by up to 50%, yet PCO and RGM increased two- and threefold relative to control groups. The results of the present study indicated that 4 °C and 40 g MgCl 2 L −1 were more effective conditions as pre-treatments than low dissolved oxygen lower the metabolism of P. canaliculus before live transport.

Successful Invasion Into New Environments Without Evidence of Rapid Adaptation by a Predatory Marine Gastropod - Blair P. Bentley; Brian S. Cheng; Reid S. Brennan; John D. Swenson; Jamie L. Adkins; Andrew R. Villeneuve; Lisa M. Komoroske (Molecular Ecology, 2024)
Invasive species with native ranges spanning strong environmental gradients are well suited for examining the roles of selection and population history in rapid adaptation to new habitats, providing insight into potential evolutionary responses to climate change. The Atlantic oyster drill ( Urosalpinx cinerea ) is a marine snail whose native range spans the strongest coastal latitudinal temperature gradient in the world, with invasive populations established on the US Pacific coast. Here, we leverage this system using genome‐wide SNPs and environmental data to examine invasion history and identify genotype–environment associations indicative of local adaptation across the native range, and then assess evidence for allelic frequency shifts that would signal rapid adaptation within invasive populations. We demonstrate strong genetic structuring among native regions which aligns with life history expectations, identifying southern New England as the source of invasive populations. Then, we identify putatively thermally adaptive loci across the native range but find no evidence of allele frequency shifts in invasive populations that suggest rapid adaptation to new environments. Our results indicate that while these loci may underpin local thermal adaptation in their native range, selection is relaxed in invasive populations, perhaps due to complex polygenic architecture underlying thermal traits and/or standing capacity for phenotypic plasticity. Given the prolific invasion of Urosalpinx , our study suggests population success in new environments is influenced by factors other than selection on standing genetic variation that underlies local adaptation in the native range and highlights the importance of considering population history and environmental selection pressures when evaluating adaptive capacity.

Seasonal wet–dry transition and denitrifying communities contributed to nitrous oxide emissions in the water-level fluctuating zone of the largest freshwater lake in China - Rui Su; Dayong Zhao; Xiaomin Zhang; Zixu Guo; Junxiang Cheng; Zhongbo Yu; Ligang Xu; Qinglong L. Wu; Jin Zeng (Journal of Hydrology, 2024)

Developing reliable and valid measures for evaluating collaborative governance and adaptability: An example from the Collaborative Forest Landscape Restoration Program - Tyler A. Beeton; Tara L. Teel; Melanie M. Colavito; Nicolena vonHedemann; Ch'aska Huayhuaca; Antony S. Cheng; Benjamin Ghasemi; Adam J. Snitker (Journal of Environmental Management, 2024)

Dynamic interactions between groundwater level and discharge by phreatophytes - Cheng-Wei Huang; Jean-Christophe Domec; Thomas L. O’Halloran; Samantha Hartzell (Advances in Water Resources, 2024)

Predation on Live and Artificial Insect Prey Shows Different Global Latitudinal Patterns - Elena L. Zvereva; Benjamin Adroit; Tommi Andersson; Craig R. A. Barnett; Sofia Branco; Bastien Castagneyrol; Giancarlo Maria Chiarenza; Wesley Dáttilo; Ek del‐Val; Jan Filip; Jory Griffith; Anna L. Hargreaves; et al. (Global Ecology and Biogeography, 2024)
Aim Long‐standing theory predicts that the intensity of biotic interactions increases from high to low latitudes. Studies addressing geographic variation in predation on insect prey have often relied on prey models, which lack many characteristics of live prey. Our goals were to explore global latitudinal patterns of predator attack rates on standardised live insect prey and to compare the patterns in predation on live insects with those on plasticine prey models. Location Global forested areas. Time Period 2021–2023. Major Taxa Arthropods, birds. Methods We measured predation rates in 43 forested locations distributed across five continents from 34.1° S to 69.5° N latitude. At each location, we exposed 20 sets of three bait types, one set per tree. Each set included three live fly larvae (maggots), three live fly puparia and three plasticine models of the puparia. We used glue rings to isolate half of the sets from non‐flying predators. Results Arthropod attack rates on plasticine prey decreased linearly from low to high latitudes, whereas attack rates on maggots had a U shaped distribution, with the lowest predation rates at temperate latitudes and the highest rates at tropical and boreal latitudes. This difference emerged from intensive predator attacks on live maggots, but not on plasticine models, in boreal sites. Site‐specific attack rates of arthropod predators on live and plasticine prey were not correlated. In contrast, bird attack rates on live maggots and plasticine models were positively correlated, but did not show significant latitudinal changes. Main Conclusions Latitudinal patterns in predation differ between major groups of predators and between types of prey. Poleward decreases in both arthropod and combined arthropod and bird predation on plasticine models do not mirror patterns of predation on our live prey, the latter likely reflecting real patterns of predation risk better than do patterns of attack on artificial prey.

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

A Prospective Cohort Study of the Impact of Maternal Avocado Consumption During Pregnancy on Offspring Allergic Diseases: The Kuopio Birth Cohort Study (KuBiCo) - F. Cheng; S. Hantunen; L. Keski-Nisula; K. Backman; N. Ford (Journal of the Academy of Nutrition and Dietetics, 2024)

How is Excitotoxicity Being Modelled in iPSC-Derived Neurons? - Jan L. Cheng; Anthony L. Cook; Jana Talbot; Sharn Perry (Neurotoxicity Research, 2024)
Excitotoxicity linked either to environmental causes (pesticide and cyanotoxin exposure), excitatory neurotransmitter imbalance, or to intrinsic neuronal hyperexcitability, is a pathological mechanism central to neurodegeneration in amyotrophic lateral sclerosis (ALS). Investigation of excitotoxic mechanisms using in vitro and in vivo animal models has been central to understanding ALS mechanisms of disease. In particular, advances in induced pluripotent stem cell (iPSC) technologies now provide human cell-based models that are readily amenable to environmental and network-based excitotoxic manipulations. The cell-type specific differentiation of iPSC, combined with approaches to modelling excitotoxicity that include editing of disease-associated gene variants, chemogenetics, and environmental risk-associated exposures make iPSC primed to examine gene-environment interactions and disease-associated excitotoxic mechanisms. Critical to this is knowledge of which neurotransmitter receptor subunits are expressed by iPSC-derived neuronal cultures being studied, how their activity responds to antagonists and agonists of these receptors, and how to interpret data derived from multi-parameter electrophysiological recordings. This review explores how iPSC-based studies have contributed to our understanding of ALS-linked excitotoxicity and highlights novel approaches to inducing excitotoxicity in iPSC-derived neurons to further our understanding of its pathological pathways.

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Investigation of oxygen packaging to maintain beef color stability and microbiology safety after periods of long-term superchilled storage - Jun Yang; Xue Chen; Xinxin Duan; Ke Li; Haijian Cheng; Ge Sun; Xin Luo; David L. Hopkins; Benjamin W.B. Holman; Yimin Zhang; Enliang Song (Meat Science, 2024)

Inclined loading of suction caisson anchors in calcareous sand with particle breakage - L. Cheng; M.S. Hossain; Y. Hu; S.N. Ullah; Y.H. Kim (Computers and Geotechnics, 2024)

Mild chemical recycling of carbon fiber-reinforced epoxy composites in aqueous buffers and development of hydrothermally recyclable vitrimer composites from recyclates - Cheng Hao; Baoming Zhao; Lin Shao; Yiding Cao; Mingen Fei; Wangcheng Liu; Tuan Liu; Yu-Chung Chang; Kevin L. Simmons; Jinwen Zhang (Resources, Conservation and Recycling, 2024)

Wheat bran layers: composition, structure, fractionation, and potential uses in foods - Zhongwei Chen; Andrew L. Mense; Lauren R. Brewer; Yong-Cheng Shi (Critical Reviews in Food Science and Nutrition, 2024)

Creating Boundary Objects Supports Knowledge Co-development Processes: A Case Study Evaluation from the Colorado Front Range - Hannah L C Brown; Antony S Cheng; Nehalem C Clark; Andrew W Slack; Brett H Wolk (Journal of Forestry, 2024)
This qualitative case study evaluates manager and researcher perceptions of the impact of a place-based, collaborative knowledge co-development process and examines the outcomes of that co-development for changes to management approaches. The USDA Forest Service (Forest Service) Rocky Mountain Research Station General Technical Report 373 (GTR-373) is a codeveloped science synthesis that functions as a boundary object providing a framework for planning, designing, and implementing management action for restoration of ponderosa and dry mixed-conifer forests. The process of creating and socializing the GTR-373 framework fostered continual knowledge exchange and engagement between researchers and managers across different organizations and levels of decision-making. This built trust in the information, improved justification for management action, developed a common foundation for cross-boundary implementation, and increased communication. The framework has been applied across jurisdictions and has been used as a foundational tool for training staff and designing projects. However, adapting the GTR-373 framework across scales remains challenging. Study Implications: This qualitative case study evaluates a co-development process in which researchers and managers from multiple organizations and agencies collaborated to produce a science-informed restoration framework to support forest management on the Colorado Front Range (GTR-373). The process built trust, improved justification for management action, developed a common foundation for implementation, and increased communication. However, cross-boundary management across spatial scales remains challenging, and managers interpret information through organizational mandates and site-specific context. Sustained collaboration between researchers and land managers can help make science actionable and relevant at the appropriate scale for planning and management across expertise and jurisdictional boundaries.

GHK-Cu/Pionin-loaded in situ electrospun PVB/PVP smart dressing promotes wound healing via anti-oxidant, anti-inflammatory, antimicrobial, and tissue regenerative effects - Yan Wang; Zhichao Zheng; Janak L. Pathak; Haoyu Cheng; Sizhen Huang; Zi Fu; Ping Li; Lihong Wu; Huade Zheng (Chemical Engineering Journal, 2024)

Efficient nutrient recycling from wastewater to deserts: A comparative study on biocrust cyanobacteria performance - Li Wu; Cheng Zhang; Ashiwin Vadiveloo; María L. Montes; Ling Xia; Shaoxian Song; Mariela A. Fernandez; Shubin Lan (Chemical Engineering Journal, 2024)

Major source categories of PM2.5 oxidative potential in wintertime Beijing and surroundings based on online dithiothreitol-based field measurements - Rico K.Y. Cheung; Lu Qi; Manousos I. Manousakas; Joseph V. Puthussery; Yan Zheng; Theodore K. Koenig; Tianqu Cui; Tiantian Wang; Yanli Ge; Gaoyuan Wei; Yu Kuang; Mengshuang Sheng; et al. (Science of The Total Environment, 2024)

Antimicrobial residues in meat from chickens in Northeast Vietnam: analytical validation and pilot study for sampling optimisation - Sophie Hedges; Ludovic Pelligand; Liwei Chen; Kelyn Seow; Thuy Thi Hoang; Huong Quynh Luu; Son Thi Thanh Dang; Ngoc Thi Pham; Hoa Thi Thanh Pham; Yeong Cheng Cheah; Yulan Wang; Dominique Hurtaud-Pessel; et al. (Journal of Consumer Protection and Food Safety, 2024)
Antimicrobials used in chicken farming for therapeutic and/or prophylactic purposes may result in unacceptable levels of edible residues, if withdrawal periods are not respected. To evaluate the risk in Vietnam, we validated an analytical method to detect antimicrobial residues from chicken meat samples and carried out a pilot cross-sectional study to identify optimal sampling strategies. A total of 45 raw meat samples were collected from 4 markets, 1 slaughterhouse and 4 farms (5 per site) in Northern Vietnam, between March and April 2021. Farmers were asked about antimicrobials used during sampled production cycles (5 chickens sampled per batch). Samples were analysed using liquid chromatography-tandem mass spectrometry for the presence of 68 antimicrobials at a pre-defined validation concentration. 7 compounds were identified from 4 classes (tetracyclines, sulphonamides, macrolides, and fluoroquinolones). In markets, where the source of sampled chickens was unknown, a diverse pool of residual antimicrobials was detected in 20% (4/20) of the meat samples. No residues were detected in samples from the slaughterhouse. No residues were detected in chickens from the one farm that reported using antimicrobials, whereas sulfadimethoxine, doxycycline and tilmicosin residues were identified from the other 3 farms reporting no antimicrobial use. The probability of detecting antimicrobial residues present in a flock based on sampling a single chicken was estimated at 0.93 (highest density interval 0.735–0.997). The preliminary results suggest a disparity between farmers’ reports on antimicrobial drug use and actual usage, and that the analysis of a single sample per farm has a high probability of detecting antimicrobial residues, if present.

Combining camera trap surveys and IUCN range maps to improve knowledge of species distributions - Cheng Chen; Alys Granados; Jedediah F. Brodie; Roland Kays; T. Jonathan Davies; Runzhe Liu; Jason T. Fisher; Jorge Ahumada; William McShea; Douglas Sheil; Jayasilan Mohd‐Azlan; Bernard Agwanda; et al. (Conservation Biology, 2024)
Reliable maps of species distributions are fundamental for biodiversity research and conservation. The International Union for Conservation of Nature (IUCN) range maps are widely recognized as authoritative representations of species’ geographic limits, yet they might not always align with actual occurrence data. In recent area of habitat (AOH) maps, areas that are not habitat have been removed from IUCN ranges to reduce commission errors, but their concordance with actual species occurrence also remains untested. We tested concordance between occurrences recorded in camera trap surveys and predicted occurrences from the IUCN and AOH maps for 510 medium‐ to large‐bodied mammalian species in 80 camera trap sampling areas. Across all areas, cameras detected only 39% of species expected to occur based on IUCN ranges and AOH maps; 85% of the IUCN only mismatches occurred within 200 km of range edges. Only 4% of species occurrences were detected by cameras outside IUCN ranges. The probability of mismatches between cameras and the IUCN range was significantly higher for smaller‐bodied mammals and habitat specialists in the Neotropics and Indomalaya and in areas with shorter canopy forests. Our findings suggest that range and AOH maps rarely underrepresent areas where species occur, but they may more often overrepresent ranges by including areas where a species may be absent, particularly at range edges. We suggest that combining range maps with data from ground‐based biodiversity sensors, such as camera traps, provides a richer knowledge base for conservation mapping and planning.

Mechanism of organic phosphorus transformation and its impact on the primary production in a deep oligotrophic plateau lake during stratification - Xiaotong Han; Fan Xun; Xianlong Zhu; Cheng Zhao; Wenlei Luo; Yanru Liu; Man Wang; Di Xu; Shiqiang Wan; Qinglong L. Wu; Peng Xing (Water Research, 2024)

Iron-containing nanominerals for sustainable phosphate management: A comprehensive review and future perspectives - Teng Bao; Mekdimu Mezemir Damtie; Chu Yan Wang; Cheng Long Li; Zhijie Chen; Kuk CHO; Wei Wei; Peng Yuan; Ray L. Frost; Bing-Jie Ni (Science of The Total Environment, 2024)

Investigating the uses of machine learning algorithms to inform risk factor analyses: The example of avian infectious bronchitis virus (IBV) in broiler chickens - Magnus R. Campler; Ting-Yu Cheng; Chang-Won Lee; Charles L. Hofacre; Geoffrey Lossie; Gustavo S. Silva; Mohamed M. El-Gazzar; Andréia G. Arruda (Research in Veterinary Science, 2024)

Variation in patterns of second primary malignancies across U.S. race and ethnicity groups: a Surveillance, Epidemiology, and End Results (SEER) analysis - Valerie McGuire; Daphne Y. Lichtensztajn; Li Tao; Juan Yang; Christina A. Clarke; Anna H. Wu; Lynne Wilkens; Sally L. Glaser; Sungshim Lani Park; Iona Cheng (Cancer Causes & Control, 2024)

On the brink of explosion? Identifying the source and potential spread of introduced Zosterops white-eyes in North America - Devon A. DeRaad; Marlon E. Cobos; Natalie R. Hofmeister; Lucas H. DeCicco; Madhvi X. Venkatraman; Isao Nishiumi; Bailey McKay; Fa-Sheng Zou; Kazuto Kawakami; Chang-Hoe Kim; Ruey-Shing Lin; Cheng-Te Yao; et al. (Biological Invasions, 2024)

Nucleocytoplasmic shuttling of BEFV M protein-modulated by lamin A/C and chromosome maintenance region 1 through a transcription-, carrier- and energy-dependent pathway - Yu-Kang Chang; Yi-Jyum Lin; Ching-Yuan Cheng; Pei-Chien Tsai; Chi-Young Wang; Brent L. Nielsen; Hung-Jen Liu (Veterinary Microbiology, 2024)

Introducing Elinor for monitoring the governance and management of area‐based conservation - Shauna L. Mahajan; Samson Obiene; Lenice Ojwang; Nasser Olwero; Abel Valdivia; Adaoma Wosu; Emily Adrid; Dominic A. Andradi‐Brown; Gildas Andriamalala; Natalie C. Ban; Nathan J. Bennett; Jessica Blythe; et al. (Conservation Biology, 2024)
Monitoring the governance and management effectiveness of area‐based conservation has long been recognized as an important foundation for achieving national and global biodiversity goals and enabling adaptive management. However, there are still many barriers that prevent conservation actors, including those affected by governance and management systems from implementing conservation activities and programs and from gathering and using data on governance and management to inform decision‐making across spatial scales and through time. We explored current and past efforts to assess governance and management effectiveness and barriers actors face in using the resulting data and insights to inform conservation decision‐making. To help overcome these barriers, we developed Elinor, a free and open‐source monitoring tool that builds on the work of Nobel Prize winner Elinor Ostrom to facilitate the gathering, storing, sharing, analyzing, and use of data on environmental governance and management across spatial scales and for areas under different governance and management types. We consider the process of codesigning and piloting Elinor with conservation scientists and practitioners and the main components of the assessment and online data system. We also consider how Elinor complements existing approaches by addressing governance and management in a single assessment at a high level for different types of area‐based conservation, providing flexible options for data collection, and integrating a data system with an assessment that can support data use and sharing across different spatial scales, including global monitoring of the Global Biodiversity Framework. Although challenges will continue, the process of developing Elinor and the tool itself offer tangible solutions to barriers that prevent the systematic collection and use of governance and management data. With broader uptake, Elinor can play a valuable role in enabling more effective, inclusive, and durable area‐based conservation.

Sitagliptin elevates plasma and CSF incretin levels following oral administration to nonhuman primates: relevance for neurodegenerative disorders - Yazhou Li; Kelli L. Vaughan; Yun Wang; Seong-Jin Yu; Eun-Kyung Bae; Ian A. Tamargo; Katherine O. Kopp; David Tweedie; Cheng-Chuan Chiang; Keith T. Schmidt; Debomoy K. Lahiri; Michael A. Tones; et al. (GeroScience, 2024)
The endogenous incretins glucagon-like peptide-1 (GLP-1) and glucose-dependent insulinotropic polypeptide (GIP) possess neurotrophic, neuroprotective, and anti-neuroinflammatory actions. The dipeptidyl peptidase 4 (DPP-4) inhibitor sitagliptin reduces degradation of endogenous GLP-1 and GIP, and, thereby, extends the circulation of these protective peptides. The current nonhuman primate (NHP) study evaluates whether human translational sitagliptin doses can elevate systemic and central nervous system (CNS) levels of GLP-1/GIP in naive, non-lesioned NHPs, in line with our prior rodent studies that demonstrated sitagliptin efficacy in preclinical models of Parkinson’s disease (PD). PD is an age-associated neurodegenerative disorder whose current treatment is inadequate. Repositioning of the well-tolerated and efficacious diabetes drug sitagliptin provides a rapid approach to add to the therapeutic armamentarium for PD. The pharmacokinetics and pharmacodynamics of 3 oral sitagliptin doses (5, 20, and 100 mg/kg), equivalent to the routine clinical dose, a tolerated higher clinical dose and a maximal dose in monkey, were evaluated. Peak plasma sitagliptin levels were aligned both with prior reports in humans administered equivalent doses and with those in rodents demonstrating reduction of PD associated neurodegeneration. Although CNS uptake of sitagliptin was low (cerebrospinal fluid (CSF)/plasma ratio 0.01), both plasma and CSF concentrations of GLP-1/GIP were elevated in line with efficacy in prior rodent PD studies. Additional cellular studies evaluating human SH-SY5Y and primary rat ventral mesencephalic cultures challenged with 6-hydroxydopamine, established cellular models of PD, demonstrated that joint treatment with GLP-1 + GIP mitigated cell death, particularly when combined with DPP-4 inhibition to maintain incretin levels. In conclusion, this study provides a supportive translational step towards the clinical evaluation of sitagliptin in PD and other neurodegenerative disorders for which aging, similarly, is the greatest risk factor.

Heterogeneous reactions significantly contribute to the atmospheric formation of nitrated aromatic compounds during the haze episode in urban Beijing - Zhen Cheng; Xinghua Qiu; Ailin Li; Qianqian Chai; Xiaodi Shi; Yanli Ge; Theodore K. Koenig; Yan Zheng; Shiyi Chen; Min Hu; Chunxiang Ye; Rico K.Y. Cheung; et al. (Science of The Total Environment, 2024)

Potassium isotopes as a tracer of hydrothermal alteration in ore systems - Kun-Feng Qiu; Rolf L. Romer; Zheng-Yu Long; Hao-Cheng Yu; Simon Turner; Ruo-Qi Wan; Xiao-Qiang Li; Zi-Yue Gao; Jun Deng (Geochimica et Cosmochimica Acta, 2024)

The dual roles of dissimilatory iron reduction in the carbon cycle: The “iron mesh” effect can increase inorganic carbon sequestration - Cheng Zhao; Fan Xun; Biao Li; Xiaotong Han; Huan Liu; Yingxun Du; Qinglong L. Wu; Peng Xing (Global Change Biology, 2024)
Dissimilatory iron reduction (DIR) can drive the release of organic carbon (OC) as carbon dioxide (CO 2 ) by mediating electron transfer between organic compounds and microbes. However, DIR is also crucial for carbon sequestration, which can affect inorganic‐carbon redistribution via iron abiotic–phase transformation. The formation conditions of modern carbonate‐bearing iron minerals (IC Fe ) and their potential as a CO 2 sink are still unclear. A natural environment with modern IC Fe , such as karst lake sediment, could be a good analog to explore the regulation of microbial iron reduction and sequential mineral formation. We find that high porosity is conducive to electron transport and dissimilatory iron‐reducing bacteria activity, which can increase the iron reduction rate. The iron‐rich environment with high calcium and OC can form a large sediment pore structure to support rapid DIR, which is conducive to the formation and growth of IC Fe . Our results further demonstrate that the minimum DIR threshold suitable for IC Fe formation is 6.65 μmol g −1 dw day −1 . DIR is the dominant pathway (average 66.93%) of organic anaerobic mineralization, and the abiotic‐phase transformation of Fe 2+ reduces CO 2 emissions by ~41.79%. Our findings indicate that as part of the carbon cycle, DIR not only drives mineralization reactions but also traps carbon, increasing the stability of carbon sinks. Considering the wide geographic distribution of DIR and IC Fe , our findings suggest that the “iron mesh” effect may become an increasingly important vector of carbon sequestration.

Microplastics and other anthropogenic fibres in large apex shark species: Abundance, characteristics, and recommendations for future research - Hsuan-Cheng Lu; Julia L. Smith; Shima Ziajahromi; Frederic D.L. Leusch (Chemosphere, 2024)

Assessment of inhalation exposure to microplastic particles when disposable masks are repeatedly used - Jhy-Charm Soo; Chun-Hsuan Wei; Jen-Kun Chen; Guo-Chung Dong; Zhen-Shu Liu; Hsiu-Chuan Chou; Rocio L. Perez; Atin Adhikari; Yu-Cheng Chen (Science of The Total Environment, 2024)

PARSIFAL: A toolkit for triple-GEM parametrized simulation - A. Amoroso; R. Baldini Ferroli; I. Balossino; M. Bertani; D. Bettoni; F. Bianchi; A. Bortone; A. Calcaterra; S. Cerioni; W. Cheng; G. Cibinetto; A. Cotta Ramusino; et al. (Computer Physics Communications, 2024)

Effects of field-aging on the impact of biochar on herbicide fate and microbial community structure in the soil environment - Hongguang Cheng; Dan Xing; Gratien Twagirayezu; Shan Lin; Shangyi Gu; Chenglong Tu; Paul W. Hill; David R. Chadwick; Davey L. Jones (Chemosphere, 2024)

Vector-mediated viral exchange between crops and weedy plants - Xiao-bin Shi; Zhuo Zhang; Fan Li; Evan L. Preisser; Li-ping Huang; De-yong Zhang; Zhan-hong Zhang; Song-bai Zhang; Xu-guo Zhou; An-sheng Zhang; Hui Liu; Yuan-hua Wu; et al. (Journal of Pest Science, 2024)

Fitness costs of pyrethroid resistance in the polyphagous pest mite, Halotydeus destructor, under field conditions - Paul A. Umina; James L. Maino; Owain Edwards; Xuan Cheng; Matthew Binns; Anthony van Rooyen; Sue Vern Song; Andrew Weeks; Aston L. Arthur; Olivia L. Reynolds; Ary A. Hoffmann (Journal of Pest Science, 2024)
The redlegged earth mite, Halotydeus destructor , is an economically important pest of winter field crops and pastures in Australia, and has evolved field resistance to pyrethroid chemicals through a polymorphism in the voltage-gated parasodium channel leading to knockdown resistance ( kdr) . In this study, we quantified the rate of reversion to susceptibility of partially resistant H. destructor populations under field conditions in the absence of pesticide exposure. This was conducted over multiple years at two geographically distant locations with mite populations known to possess pyrethroid resistance. Fitness costs associated with pyrethroid resistance were identified through reductions in the frequency of kdr resistance alleles in the absence of pesticides. This was assessed using an amplicon sequencing approach targeting known resistance alleles. We also found that resistance can increase rapidly in frequency after only a single pyrethroid application in the field. Our results highlight that, once established in H. destructor populations, pyrethroid resistance will not easily be lost even after several years, emphasizing the importance of limiting the evolution of resistance in the first place. This helps to explain why pyrethroid resistance in H. destructor continues to persist at very high frequencies in the field and continues to expand within Australia despite the existence of fitness costs. Understanding field fitness costs associated with pesticide resistance is important when devising resistance management strategies for this pest.

The effects of water temperature on cerebral blood flow during aquatic exercise - Howard H. Carter; Oliver Pienaar; Alexander Coleman; Jem L. Cheng; Maureen J. MacDonald; Louise H. Naylor; Daniel J. Green (European Journal of Applied Physiology, 2024)
Purpose Recent studies suggest that episodic increases in cerebral blood flow (CBF) may contribute to the improvement in brain health associated with exercise training. Optimising CBF during exercise may enhance this benefit. Water immersion in ~ 30–32 °C augments CBF at rest and during exercise; however, the impact of water temperature on the CBF response has not been investigated. We hypothesised that cycle ergometry in water would increase CBF compared to land-based exercise, and that warm water would attenuate the CBF benefits. Methods Eleven young heathy participants (nine males; 23.8 ± 3.1 yrs) completed 30 min of resistance-matched cycle exercise in three separate conditions; non-immersion (Land), 32 °C and 38 °C water immersion up to the level of the waist. Middle cerebral artery velocity (MCAv), blood pressure, and respiratory measures were assessed throughout the exercise bouts. Results Core temperature was significantly higher in the 38 °C immersion than 32 °C (+ 0.84 ± 0.24 vs + 0.04 ± 0.16, P < 0.001), whilst mean arterial pressure was lower during 38 °C exercise compared to Land (84 ± 8 vs 100 ± 14 mmHg, P < 0.001) and 32 °C (92 ± 9, P = 0.03). MCAv was higher in 32 °C immersion compared to the Land and 38 °C conditions throughout the exercise bout (68 ± 10 vs 64 ± 11 vs 62 ± 12 cm/s, P = 0.03 and P = 0.02, respectively). Conclusion Our findings suggest that cycle exercise in warm water attenuates the beneficial impact of water immersion on CBF velocity due to redistribution of blood flow to subserve thermoregulatory demand. Our findings suggest that, whilst water-based exercise can have beneficial effects on cerebrovascular function, water temperature is a key determinant of this benefit.

Intracellular iron accumulation facilitates mycobacterial infection in old mouse macrophages - Stephen K. Kotey; Xuejuan Tan; Owen Fleming; Ramakrishnama Raju Kasiraju; Audrey L. Dagnell; Kyle N. Van Pelt; Janet Rogers; Steven D. Hartson; Nidheesh Thadathil; Ramasamy Selvarani; Rojina Ranjit; Sreemathi Logan; et al. (GeroScience, 2023)
Aging has a significant impact on the immune system, leading to a gradual decline in immune function and changes in the body’s ability to respond to bacterial infections. Non-tuberculous mycobacteria (NTM), also known as atypical mycobacteria or environmental mycobacteria, are commonly found in soil, water, and various environmental sources. While many NTM species are considered opportunistic pathogens, some can cause significant infections, particularly in individuals with compromised immune systems, such as older individuals. When mycobacteria enter the body, macrophages are among the first immune cells to encounter them and attempt to engulf mycobacteria through a process called phagocytosis. Some NTM species, including Mycobacterium avium ( M. avium ) can survive and replicate within macrophages. However, little is known about the interaction between NTM and macrophages in older individuals. In this study, we investigated the response of bone marrow–derived macrophage (BMMs) isolated from young (5 months) and old (25 months) mice to M. avium serotype 4, one of the main NTM species in patients with pulmonary NTM diseases. Our results demonstrated that BMMs from old mice have an increased level of intracellular iron and are more susceptible to M. avium serotype 4 infection compared to BMMs from young mice. The whole-cell proteomic analysis indicated a dysregulated expression of iron homeostasis–associated proteins in old BMMs regardless of mycobacterial infection. Deferoxamine, an iron chelator, significantly rescued mycobacterial killing and phagolysosome maturation in BMMs from old mice. Therefore, our data for the first time indicate that an intracellular iron accumulation improves NTM survival within macrophages from old mice and suggest a potential application of iron-chelating drugs as a host-directed therapy for pulmonary NTM infection in older individuals.

Simulating synergistic effects of climate change and conservation practices on greenhouse gas emissions and crop growth in long-term maize cropping systems - Haomiao Cheng; Qilin Yu; Zhiming Qi; Melissa S. Bukovsky; Lulin Xue; Virginia L. Jin; Liwang Ma; R. Daren Harmel; Xiaoping Chen; Shu Ji; Lingzhan Miao; Shaoyuan Feng (Computers and Electronics in Agriculture, 2023)

Development and application of an interactive generic physiologically based pharmacokinetic (igPBPK) model for adult beef cattle and lactating dairy cows to estimate tissue distribution and edible tissue and milk withdrawal intervals for per- and polyfluoroalkyl substances (PFAS) - Wei-Chun Chou; Lisa A. Tell; Ronald E. Baynes; Jennifer L. Davis; Yi-Hsien Cheng; Fiona P. Maunsell; Jim E. Riviere; Zhoumeng Lin (Food and Chemical Toxicology, 2023)

Associations between total mercury, trace minerals, and blood health markers in Northwest Atlantic white sharks (Carcharodon carcharias) - Lisa M. Crawford; James Gelsleichter; Alisa L. Newton; Lisa A. Hoopes; Cheng-Shiuan Lee; Nicholas S. Fisher; Douglas H. Adams; Maeva Giraudo; Anne E. McElroy (Marine Pollution Bulletin, 2023)

Accelerating evidence-informed decision-making in conservation implementing agencies through effective monitoring, evaluation, and learning - Shauna L. Mahajan; Lydia Tanner; Gabby Ahmadia; Hannah Becker; Nicole DeMello; Robert Fidler; Alastair R. Harborne; Arundhati Jagadish; Morena Mills; Paul Cairney; Samantha Cheng; Brandie Fariss; et al. (Biological Conservation, 2023)

Northern high-latitude sea ice variation linked with East Asian monsoon anomalies during the Younger Dryas - Xiaolong Chen; Hongbin Zhang; Michael L. Griffiths; Xiaogui Peng; Liangzhe Yang; Ming Yu; Junhua Huang; Shuyu Xue; Hai Cheng; Shuai Chen (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

The E3 Ubiquitin Ligase SCF Cyclin F Promotes Sequestosome-1/p62 Insolubility and Foci Formation and is Dysregulated in ALS and FTD Pathogenesis - Jennilee M. Davidson; Sharlynn S. L. Wu; Stephanie L. Rayner; Flora Cheng; Kimberley Duncan; Carlo Russo; Michelle Newbery; Kunjie Ding; Natalie M. Scherer; Rachelle Balez; Alberto García-Redondo; Alberto Rábano; et al. (Molecular Neurobiology, 2023)
Amyotrophic lateral sclerosis (ALS)- and frontotemporal dementia (FTD)-linked mutations in CCNF have been shown to cause dysregulation to protein homeostasis. CCNF encodes for cyclin F, which is part of the cyclin F-E3 ligase complex SCF cyclinF known to ubiquitylate substrates for proteasomal degradation. In this study, we identified a function of cyclin F to regulate substrate solubility and show how cyclin F mechanistically underlies ALS and FTD disease pathogenesis. We demonstrated that ALS and FTD-associated protein sequestosome-1/p62 (p62) was a canonical substrate of cyclin F which was ubiquitylated by the SCF cyclinF complex. We found that SCF cyclin F ubiquitylated p62 at lysine(K)281, and that K281 regulated the propensity of p62 to aggregate. Further, cyclin F expression promoted the aggregation of p62 into the insoluble fraction, which corresponded to an increased number of p62 foci. Notably, ALS and FTD-linked mutant cyclin F p.S621G aberrantly ubiquitylated p62, dysregulated p62 solubility in neuronal-like cells, patient-derived fibroblasts and induced pluripotent stem cells and dysregulated p62 foci formation. Consistently, motor neurons from patient spinal cord tissue exhibited increased p62 ubiquitylation. We suggest that the p.S621G mutation impairs the functions of cyclin F to promote p62 foci formation and shift p62 into the insoluble fraction, which may be associated to aberrant mutant cyclin F-mediated ubiquitylation of p62. Given that p62 dysregulation is common across the ALS and FTD spectrum, our study provides insights into p62 regulation and demonstrates that ALS and FTD-linked cyclin F mutant p.S621G can drive p62 pathogenesis associated with ALS and FTD.

Air quality improvement assessment and exposure risk of Shandong Province in China during 2014 to 2020 - N. N. Wang; C. Y. Zhu; Wei Li; M. Y. Qiu; B. L. Wang; X. Y. Li; B. D. Jiang; X. Y. Qu; Z. S. Li; H. C. Cheng (International Journal of Environmental Science and Technology, 2023)

Environmental optima for common diatoms from Ontario lakes along gradients of lakewater pH, total phosphorus concentration, and depth - Matthew P. Duda; Branaavan Sivarajah; Kathleen M. Rühland; Andrew M. Paterson; Jennifer L. Barrow; Yuanyu Cheng; Elizabeth J. Favot; Kristopher R. Hadley; Roland I. Hall; Kathryn E. Hargan; Clare Nelligan; Euan D. Reavie; et al. (Journal of Paleolimnology, 2023)

Spatiotemporal characteristics of ozone and the formation sensitivity over the Fenwei Plain - H.H. Ren; Y. Cheng; F. Wu; Z.L. Gu; J.J. Cao; Y. Huang; Y.G. Xue; L. Cui; Y.W. Zhang; J.C. Chow; J.G. Watson; R.J. Zhang; et al. (Science of The Total Environment, 2023)

Basic human values of dairy producers in Canada and the U.S.: A cross-sectional survey study - Ting-Yu Cheng; Devon J. Wilson; Cecilia Brooks; Jessica A. Pempek; Kelly A. George; Stephen J. LeBlanc; Claudia Cobo-Angel; David L. Renaud; Gregory G. Habing (Journal of Rural Studies, 2023)

Comparative Analysis of Rhizosphere and Endophytic Microbial Communities Between Root Rot and Healthy Root of Psammosilene tunicoides - Wen. T. Yang; Guo. D. Li; Jun. N. Li; Cheng. F. Yang; Xiao. M. Zhang; Ai. L. Zhang (Current Microbiology, 2023)
The wild resources of Psammosilene tunicoides have decreased sharply because of the long-term mining and excavation, which has led to the increased demand for its artificial cultivation. However, root rot represents a significant obstacle leading to a poor quality and product of P. tunicoides . Previous reports have not focused on root rot in P. tunicoides. Therefore, this study explores the rhizospheric and root endophytic microbial community structure and composition of healthy and root rot P. tunicoides to understand the mechanism underlying root rot . The properties of the rhizosphere soil were assessed using physiochemical methods, and the bacterial and fungal populations were studied through amplicon sequencing of the 16S rRNA genes and ITS regions in the root and soil. Compared to healthy samples, the pH, hydrolysis N, available P, and available K were significantly decreased in the diseased samples while the organic matter and total organic carbon were significantly increased in the diseased samples. Redundancy analysis (RDA) showed that soil environmental factors are related to changes in the root and rhizosphere soil microbial community of P. tunicoides indicating that the physiochemical properties of soil affect plant health. Alpha diversity analysis showed that the microbial communities of healthy and diseased samples were similar. Some bacterial and fungal genera were significantly increased or decreased ( P < 0.05) in diseased P. tunicoides , and certain microbial factors that antagonized root rot were further explored. This study provides an abundant microbial resource for future studies and contributes to improving soil quality and P. tunicoides agricultural production.

Are males just passive? Coupling mechanism of the Brazilian cave insects with inverted genitalia - Zixin Cheng; Yoshitaka Kamimura; Rodrigo L. Ferreira; Charles Lienhard; Kazunori Yoshizawa (The Science of Nature, 2023)

Championing inclusive terminology in ecology and evolution - Susan J. Cheng; Kaitlyn M. Gaynor; Alex C. Moore; Kathy Darragh; Cesar O. Estien; J.W. Hammond; Christopher Lawrence; Kirby L. Mills; Marcella D. Baiz; Danielle Ignace; Lily Khadempour; Matthew A. McCary; et al. (Trends in Ecology & Evolution, 2023)

mTOR pathway candidate genes and obesity interaction on breast cancer risk in black women from the Women’s Circle of Health Study - Mmadili N. Ilozumba; Lusine Yaghjyan; Susmita Datta; Jinying Zhao; Chi-Chen Hong; Kathryn L. Lunetta; Gary Zirpoli; Elisa V. Bandera; Julie R. Palmer; Song Yao; Christine B. Ambrosone; Ting-Yuan David Cheng (Cancer Causes & Control, 2023)

Evaluating potential ecological risks of emerging toxic elements in lacustrine sediments: A case study in Lake Fuxian, China - Yixuan Han; Fan Xun; Cheng Zhao; Biao Li; Wenlei Luo; Muhua Feng; Di Xu; Peng Xing; Qinglong L. Wu (Environmental Pollution, 2023)

The Mechanism of the Anti-Cardiac Hypertrophy Effect of Glycyrrhizic Acid Is Related to Reducing STIM1-Dependent Store-Operated Calcium Entry - X. Cheng; L. Huang (Bulletin of Experimental Biology and Medicine, 2023)

The coincineration of sewage sludge and municipal solid waste in an industrial scale incineration power plant - S. He; K. Chen; Y. Zhang; Y. Cheng; S. Liu; B. Yu; L. Wang; X. Wang (International Journal of Environmental Science and Technology, 2023)

Experimental observation and geophysical modeling of the hydrological effects on Pleistocene glaciation deposits susceptible to landslide - L.-J. Su; F. Ullah; S. Ali; L. Cheng; M. Ur Rehman; M. Alam (International Journal of Environmental Science and Technology, 2023)

Endothelial cell expression of mutant Map2k1 causes vascular malformations in mice - Patrick J. Smits; Christopher L. Sudduth; Dennis J. Konczyk; Yu Sheng Cheng; Matthew P. Vivero; Harry P. W. Kozakewich; Matthew L. Warman; Arin K. Greene (Angiogenesis, 2023)

Linking human impacts to community processes in terrestrial and freshwater ecosystems - Ian R. McFadden; Agnieszka Sendek; Morgane Brosse; Peter M. Bach; Marco Baity‐Jesi; Janine Bolliger; Kurt Bollmann; Eckehard G. Brockerhoff; Giulia Donati; Friederike Gebert; Shyamolina Ghosh; Hsi‐Cheng Ho; et al. (Ecology Letters, 2023)
Human impacts such as habitat loss, climate change and biological invasions are radically altering biodiversity, with greater effects projected into the future. Evidence suggests human impacts may differ substantially between terrestrial and freshwater ecosystems, but the reasons for these differences are poorly understood. We propose an integrative approach to explain these differences by linking impacts to four fundamental processes that structure communities: dispersal, speciation, species‐level selection and ecological drift. Our goal is to provide process‐based insights into why human impacts, and responses to impacts, may differ across ecosystem types using a mechanistic, eco‐evolutionary comparative framework. To enable these insights, we review and synthesise (i) how the four processes influence diversity and dynamics in terrestrial versus freshwater communities, specifically whether the relative importance of each process differs among ecosystems, and (ii) the pathways by which human impacts can produce divergent responses across ecosystems, due to differences in the strength of processes among ecosystems we identify. Finally, we highlight research gaps and next steps, and discuss how this approach can provide new insights for conservation. By focusing on the processes that shape diversity in communities, we aim to mechanistically link human impacts to ongoing and future changes in ecosystems.

Meta‐analysis of ecosystem services associated with oyster restoration - Rachel S. Smith; Selina L. Cheng; Max C. N. Castorani (Conservation Biology, 2023)
Restoration of foundation species promises to reverse environmental degradation and return lost ecosystem services, but a lack of standardized evaluation across projects limits understanding of recovery, especially in marine systems. Oyster reefs are restored to reverse massive global declines and reclaim valuable ecosystem services, but the success of these projects has not been systematically and comprehensively quantified. We synthesized data on ecosystem services associated with oyster restoration from 245 pairs of restored and degraded reefs and 136 pairs of restored and reference reefs across 3500 km of U.S. Gulf of Mexico and Atlantic coastlines. On average, restoration was associated with a 21‐fold increase in oyster production (mean log response ratio = 3.08 [95% confidence interval: 2.58–3.58]), 34–97% enhancement of habitat provisioning (mean community abundance = 0.51 [0.41–0.61], mean richness = 0.29 [0.19–0.39], and mean biomass = 0.69 [0.39–0.99]), 54% more nitrogen removal (mean = 0.43 [0.13–0.73]), and 89–95% greater sediment nutrients (mean = 0.67 [0.27–1.07]) and organic matter (mean = 0.64 [0.44–0.84]) relative to degraded habitats. Moreover, restored reefs matched reference reefs for these ecosystem services. Our results support the continued and expanded use of oyster restoration to enhance ecosystem services of degraded coastal systems and match many functions provided by reference reefs.

A 10-miRNA risk score-based prediction model for pathological complete response to neoadjuvant chemotherapy in hormone receptor-positive breast cancer - Chang Gong; Ziliang Cheng; Yaping Yang; Jun Shen; Yingying Zhu; Li Ling; Wanyi Lin; Zhigang Yu; Zhihua Li; Weige Tan; Chushan Zheng; Wenbo Zheng; et al. (Science China Life Sciences, 2022)

Seals, whales and the Cenozoic decline of nautiloid cephalopods - Steffen Kiel; James L. Goedert; Cheng‐Hsiu Tsai (Journal of Biogeography, 2022)
Aim Nautilus and Allonautilus , last members of the once widespread nautiloid cephalopods, are today restricted to the deep central Indo‐West Pacific Ocean, for reasons that remain unclear. Cephalopod evolution is generally considered as being driven by vertebrate predation; therefore, we investigated the role of whales and seals in the decline of nautiloids through the Cenozoic. Location Global. Taxon Nautiloids, pinnipeds, cetaceans. Methods Distribution data for nautiloids, pinnipeds and cetaceans through the Cenozoic were compiled and plotted on a series of paleogeographic maps. Nautiloid shell sizes were compiled and plotted against the first appearance of pinnipeds and cetaceans in key regions. Results From the Oligocene onward, nautiloids became extinct in areas where pinnipeds appeared. The exception is the agile nautiloid Aturia , extinct globally at the end of the Miocene. A major role of odontocetes in the demise of nautiloids is not apparent, except for a few brevirostrine Oligocene taxa from the North American Atlantic and Pacific coasts, which appeared in these areas at the same time as nautilids disappeared. The Oligocene disappearance of nautiloids (except Aturia ) from the American Pacific coasts coincides with the development of oxygen minimum zones (OMZs) in this region. Main conclusions We hypothesize that the Cenozoic spread of pinnipeds drove nautiloids into their present‐day central Indo‐West Pacific refuge. Additional factors for the local extinction of nautiloids in the Oligocene include predation by short‐snouted whales and the development of OMZs, preventing nautiloids from retreating into deeper water.

Interactions between central nervous system and peripheral metabolic organs - Wenwen Zeng; Fan Yang; Wei L. Shen; Cheng Zhan; Peng Zheng; Ji Hu (Science China Life Sciences, 2022)

Decolorization characteristics and mechanism of methyl orange dye by using Stenotrophomonas acidaminiphila EFS1 - C Yang; H Luo; W Cheng; K Jiang; L Lu; L Ling (International Journal of Environmental Science and Technology, 2022)

Calcium amendments affect heavy metal bioavailability in acidic and calcareous soils - L. Li; K. Mao; J. A. Ippolito; W. Xing; X. Chen; W. Zhu; Y. Cheng (International Journal of Environmental Science and Technology, 2022)

A systematic review and meta-analysis of non-vitamin K antagonist oral anticoagulants vs vitamin K antagonists after transcatheter aortic valve replacement in patients with atrial fibrillation - Amanda Jia Qi Ooi; Chloe Wong; Timothy Wei Ern Tan; Trina Priscilla Ng; Yao Neng Teo; Yao Hao Teo; Nicholas L. Syn; Andie H. Djohan; Yinghao Lim; Leonard L. L. Yeo; Benjamin Y. Q. Tan; Mark Yan-Yee Chan; et al. (European Journal of Clinical Pharmacology, 2022)

Coastal Vegetation and Bathymetry Influence Blue Crab Abundance Across Spatial Scales - Selina L. Cheng; Kinsey N. Tedford; Rachel S. Smith; Sean Hardison; Michael R. Cornish; Max C. N. Castorani (Estuaries and Coasts, 2022)
Blue crabs ( Callinectes sapidus ) are highly mobile, ecologically-important mesopredators that support multimillion-dollar fisheries along the western Atlantic Ocean. Understanding how blue crabs respond to coastal landscape change is integral to conservation and management, but such insights have been limited to a narrow range of habitats and spatial scales. We examined how local-scale to landscape-scale habitat characteristics and bathymetric features (channels and oceanic inlets) affect the relative abundance (catch per unit effort, CPUE) of adult blue crabs across a > 33 km 2 seagrass landscape in coastal Virginia, USA. We found that crab CPUE was 1.7 × higher in sparse (versus dense) seagrass, 2.4 × higher at sites farther from (versus nearer to) salt marshes, and unaffected by proximity to oyster reefs. The probability that a trapped crab was female was 5.1 × higher in sparse seagrass and 8 × higher near deep channels. The probability of a female crab being gravid was 2.8 × higher near seagrass meadow edges and 3.3 × higher near deep channels. Moreover, the likelihood of a gravid female having mature eggs was 16 × greater in sparse seagrass and 32 × greater near oceanic inlets. Overall, we discovered that adult blue crab CPUE is influenced by seagrass, salt marsh, and bathymetric features on scales from meters to kilometers, and that habitat associations depend on sex and reproductive stage. Hence, accelerating changes to coastal geomorphology and vegetation will likely alter the abundance and distribution of adult blue crabs, challenging marine spatial planning and ecosystem-based fisheries management.

Complex impacts of hydraulic fracturing return fluids on soil microbial community respiration, structure and functional potentials - Cheng Zhong; Camilla L. Nesbø; Konstantin von Gunten; Yifeng Zhang; Xiaoqing Shao; Rong Jin; Kurt O. Konhauser; Greg G. Goss; Jonathan W. Martin; Yuhe He; Pei‐Yuan Qian; Brian D. Lanoil; et al. (Environmental Microbiology, 2022)
Summary The consequences of soils exposed to hydraulic fracturing (HF) return fluid, often collectively termed flowback and produced water (FPW), are poorly understood, even though soils are a common receptor of FPW spills. Here, we investigate the impacts on soil microbiota exposed to FPW collected from the Montney Formation of western Canada. We measured soil respiration, microbial community structure and functional potentials under FPW exposure across a range of concentrations, exposure time and soil types (luvisol and chernozem). We find that soil type governs microbial community response upon FPW exposure. Within each soil, FPW exposure led to reduced biotic soil respiration, and shifted microbial community structure and functional potentials. We detect substantially higher species richness and more unique functional genes in FPW‐exposed soils than in FPW‐unexposed soils, with metagenome‐assembled genomes (e.g. Marinobacter persicus ) from luvisol soil exposed to concentrated FPW being most similar to genomes from HF/FPW sites. Our data demonstrate the complex impacts of microbial communities following FPW exposure and highlight the site‐specific effects in evaluation of spills and agricultural reuse of FPW on the normal soil functions.

Striatal dopamine synthesis capacity and its association with negative symptoms upon resolution of positive symptoms in first-episode schizophrenia and delusional disorder - Stephanie M. Y. Wong; Y. N. Suen; Charlotte W. C. Wong; Sherry K. W. Chan; Christy L. M. Hui; W. C. Chang; Edwin H. M. Lee; Calvin P. W. Cheng; Garrett C. L. Ho; Gladys Goh Lo; Eric Y. L. Leung; Paul K. M. Au Yeung; et al. (Psychopharmacology, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

A targeted approach to investigating immune genes of an iconic Australian marsupial - Luke W. Silver; Yuanyuan Cheng; Bonnie L. Quigley; Amy Robbins; Peter Timms; Carolyn J. Hogg; Katherine Belov (Molecular Ecology, 2022)
Disease is a contributing factor to the decline of wildlife populations across the globe. Koalas, iconic yet declining Australian marsupials, are predominantly impacted by two pathogens, Chlamydia and koala retrovirus. Chlamydia is an obligate intracellular bacterium and one of the most widespread sexually transmitted infections in humans worldwide. In koalas, Chlamydia infections can present as asymptomatic or can cause a range of ocular and urogenital disease signs, such as conjunctivitis, cystitis and infertility. In this study, we looked at differences in response to Chlamydia in two northern populations of koalas using a targeted gene sequencing of 1209 immune genes in addition to genome‐wide reduced representation data. We identified two MHC Class I genes associated with Chlamydia disease progression as well as 25 single nucleotide polymorphisms across 17 genes that were associated with resolution of Chlamydia infection. These genes are involved in the innate immune response (TLR5) and defence (TLR5, IFNγ, SERPINE1, STAT2 and STX4). This study deepens our understanding of the role that genetics plays in disease progression in koalas and leads into future work that will use whole genome resequencing of a larger sample set to investigate in greater detail regions identified in this study. Elucidation of the role of host genetics in disease progression and resolution in koalas will directly contribute to better design of Chlamydia vaccines and management of koala populations which have recently been listed as “endangered.”

Quantifying cancer risk from exposures to medical imaging in the Risk of Pediatric and Adolescent Cancer Associated with Medical Imaging (RIC) Study: research methods and cohort profile - Marilyn L. Kwan; Diana L. Miglioretti; Erin J. A. Bowles; Sheila Weinmann; Robert T. Greenlee; Natasha K. Stout; Alanna Kulchak Rahm; Susan A. Alber; Priscila Pequeno; Lisa M. Moy; Carly Stewart; Cindy Fong; et al. (Cancer Causes & Control, 2022)

Safety and Pharmacokinetics of Intranasally Administered Heparin - Hannah M. Harris; Katherine L. Boyet; Hao Liu; Rohini Dwivedi; Nicole M. Ashpole; Ritesh Tandon; Gene L. Bidwell; Zhi Cheng; Lauren A. Fassero; Christian S. Yu; Vitor H. Pomin; Dipanwita Mitra; et al. (Pharmaceutical Research, 2022)

Transcriptomic and histological analysis of exposed facial skin areas wrinkled or not and unexposed skin - Renan Paulo Martin; Patricia Varela; Caio Peres Gomes; Maryana Mara Marins; Rafael Filippelli-Silva; Samira Yarak; Juliana L. M. Soares; Adriana Sanudo; Jolanta Idkowiak-Baldys; Siming Chen; Cheng Hwang; Yong Zhuang; et al. (Molecular Biology Reports, 2022)

Severe introduced predator impacts despite attempted functional eradication - Brian S. Cheng; Jeffrey Blumenthal; Andrew L. Chang; Jordanna Barley; Matthew C. Ferner; Karina J. Nielsen; Gregory M. Ruiz; Chela J. Zabin (Biological Invasions, 2022)

Not out of the woods yet: Signatures of the prolonged negative genetic consequences of a population bottleneck in a rapidly re‐expanding wader, the black‐faced spoonbill Platalea minor - Shou‐Hsien Li; Yang Liu; Chia‐Fen Yeh; Yuchen Fu; Carol K. L. Yeung; Chun‐Cheng Lee; Chi‐Cheng Chiu; Tung Hui Kuo; Fang‐Tse Chan; Yu‐Chia Chen; Wen‐Ya Ko; Cheng‐Te Yao (Molecular Ecology, 2022)
The long‐term persistence of a population which has suffered a bottleneck partly depends on how historical demographic dynamics impacted its genetic diversity and the accumulation of deleterious mutations. Here we provide genomic evidence for the genetic effect of a recent population bottleneck in the endangered black‐faced spoonbill ( Platalea minor ) after its rapid population recovery. Our data suggest that the bird's effective population size, N e , had been relatively stable (7500–9000) since 22,000 years ago; however, a recent brief yet severe bottleneck ( N e = 20) which we here estimated to occur around the 1940s wiped out >99% of its historical N e in roughly three generations. Despite a >15‐fold population recovery since 1988, we found that black‐faced spoonbill population has higher levels of inbreeding (7.4 times more runs of homozygosity) than its sister species, the royal spoonbill ( P. regia ), which is not thought to have undergone a marked population contraction. Although the two spoonbills have similar levels of genome‐wide genetic diversity, our results suggest that selection on more genes was relaxed in the black‐faced spoonbill; moreover individual black‐faced spoonbills carry more putatively deleterious mutations (Grantham's score > 50), and may therefore express more deleterious phenotypic effects than royal spoonbills. Here we demonstrate the value of using genomic indices to monitor levels of genetic erosion, inbreeding and mutation load in species with conservation concerns. To mitigate the prolonged negative genetic effect of a population bottleneck, we recommend that all possible measures should be employed to maintain population growth of a threatened species.

Miocene Nautilus (Mollusca, Cephalopoda) from Taiwan, and a review of the Indo‐Pacific fossil record of Nautilus - James L. Goedert; Steffen Kiel; Cheng‐Hsiu Tsai (Island Arc, 2022)
The fossil record of the cephalopod genus Nautilus has been obscured because a few influential taxonomists during the 20th Century decided that fossils similar to Nautilus were instead other genera. We now recognize fossils once classified as species of other genera as species of Nautilus . This includes fossils from Miocene rocks of Taiwan that were previously described as Kummelonautilus taiwanum but herein recognized instead as being the northernmost Neogene record of Nautilus in the Indo‐Pacific region. The name is corrected to Nautilus taiwanus , and now known to occur in two formations in central Taiwan, the early Miocene Shihmentsun and early to middle Miocene Houdongkeng formations. Miocene fossils from Indonesia that were placed in other genera are now considered to represent Nautilus as they were originally assigned, in addition to several Miocene species from Australia, which provide the southernmost Neogene fossil record for the genus. Some of these Indo‐Pacific fossils may represent the same species, but more specimens are needed to determine the amount of variability within these Neogene taxa.

Increasing the spatial and temporal impact of ecological research: A roadmap for integrating a novel terrestrial process into an Earth system model - Emily Kyker‐Snowman; Danica L. Lombardozzi; Gordon B. Bonan; Susan J. Cheng; Jeffrey S. Dukes; Serita D. Frey; Elin M. Jacobs; Risa McNellis; Joshua M. Rady; Nicholas G. Smith; R. Quinn Thomas; William R. Wieder; et al. (Global Change Biology, 2022)
Terrestrial ecosystems regulate Earth's climate through water, energy, and biogeochemical transformations. Despite a key role in regulating the Earth system, terrestrial ecology has historically been underrepresented in the Earth system models (ESMs) that are used to understand and project global environmental change. Ecology and Earth system modeling must be integrated for scientists to fully comprehend the role of ecological systems in driving and responding to global change. Ecological insights can improve ESM realism and reduce process uncertainty, while ESMs offer ecologists an opportunity to broadly test ecological theory and increase the impact of their work by scaling concepts through time and space. Despite this mutualism, meaningfully integrating the two remains a persistent challenge, in part because of logistical obstacles in translating processes into mathematical formulas and identifying ways to integrate new theories and code into large, complex model structures. To help overcome this interdisciplinary challenge, we present a framework consisting of a series of interconnected stages for integrating a new ecological process or insight into an ESM. First, we highlight the multiple ways that ecological observations and modeling iteratively strengthen one another, dispelling the illusion that the ecologist's role ends with initial provision of data. Second, we show that many valuable insights, products, and theoretical developments are produced through sustained interdisciplinary collaborations between empiricists and modelers, regardless of eventual inclusion of a process in an ESM. Finally, we provide concrete actions and resources to facilitate learning and collaboration at every stage of data‐model integration. This framework will create synergies that will transform our understanding of ecology within the Earth system, ultimately improving our understanding of global environmental change, and broadening the impact of ecological research.

Cytotoxic activity of phytochemicals from Garcinia mangostana L. and G. benthamiana (Planch. & Triana) Pipoly against breast cancer cells - Irene See; Gwendoline Cheng Lian Ee; Vivien Yi Mian Jong; Soek Sin Teh; Carlos L. Céspedes Acuña; Siau Hui Mah (Natural Product Research, 2021)

Biological control of Qinghai plateau terrestrial weeds with the A. alternata HL-1 - L. Cheng; H. X. Zhu; Y. H. Wei; L. Z. Guo; H. Weng; Q. Y. Guo (Journal of Plant Diseases and Protection, 2021)

Interactive effects of aging and aerobic capacity on energy metabolism–related metabolites of serum, skeletal muscle, and white adipose tissue - Haihui Zhuang; Sira Karvinen; Timo Törmäkangas; Xiaobo Zhang; Xiaowei Ojanen; Vidya Velagapudi; Markku Alen; Steven L. Britton; Lauren G. Koch; Heikki Kainulainen; Sulin Cheng; Petri Wiklund (GeroScience, 2021)
Aerobic capacity is a strong predictor of longevity. With aging, aerobic capacity decreases concomitantly with changes in whole body metabolism leading to increased disease risk. To address the role of aerobic capacity, aging, and their interaction on metabolism, we utilized rat models selectively bred for low and high intrinsic aerobic capacity (LCRs/HCRs) and compared the metabolomics of serum, muscle, and white adipose tissue (WAT) at two time points: Young rats were sacrificed at 9 months of age, and old rats were sacrificed at 21 months of age. Targeted and semi-quantitative metabolomics analysis was performed on the ultra-pressure liquid chromatography tandem mass spectrometry (UPLC-MS) platform. The effects of aerobic capacity, aging, and their interaction were studied via regression analysis. Our results showed that high aerobic capacity is associated with an accumulation of isovalerylcarnitine in muscle and serum at rest, which is likely due to more efficient leucine catabolism in muscle. With aging, several amino acids were downregulated in muscle, indicating more efficient amino acid metabolism, whereas in WAT less efficient amino acid metabolism and decreased mitochondrial β-oxidation were observed. Our results further revealed that high aerobic capacity and aging interactively affect lipid metabolism in muscle and WAT, possibly combating unfavorable aging-related changes in whole body metabolism. Our results highlight the significant role of WAT metabolism for healthy aging.

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Keep your friends close: Host compartmentalisation of microbial communities facilitates decoupling from effects of habitat fragmentation - Claire E. Willing; Grady Pierroz; Aidee Guzman; Leander D. L. Anderegg; Cheng Gao; Devin Coleman‐Derr; John W. Taylor; Tom D. Bruns; Todd E. Dawson (Ecology Letters, 2021)
Root‐associated fungal communities modify the climatic niches and even the competitive ability of their hosts, yet how the different components of the root microbiome are modified by habitat loss remains a key knowledge gap. Using principles of landscape ecology, we tested how free‐living versus host‐associated microbes differ in their response to landscape heterogeneity. Further, we explore how compartmentalisation of microbes into specialised root structures filters for key fungal symbionts. Our study demonstrates that free‐living fungal community structure correlates with landscape heterogeneity, but that host‐associated fungal communities depart from these patterns. Specifically, biotic filtering in roots, especially via compartmentalisation within specialised root structures, decouples the biogeographic patterns of host‐associated fungal communities from the soil community. In this way, even as habitat loss and fragmentation threaten fungal diversity in the soils, plant hosts exert biotic controls to ensure associations with critical mutualists, helping to preserve the root mycobiome.

Comparing the clinical outcomes across different sodium/glucose cotransporter 2 (SGLT2) inhibitors in heart failure patients: a systematic review and network meta-analysis of randomized controlled trials - Yao Hao Teo; Celine Shuen Yin Yoong; Nicholas L. Syn; Yao Neng Teo; Jia Yang Alex Cheong; Yoke-Ching Lim; Chi-Hang Lee; Tiong-Cheng Yeo; Ping Chai; Raymond C. C. Wong; Weiqin Lin; Ching-Hui Sia (European Journal of Clinical Pharmacology, 2021)

The scope and severity of white‐nose syndrome on hibernating bats in North America - Tina L. Cheng; Jonathan D. Reichard; Jeremy T. H. Coleman; Theodore J. Weller; Wayne E. Thogmartin; Brian E. Reichert; Alyssa B. Bennett; Hugh G. Broders; Joshua Campbell; Katherine Etchison; Daniel J. Feller; Richard Geboy; et al. (Conservation Biology, 2021)
Assessing the scope and severity of threats is necessary for evaluating impacts on populations to inform conservation planning. Quantitative threat assessment often requires monitoring programs that provide reliable data over relevant spatial and temporal scales, yet such programs can be difficult to justify until there is an apparent stressor. Leveraging efforts of wildlife management agencies to record winter counts of hibernating bats, we collated data for 5 species from over 200 sites across 27 U.S. states and 2 Canadian provinces from 1995 to 2018 to determine the impact of white‐nose syndrome (WNS), a deadly disease of hibernating bats. We estimated declines of winter counts of bat colonies at sites where the invasive fungus that causes WNS ( Pseudogymnoascus destructans ) had been detected to assess the threat impact of WNS. Three species undergoing species status assessment by the U.S. Fish and Wildlife Service ( Myotis septentrionalis , Myotis lucifugus , and Perimyotis subflavus ) declined by more than 90%, which warrants classifying the severity of the WNS threat as extreme based on criteria used by NatureServe. The scope of the WNS threat as defined by NatureServe criteria was large (36% of Myotis lucifugus range) to pervasive (79% of Myotis septentrionalis range) for these species. Declines for 2 other species ( Myotis sodalis and Eptesicus fuscus ) were less severe but still qualified as moderate to serious based on NatureServe criteria. Data‐sharing across jurisdictions provided a comprehensive evaluation of scope and severity of the threat of WNS and indicated regional differences that can inform response efforts at international, national, and state or provincial jurisdictions. We assessed the threat impact of an emerging infectious disease by uniting monitoring efforts across jurisdictional boundaries and demonstrated the importance of coordinated monitoring programs, such as the North American Bat Monitoring Program (NABat), for data‐driven conservation assessments and planning.

Limited Progress in Improving Gender and Geographic Representation in Coral Reef Science - Gabby N. Ahmadia; Samantha H. Cheng; Dominic A. Andradi-Brown; Stacy K. Baez; Megan D. Barnes; Nathan J. Bennett; Stuart J. Campbell; Emily S. Darling; Estradivari; David Gill; Erika Gress; Georgina G. Gurney; et al. (Frontiers in Marine Science, 2021)
Despite increasing recognition of the need for more diverse and equitable representation in the sciences, it is unclear whether measurable progress has been made. Here, we examine trends in authorship in coral reef science from 1,677 articles published over the past 16 years (2003–2018) and find that while representation of authors that are women (from 18 to 33%) and from non-OECD nations (from 4 to 13%) have increased over time, progress is slow in achieving more equitable representation. For example, at the current rate, it would take over two decades for female representation to reach 50%. Given that there are more coral reef non-OECD countries, at the current rate, truly equitable representation of non-OECD countries would take even longer. OECD nations also continue to dominate authorship contributions in coral reef science (89%), in research conducted in both OECD (63%) and non-OECD nations (68%). We identify systemic issues that remain prevalent in coral reef science (i.e., parachute science, gender bias) that likely contribute to observed trends. We provide recommendations to address systemic biases in research to foster a more inclusive global science community. Adoption of these recommendations will lead to more creative, innovative, and impactful scientific approaches urgently needed for coral reefs and contribute to environmental justice efforts.

Genetic analyses of gynecological disease identify genetic relationships between uterine fibroids and endometrial cancer, and a novel endometrial cancer genetic risk region at the WNT4 1p36.12 locus - Pik Fang Kho; Sally Mortlock; Frederic Amant; Daniela Annibali; Katie Ashton; John Attia; Paul L. Auer; Matthias W. Beckmann; Amanda Black; Louise Brinton; Daniel D. Buchanan; Stephen J. Chanock; et al. (Human Genetics, 2021)

Evaluation of arsenic sorption performance using dendritic anatase and polycrystalline rutile nano-TiO2 for environmental applications - S. Yin; C.-L. Cheng; J. Parsons; Y. Mao; J. J. Kang; J. Kim (International Journal of Environmental Science and Technology, 2021)

Microbially mediated kinetic sulfur isotope fractionation: reactive transport modeling benchmark - Yiwei Cheng; Bhavna Arora; S. Sevinç Şengör; Jennifer L. Druhan; Christoph Wanner; Boris M. van Breukelen; Carl I. Steefel (Computational Geosciences, 2021)

Synthesis, structure-activity relationship studies and evaluation of a TLR 3/8/9 agonist and its analogues - Anindya Sarkar; Anushka C. Galasiti Kankanamalage; Qian Zhang; Heng Cheng; Prasanna Sivaprakasam; Joseph Naglich; Chunshan Xie; Sanjeev Gangwar; Dale L. Boger (Medicinal Chemistry Research, 2021)

Novel disease resistance gene paralogs created by CRISPR/Cas9 in soy - Ervin D. Nagy; Julia L. Stevens; Neil Yu; Chris S. Hubmeier; Nona LaFaver; Megan Gillespie; Brian Gardunia; Qianshun Cheng; Steven Johnson; Audrey L. Vaughn; Miguel E. Vega-Sanchez; Mingqui Deng; et al. (Plant Cell Reports, 2021)
Key message Novel disease resistance gene paralogues are generated by targeted chromosome cleavage of tandem duplicated NBS-LRR gene complexes and subsequent DNA repair in soybean. This study demonstrates accelerated diversification of innate immunity of plants using CRISPR. Abstract Nucleotide-binding-site-leucine-rich-repeat (NBS-LRR) gene families are key components of effector-triggered immunity. They are often arranged in tandem duplicated arrays in the genome, a configuration that is conducive to recombinations that will lead to new, chimeric genes. These rearrangements have been recognized as major sources of novel disease resistance phenotypes. Targeted chromosome cleavage by CRISPR/Cas9 can conceivably induce rearrangements and thus emergence of new resistance gene paralogues. Two NBS-LRR families of soy have been selected to demonstrate this concept: a four-copy family in the Rpp1 region (Rpp1L) and a large, complex locus, Rps1 with 22 copies. Copy-number variations suggesting large-scale, CRISPR/Cas9-mediated chromosome rearrangements in the Rpp1L and Rps1 complexes were detected in up to 58.8% of progenies of primary transformants using droplet-digital PCR. Sequencing confirmed development of novel, chimeric paralogs with intact open reading frames. These novel paralogs may confer new disease resistance specificities. This method to diversify innate immunity of plants by genome editing is readily applicable to other disease resistance genes or other repetitive loci.

Brain activation and connectivity in anorexia nervosa and body dysmorphic disorder when viewing bodies: relationships to clinical symptoms and perception of appearance - Teena D. Moody; Francesca Morfini; Gigi Cheng; Courtney L. Sheen; Wesley T Kerr; Michael Strober; Jamie D. Feusner (Brain Imaging and Behavior, 2021)

NABat: A top-down, bottom-up solution to collaborative continental-scale monitoring - Brian E. Reichert; Mylea Bayless; Tina L. Cheng; Jeremy T. H. Coleman; Charles M. Francis; Winifred F. Frick; Benjamin S. Gotthold; Kathryn M. Irvine; Cori Lausen; Han Li; Susan C. Loeb; Jonathan D. Reichard; et al. (Ambio, 2021)
Collaborative monitoring over broad scales and levels of ecological organization can inform conservation efforts necessary to address the contemporary biodiversity crisis. An important challenge to collaborative monitoring is motivating local engagement with enough buy-in from stakeholders while providing adequate top-down direction for scientific rigor, quality control, and coordination. Collaborative monitoring must reconcile this inherent tension between top-down control and bottom-up engagement. Highly mobile and cryptic taxa, such as bats, present a particularly acute challenge. Given their scale of movement, complex life histories, and rapidly expanding threats, understanding population trends of bats requires coordinated broad-scale collaborative monitoring. The North American Bat Monitoring Program (NABat) reconciles top-down, bottom-up tension with a hierarchical master sample survey design, integrated data analysis, dynamic data curation, regional monitoring hubs, and knowledge delivery through web-based infrastructure. NABat supports collaborative monitoring across spatial and organizational scales and the full annual lifecycle of bats.

The influence of vector‐borne disease on human history: socio‐ecological mechanisms - Tejas S. Athni; Marta S. Shocket; Lisa I. Couper; Nicole Nova; Iain R. Caldwell; Jamie M. Caldwell; Jasmine N. Childress; Marissa L. Childs; Giulio A. De Leo; Devin G. Kirk; Andrew J. MacDonald; Kathryn Olivarius; et al. (Ecology Letters, 2021)
Vector‐borne diseases (VBDs) are embedded within complex socio‐ecological systems. While research has traditionally focused on the direct effects of VBDs on human morbidity and mortality, it is increasingly clear that their impacts are much more pervasive. VBDs are dynamically linked to feedbacks between environmental conditions, vector ecology, disease burden, and societal responses that drive transmission. As a result, VBDs have had profound influence on human history. Mechanisms include: (1) killing or debilitating large numbers of people, with demographic and population‐level impacts; (2) differentially affecting populations based on prior history of disease exposure, immunity, and resistance; (3) being weaponised to promote or justify hierarchies of power, colonialism, racism, classism and sexism; (4) catalysing changes in ideas, institutions, infrastructure, technologies and social practices in efforts to control disease outbreaks; and (5) changing human relationships with the land and environment. We use historical and archaeological evidence interpreted through an ecological lens to illustrate how VBDs have shaped society and culture, focusing on case studies from four pertinent VBDs: plague, malaria, yellow fever and trypanosomiasis. By comparing across diseases, time periods and geographies, we highlight the enormous scope and variety of mechanisms by which VBDs have influenced human history.

Response of plantain (Plantago lanceolata L.) supplementation on nutritional, endo-parasitic, and endocrine status in lambs - M. M. Reza; M. R. A. Redoy; M. A. Rahman; S. Ety; M. A. Alim; L. Cheng; M. Al-Mamun (Tropical Animal Health and Production, 2021)

Identification of reproduction-related genes and pathways in the Culter alburnus H-P-G axis and characterization of their expression differences in malformed and normal gynogenetic ovaries - Yong Y. Jia; Mei L. Chi; Wen P. Jiang; Shi L. Liu; Shun Cheng; Jian B. Zheng; Zhi M. Gu (Fish Physiology and Biochemistry, 2021)

Dissecting the phenotypic response of maize to low phosphorus soils by field screening of a large diversity panel - Dongdong Li; Zhe Chen; Meng Wang; Willmar L. Leiser; Thea Mi Weiß; Zheng Zhao; Song Cheng; Shaojiang Chen; Fanjun Chen; Lixing Yuan; Tobias Würschum; Wenxin Liu (Euphytica, 2021)

Effects of some parameters on the removal of Cd(II) ions from aqueous solutions by polyethyleneimine–sodium xanthogenate - G. Wang; X. L. Cheng; Y. C. Zeng; Y. F. Jiang (International Journal of Environmental Science and Technology, 2020)

An integrated biophysical approach to discovering mechanisms of NDM-1 inhibition for several thiol-containing drugs - Sarah Fullington; Zishuo Cheng; Caitlyn Thomas; Callie Miller; Kundi Yang; Lin-Cheng Ju; Alexander Bergstrom; Ben A. Shurina; Stacey Lowery Bretz; Richard C. Page; David L. Tierney; Michael W. Crowder (JBIC Journal of Biological Inorganic Chemistry, 2020)

Mechanical injury and IL-1β regulated LOXs and MMP-1, 2, 3 expression in ACL fibroblasts co-cultured with synoviocytes - Chunli Wang; Qingjia Chi; Yongqiang Sha; Kang Xu; Chunming Xu; Cheng Chen; Wei Huang; Peixing Chen; Peter Chen; Li Yang; K. L. Paul Sung (Biotechnology Letters, 2020)

Toxicity assessment of electrochemical advanced oxidation process-treated groundwater from a gas station with petrochemical contamination - How-Ran Chao; Danielle E. Que; Alisha C. Aquino; Yan-You Gou; Lemmuel L. Tayo; Yi-Hsien Lin; Ming-Hsien Tsai; Fu-Lin Hsu; I-Cheng Lu; Sheng-Lun Lin; Natwat Srikhao; Cherng-Gueih Shy; et al. (Environmental Monitoring and Assessment, 2020)

Great journey of Great Tits (Parus major group): Origin, diversification and historical demographics of a broadly distributed bird lineage - Gang Song; Ruiying Zhang; Fernando Machado‐Stredel; Per Alström; Ulf S. Johansson; Martin Irestedt; Herman L. Mays; Bailey D. McKay; Isao Nishiumi; Yalin Cheng; Yanhua Qu; Per G. P. Ericson; et al. (Journal of Biogeography, 2020)
Aim The Pleistocene glacial cycles play a prominent role in shaping phylogeographical patterns of organisms, while few studies have focused on the regional difference of glacial effects. By acquiring comprehensive knowledge of the origin, diversification and historical demography of an intensively studied passerine species complex, Great Tit, we aim to test the regional variation of the Late Pleistocene glaciation impacts on this widely distributed bird lineage. Location Eurasia and associated peninsulas and archipelagos. Taxa Parus major species complex. Methods Phylogeny, divergence times and demographic dynamics were estimated with Bayesian methods. Population structure, genetic diversity and correlation between genetic and physical distances were estimated based on mtDNA variation. Glacial‐to‐present distributional changes were assessed via ecological niche modelling (ENM). Results Five major clades (Central Asia, Eastern Asia, Eastern Himalaya, Northern and Western Eurasia and Southern Asia) were detected, with divergence times ranging 1.57–0.50 million years ago. Genetic diversity values and Bayesian skyline plots suggest that the three eastern clades had a deeper population history. A more complex geographic structure was observed in East Asia. Demographic expansion during the last glacial cycle was indicated for all five clades. ENM results showed broad conservatism of traits related to climate tolerances, and generally broader and more continuous distributional patterns under glacial conditions. Main Conclusions The Great Tit complex probably originated in Southeast Asia. Geographic barriers, such as the deserts of Central Asia and the Qinghai–Tibet Plateau appear to be related to the lineage divergence. Late Pleistocene climate cycles influenced both demographic dynamics and divergence, especially in terms of east–west differences in relation to geographic complexity.

7700-year persistence of an isolated, free-living coral assemblage in the Galápagos Islands: a model for coral refugia? - J. S. Feingold; B. Riegl; K. Hendrickson; L. T. Toth; H. Cheng; R. L. Edwards; R. B. Aronson (Coral Reefs, 2020)

Skeletal impact of 17β-estradiol in T cell-deficient mice: age-dependent bone effects and osteosarcoma formation - Julia N. Cheng; Jennifer B. Frye; Susan A. Whitman; Janet L. Funk (Clinical & Experimental Metastasis, 2020)

Ensemble Projections of Future Climate Change Impacts on the Eastern Bering Sea Food Web Using a Multispecies Size Spectrum Model - Jonathan C. P. Reum; Julia L. Blanchard; Kirstin K. Holsman; Kerim Aydin; Anne B. Hollowed; Albert J. Hermann; Wei Cheng; Amanda Faig; Alan C. Haynie; André E. Punt (Frontiers in Marine Science, 2020)

The diversity of powdery mildew resistance gene loci among wheat germplasm in Southwest China - B. Cheng; Y. Q. Ding; X. Gao; N. Cao; Z. H. Xin; L. Y. Zhang (Cereal Research Communications, 2020)
Knowledge of genetic diversity and genes conferring disease resistance is essential for the effective use of wheat germplasm resistant to powdery mildew in breeding programs in southwest China. In this study, a collection of 140 common wheat varieties was evaluated for their resistance to powdery mildew in four different environments. Thirty-six varieties (25.71%) showed resistance in all four environments, and most of these varieties originated from the Guizhou Province. This collection was also scanned for molecular markers closely linked to the powdery mildew resistance genes. Most of the wheat varieties (79.86%) carried the resistance Pm30 gene locus. Genotyping by sequencing (GBS) was used to screen our collection against the whole genome. Finally, 6864 informative SNP markers were used to construct a consensus tree with 1000 bootstraps, which showed two groups based on their origins and the presence of the Pm21 gene locus. Our results provide useful information for breeding wheat resistant to powdery mildew in China, and they will likely contribute to the identification of new resistance genes in the future.

Differential Gamma-Synuclein Expression in Acute and Chronic Retinal Ganglion Cell Death in the Retina and Optic Nerve - Yuan Liu; Mary L. Tapia; Justin Yeh; Rossana Cheng He; Dustin Pomerleu; Richard K. Lee (Molecular Neurobiology, 2020)

Speciation and sorption structure of diphenylarsinic acid in soil clay mineral fractions using sequential extraction and EXAFS spectroscopy - Meng Zhu; Xuefeng Hu; Chen Tu; Yongming Luo; Ruyi Yang; Shoubiao Zhou; Nannan Cheng; Elizabeth L. Rylott (Journal of Soils and Sediments, 2020)

Accuracy assessment and waveform analysis of CryoSat-2 SARIn mode data over Antarctica - Fang Wang; Jonathan L. Bamber; Shuangbao Yang; Xiao Cheng; Shubin Liu; Youzhi Zhang; Yunping Chi (International Journal of Remote Sensing, 2019)

Seismic landslides hazard zoning based on the modified Newmark model: a case study from the Lushan earthquake, China - K. P. Jin; L. K. Yao; Q. G. Cheng; A. G. Xing (Natural Hazards, 2019)

Lead removal from aqueous solutions using biochars derived from corn stover, orange peel, and pistachio shell - S. Mireles; J. Parsons; T. Trad; C.-L. Cheng; J. Kang (International Journal of Environmental Science and Technology, 2019)

LpxD gene knockout elicits protection to Litopenaeus vannamei, white shrimp, against Vibrio parahaemolyticus infection - Ching-Yi Tsai; Harvey M. Santos; Shao-Yang Hu; Cheng Yu Sang; Ciara Alyssa S. Yanuaria; Ernest Nicolo G. Lola; Lemmuel L. Tayo; Karmella Marie A. Nitura; Chun Hung Liu; Kuo Pin Chuang (Aquaculture International, 2019)

Measuring Global Ocean Heat Content to Estimate the Earth Energy Imbalance - Benoit Meyssignac; Tim Boyer; Zhongxiang Zhao; Maria Z. Hakuba; Felix W. Landerer; Detlef Stammer; Armin Köhl; Seiji Kato; Tristan L’Ecuyer; Michael Ablain; John Patrick Abraham; Alejandro Blazquez; et al. (Frontiers in Marine Science, 2019)

U–Pb detrital zircon geochronology and Hf isotopic composition of Permian clastic rocks, Zhen’an basin, South Qinling belt: implications for the Paleozoic tectonic evolution of the Qinling orogenic belt - Cheng Cheng; Shuangying Li; Xiangyang Xie; Walter L. Manger; Arthur B. Busbey (International Geology Review, 2019)

POD characterisation of extreme wake patterns of turbulent wind fields past rectangular buildings - F. Wang; L. Cheng; K. M. Lam (Environmental Fluid Mechanics, 2019)

An End-to-end System for Automatic Characterization of Iba1 Immunopositive Microglia in Whole Slide Imaging - Alexander D. Kyriazis; Shahriar Noroozizadeh; Amir Refaee; Woongcheol Choi; Lap-Tak Chu; Asma Bashir; Wai Hang Cheng; Rachel Zhao; Dhananjay R. Namjoshi; Septimiu E. Salcudean; Cheryl L. Wellington; Guy Nir (Neuroinformatics, 2019)

Integration of Food Animal Residue Avoidance Databank (FARAD) empirical methods for drug withdrawal interval determination with a mechanistic population-based interactive physiologically based pharmacokinetic (iPBPK) modeling platform: example for flunixin meglumine administration - Miao Li; Yi-Hsien Cheng; Jason T. Chittenden; Ronald E. Baynes; Lisa A. Tell; Jennifer L. Davis; Thomas W. Vickroy; Jim E. Riviere; Zhoumeng Lin (Archives of Toxicology, 2019)

Transcriptomic Response to Feeding and Starvation in a Herbivorous Dinoflagellate - Ewelina T. Rubin; Shu Cheng; Amanda L. Montalbano; Susanne Menden-Deuer; Tatiana A. Rynearson (Frontiers in Marine Science, 2019)

A modified Sarma method for stability analysis of layered slopes - X. P. Zhou; X. D. Zhao; L. N. Y. Wong; H. Cheng (Bulletin of Engineering Geology and the Environment, 2019)

Thioredoxin overexpression in both the cytosol and mitochondria accelerates age-related disease and shortens lifespan in male C57BL/6 mice - Geneva M. Cunningham; Lisa C. Flores; Madeline G. Roman; Christie Cheng; Sara Dube; Colton Allen; Joseph M. Valentine; Gene B. Hubbard; Yidong Bai; Thomas L. Saunders; Yuji Ikeno (GeroScience, 2018)

Impact of individual and neighborhood factors on socioeconomic disparities in localized and advanced prostate cancer risk - Mindy C. DeRouen; Clayton W. Schupp; Juan Yang; Jocelyn Koo; Andrew Hertz; Salma Shariff-Marco; Myles Cockburn; David O. Nelson; Sue A. Ingles; Iona Cheng; Esther M. John; Scarlett L. Gomez (Cancer Causes & Control, 2018)

A New Venous Entry Detection Method Based on Electrical Bio-impedance Sensing - Zhuoqi Cheng; Brian L. Davies; Darwin G. Caldwell; Leonardo S. Mattos (Annals of Biomedical Engineering, 2018)

High‐resolution reconstruction of 8.2‐ka BP event documented in Père Noël cave, southern Belgium - M. Allan; N. Fagel; H. J. L. van der Lubbe; H. B. Vonhof; H. Cheng; R. Lawrence Edwards; S. Verheyden (Journal of Quaternary Science, 2018)
A distinct shift in δ 18 O, δ 13 C and trace element contents of the Père Noël (PN) stalagmite from southern Belgium revealed an abrupt climatic anomaly at 8.13 ± 0.03 ka BP (before present = before 1950 AD). This anomaly is characterized by a maximum drop in the δ 18 O (−1.4‰ compared the mean) between 8.13 and 8.10 ka BP (±0.03). This drop of δ 18 O coincides with a decrease in δ 13 C and trace element (Sr, Ba and Mg) concentrations suggesting drier conditions. Our precise chronology provides the timing of the outburst of proglacial lakes Agassiz and Ojibway that caused the δ 18 O, δ 13 C and trace elemental anomalies at 8.13–8.10 ± 0.03 ka BP, which corresponds to the 8.2‐ka BP event. The PN stalagmite bears δ 18 O values in fluid inclusions that covary with the δ 18 O values in calcite, suggesting that the speleothem calcite δ 18 O primarily reflects variations in the rainfall δ 18 O. Comparison of the PN record with different marine and terrestrial archives during the 8.2‐ka BP event shows a good agreement in timing and duration, suggesting that the PN speleothem can be regarded as a valuable proxy to better understand the 8.2‐ka BP event.

Comparing the spatial patterns of earthquake disaster probability and individual risk perception: a case study of Yongkang Township in Tainan, Taiwan - H. S. Chang; T. L. Chen; H. T. Cheng (Natural Hazards, 2018)

Phylogeny and species delimitation of Flammulina: taxonomic status of winter mushroom in East Asia and a new European species identified using an integrated approach - Pan Meng Wang; Xiao Bin Liu; Yu Cheng Dai; Egon Horak; Kari Steffen; Zhu L. Yang (Mycological Progress, 2018)

Bacteria and viruses in the nasopharynx immediately prior to onset of acute lower respiratory infections in Indigenous Australian children - Heidi C. Smith-Vaughan; Michael J. Binks; Jemima Beissbarth; Anne B. Chang; Gabrielle B. McCallum; Ian M. Mackay; Peter S. Morris; Robyn L. Marsh; Paul J. Torzillo; Danielle F. Wurzel; Keith Grimwood; Elizabeth Nosworthy; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

Roles of seed components in the growth of barley seedlings under salt stress - W. Xue; A. Gianinetti; Y. Jiang; Z. Zhan; L. Kuang; G. Zhao; J. Yan; J. Cheng (Cereal Research Communications, 2018)

Material Processing and Design of Biodegradable Metal Matrix Composites for Biomedical Applications - Jingxin Yang; Jason L. Guo; Antonios G. Mikos; Chunyan He; Guang Cheng (Annals of Biomedical Engineering, 2018)

Statistical prediction of non‐Gaussian climate extremes in urban areas based on the first‐order difference method - Cheng Qian; Wen Zhou; Xiu‐Qun Yang; Johnny C. L. Chan (International Journal of Climatology, 2018)
Prediction of climate extremes is challenging, especially for non‐Gaussian extremes in urban areas where the majority of people live, since the Gaussian assumption used in linear regression is violated and the urbanization effect needs to be considered. In this study, the first‐order difference method is introduced to take these difficulties into account. Statistical prediction of the non‐Gaussian annual occurrence of hot days in downtown Hong Kong, which is highly urbanized, is used to illustrate this method. With the help of the first‐order difference of the annual occurrences, which follows a Gaussian distribution, the difference series is used as the predictant to find predictors and to construct a prediction model by using traditional linear regression. The difference is first predicted and is then added to the observed value at the preceding time to obtain the predicted annual occurrence. The historical urbanization effect is thus obtained directly from the observations at the preceding time. The prediction results are found desirable. The broad application potential and conditions in which this method should be used are also discussed.

Noninvasive induction of angiogenesis in tissues by external suction: sequential optimization for use in reconstructive surgery - G. Giatsidis; L. Cheng; Anthony Haddad; K. Ji; J. Succar; L. Lancerotto; J. Lujan-Hernandez; P. Fiorina; H. Matsumine; D. P. Orgill (Angiogenesis, 2018)

Integrating Bayesian genomic cline analyses and association mapping of morphological and ecological traits to dissect reproductive isolation and introgression in a Louisiana Iris hybrid zone - Cheng‐Jung Sung; Katherine L. Bell; Chris C. Nice; Noland H. Martin (Molecular Ecology, 2018)
Hybrid zones provide unique opportunities to examine reproductive isolation and introgression in nature. We utilized 45,384 single nucleotide polymorphism ( SNP ) loci to perform association mapping of 14 floral, vegetative and ecological traits that differ between Iris hexagona and Iris fulva, and to investigate, using a Bayesian genomic cline ( BGC ) framework, patterns of genomic introgression in a large and phenotypically diverse hybrid zone in southern Louisiana. Many loci of small effect size were consistently found to be associated with phenotypic variation across all traits, and several individual loci were revealed to influence phenotypic variation across multiple traits. Patterns of genomic introgression were quite heterogeneous throughout the Louisiana Iris genome, with I. hexagona alleles tending to be favoured over those of I. fulva . Loci that were found to have exceptional patterns of introgression were also found to be significantly associated with phenotypic variation in a small number of morphological traits. However, this was the exception rather than the rule, as most loci that were associated with morphological trait variation were not significantly associated with excess ancestry. These findings provide insights into the complexity of the genomic architecture of phenotypic differences and are a first step towards identifying loci that are associated with both trait variation and reproductive isolation in nature.

Erratum to: Degradation of βII-Spectrin Protein by Calpain-2 and Caspase-3 Under Neurotoxic and Traumatic Brain Injury Conditions - Firas H. Kobeissy; Ming Cheng Liu; Zhihui Yang; Zhiqun Zhang; Wenrong Zheng; Olena Glushakova; Stefania Mondello; John Anagli; Ronald L. Hayes; Kevin K. W. Wang (Molecular Neurobiology, 2018)

Characterizing the neighborhood obesogenic environment in the Multiethnic Cohort: a multi-level infrastructure for cancer health disparities research - Shannon M. Conroy; Salma Shariff-Marco; Juan Yang; Andrew Hertz; Myles Cockburn; Yurii B. Shvetsov; Christina A. Clarke; Cheryl L. Abright; Christopher A. Haiman; Loïc Le Marchand; Laurence N. Kolonel; Kristine R. Monroe; et al. (Cancer Causes & Control, 2018)

Corticosteroids and aldose reductase inhibitor Epalrestat modulates cardiac action potential via Kvβ1.1 (AKR6A8) subunit of voltage-gated potassium channel - Jared Tur; Sachin L. Badole; Feng Cheng; Aparoop Das; Rakesh C. Kukreja; Srinivas M. Tipparaju (Molecular and Cellular Biochemistry, 2017)

Untangling the proximate causes and underlying drivers of deforestation and forest degradation in Myanmar - Cheng Ling Lim; Graham W. Prescott; Jose Don T. De Alban; Alan D. Ziegler; Edward L. Webb (Conservation Biology, 2017)
Political transitions often trigger substantial environmental changes. In particular, deforestation can result from the complex interplay among the components of a system—actors, institutions, and existing policies—adapting to new opportunities. A dynamic conceptual map of system components is particularly useful for systems in which multiple actors, each with different worldviews and motivations, may be simultaneously trying to alter different facets of the system, unaware of the impacts on other components. In Myanmar, a global biodiversity hotspot with the largest forest area in mainland Southeast Asia, ongoing political and economic reforms are likely to change the dynamics of deforestation drivers. A fundamental conceptual map of these dynamics is therefore a prerequisite for interventions to reduce deforestation. We used a system‐dynamics approach and causal‐network analysis to determine the proximate causes and underlying drivers of forest loss and degradation in Myanmar from 1995 to 2016 and to articulate the linkages among them. Proximate causes included infrastructure development, timber extraction, and agricultural expansion. These were stimulated primarily by formal agricultural, logging, mining, and hydropower concessions and economic investment and social issues relating to civil war and land tenure. Reform of land laws, the link between natural resource extraction and civil war, and the allocation of agricultural concessions will influence the extent of future forest loss and degradation in Myanmar. The causal‐network analysis identified priority areas for policy interventions, for example, creating a public registry of land‐concession holders to deter corruption in concession allocation. We recommend application of this analytical approach to other countries, particularly those undergoing political transition, to inform policy interventions to reduce forest loss and degradation.

Political transition and emergent forest‐conservation issues in Myanmar - Graham W. Prescott; William J. Sutherland; Daniel Aguirre; Matthew Baird; Vicky Bowman; Jake Brunner; Grant M. Connette; Martin Cosier; David Dapice; Jose Don T. De Alban; Alex Diment; Julia Fogerite; et al. (Conservation Biology, 2017)
Political and economic transitions have had substantial impacts on forest conservation. Where transitions are underway or anticipated, historical precedent and methods for systematically assessing future trends should be used to anticipate likely threats to forest conservation and design appropriate and prescient policy measures to counteract them. Myanmar is transitioning from an authoritarian, centralized state with a highly regulated economy to a more decentralized and economically liberal democracy and is working to end a long‐running civil war. With these transitions in mind, we used a horizon‐scanning approach to assess the 40 emerging issues most affecting Myanmar's forests, including internal conflict, land‐tenure insecurity, large‐scale agricultural development, demise of state timber enterprises, shortfalls in government revenue and capacity, and opening of new deforestation frontiers with new roads, mines, and hydroelectric dams. Averting these threats will require, for example, overhauling governance models, building capacity, improving infrastructure‐ and energy‐project planning, and reforming land‐tenure and environmental‐protection laws. Although challenges to conservation in Myanmar are daunting, the political transition offers an opportunity for conservationists and researchers to help shape a future that enhances Myanmar's social, economic, and environmental potential while learning and applying lessons from other countries. Our approach and results are relevant to other countries undergoing similar transitions.

Larger but not louder: bigger honey bee colonies have quieter combs - Michael L Smith; Po-Cheng Chen (Behavioral Ecology and Sociobiology, 2017)

Neovascularization and Synaptic Function Regulation with Memantine and Rosuvastatin in a Rat Model of Chronic Cerebral Hypoperfusion - Nan Zhang; Chenchen Song; Baomin Zhao; Mengya Xing; Lanlan Luo; Marc L. Gordon; Yan Cheng (Journal of Molecular Neuroscience, 2017)

Serum 25-hydroxyvitamin D concentrations and lung cancer risk in never-smoking postmenopausal women - Ting-Yuan David Cheng; Xiaoling Song; Shirley A. A. Beresford; Gloria Y. F. Ho; Karen C. Johnson; Mridul Datta; Rowan T. Chlebowski; Jean Wactawski-Wende; Lihong Qi; Marian L. Neuhouser (Cancer Causes & Control, 2017)

Human subcortical brain asymmetries in 15,847 people worldwide reveal effects of age and sex - Tulio Guadalupe; Samuel R. Mathias; Theo G. M. vanErp; Christopher D. Whelan; Marcel P. Zwiers; Yoshinari Abe; Lucija Abramovic; Ingrid Agartz; Ole A. Andreassen; Alejandro Arias-Vásquez; Benjamin S. Aribisala; Nicola J. Armstrong; et al. (Brain Imaging and Behavior, 2017)

Molecular characterization of two Rhesus glycoproteins from the euryhaline freshwater white-rimmed stingray, Himantura signifer, and changes in their transcript levels and protein abundance in the gills, kidney, and liver during brackish water acclimation - Cheng T. Yeam; You R. Chng; Jasmine L. Y. Ong; Wai P. Wong; Shit F. Chew; Yuen K. Ip (Journal of Comparative Physiology B, 2017)

Using DNA barcoding to track seafood mislabeling in Los Angeles restaurants - Demian A. Willette; Sara E. Simmonds; Samantha H. Cheng; Sofia Esteves; Tonya L. Kane; Hayley Nuetzel; Nicholas Pilaud; Rita Rachmawati; Paul H. Barber (Conservation Biology, 2017)
Seafood mislabeling is common in both domestic and international markets. Studies on seafood fraud often report high rates of mislabeling (e.g., >70%), but these studies have been limited to a single sampling year, which means it is difficult to assess the impact of stricter governmental truth‐in‐labeling regulations. We used DNA barcoding to assess seafood labeling in 26 sushi restaurants in Los Angeles over 4 years. Seafood from 3 high‐end grocery stores were also sampled ( n = 16) in 2014. We ordered 9 common sushi fish from menus, preserved tissue samples in 95% ethanol, extracted the genomic DNA, amplified and sequenced a portion of the mtDNA COI gene, and identified the resulting sequence to known fish sequences from the National Center for Biotechnology Information nucleotide database. We compared DNA results with the U.S. Food and Drug Administration (FDA) list of acceptable market names and retail names. We considered sushi‐sample labels that were inconsistent with FDA names mislabeled. Sushi restaurants had a consistently high percentage of mislabeling (47%; 151 of 323) from 2012 to 2015, yet mislabeling was not homogenous across species. Halibut, red snapper, yellowfin tuna, and yellowtail had consistently high ( 15%). All sampled sushi restaurants had at least one case of mislabeling. Mislabeling of sushi‐grade fish from high‐end grocery stores was also identified in red snapper, yellowfin tuna, and yellowtail, but at a slightly lower frequency (42%) than sushi restaurants. Despite increased regulatory measures and media attention, we found seafood mislabeling continues to be prevalent.

Benign breast disease and risk of thyroid cancer - Juhua Luo; Michael Hendryx; Rami Nassir; Ting-Yuan David Cheng; Dorothy Lane; Karen L. Margolis (Cancer Causes & Control, 2017)

Timing of stressors alters interactive effects on a coastal foundation species - Jillian M. Bible; Brian S. Cheng; Andrew L. Chang; Matthew C. Ferner; Kerstin Wasson; Chela J. Zabin; Marilyn Latta; Eric Sanford; Anna Deck; Edwin D. Grosholz (Ecology, 2017)
The effects of climate‐driven stressors on organismal performance and ecosystem functioning have been investigated across many systems; however, manipulative experiments generally apply stressors as constant and simultaneous treatments, rather than accurately reflecting temporal patterns in the natural environment. Here, we assessed the effects of temporal patterns of high aerial temperature and low salinity on survival of Olympia oysters ( Ostrea lurida ), a foundation species of conservation and restoration concern. As single stressors, low salinity (5 and 10 psu) and the highest air temperature (40°C) resulted in oyster mortality of 55.8, 11.3, and 23.5%, respectively. When applied on the same day, low salinity and high air temperature had synergistic negative effects that increased oyster mortality. This was true even for stressor levels that were relatively mild when applied alone (10 psu and 35°C). However, recovery times of two or four weeks between stressors eliminated the synergistic effects. Given that most natural systems threatened by climate change are subject to multiple stressors that vary in the timing of their occurrence, our results suggest that it is important to examine temporal variation of stressors in order to more accurately understand the possible biological responses to global change.

Laser Sintered Porous Ti–6Al–4V Implants Stimulate Vertical Bone Growth - Alice Cheng; David J. Cohen; Adrian Kahn; Ryan M. Clohessy; Kaan Sahingur; Joseph B. Newton; Sharon L. Hyzy; Barbara D. Boyan; Zvi Schwartz (Annals of Biomedical Engineering, 2017)

Utilizing secondary agricultural education programs to deliver evidence-based grain safety training for young and beginning workers - Yuan-Hsin Cheng; William E Field; Roger L Tormoehlen; Brian F French (Journal of Agromedicine, 2017)

Acinetobacter baumannii bacteraemia in patients with haematological malignancy: a multicentre retrospective study from the Infection Working Party of Jiangsu Society of Hematology - X. Wang; L. Zhang; A. Sun; X. Yang; W. Sang; Y. Jiang; J. Cheng; J. Wang; M. Zhou; B. Chen; J. Ouyang (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

Lipid emulsion enhances cardiac performance after ischemia–reperfusion in isolated hearts from summer-active arctic ground squirrels - Michele M. Salzman; Qunli Cheng; Richard J. Deklotz; Gurpreet K. Dulai; Hunter F. Douglas; Anna E. Dikalova; Dorothee Weihrauch; Brian M. Barnes; Matthias L. Riess (Journal of Comparative Physiology B, 2017)

Pathogen dynamics during invasion and establishment of white‐nose syndrome explain mechanisms of host persistence - Winifred F. Frick; Tina L. Cheng; Kate E. Langwig; Joseph R. Hoyt; Amanda F. Janicki; Katy L. Parise; Jeffrey T. Foster; A. Marm Kilpatrick (Ecology, 2017)
Disease dynamics during pathogen invasion and establishment determine the impacts of disease on host populations and determine the mechanisms of host persistence. Temporal progression of prevalence and infection intensity illustrate whether tolerance, resistance, reduced transmission, or demographic compensation allow initially declining populations to persist. We measured infection dynamics of the fungal pathogen Pseudogymnoascus destructans that causes white‐nose syndrome in bats by estimating pathogen prevalence and load in seven bat species at 167 hibernacula over a decade as the pathogen invaded, became established, and some host populations stabilized. Fungal loads increased rapidly and prevalence rose to nearly 100% at most sites within 2 yr of invasion in six of seven species. Prevalence and loads did not decline over time despite huge reductions in colony sizes, likely due to an extensive environmental reservoir. However, there was substantial variation in fungal load among sites with persisting colonies, suggesting that both tolerance and resistance developed at different sites in the same species. In contrast, one species disappeared from hibernacula within 3 yr of pathogen invasion. Variable host responses to pathogen invasion require different management strategies to prevent disease‐induced extinction and to facilitate evolution of tolerance or resistance in persisting populations.

Recent declines in cancer incidence: related to the Great Recession? - Scarlett Lin Gomez; Alison J. Canchola; David O. Nelson; Theresa H. M. Keegan; Christina A. Clarke; Iona Cheng; Salma Shariff-Marco; Mindy DeRouen; Ralph Catalano; William A. Satariano; Kathleen Davidson-Allen; Sally L. Glaser (Cancer Causes & Control, 2017)

Erratum to: Small RNAs from a Big Genome: The piRNA Pathway and Transposable Elements in the Salamander Species Desmognathus fuscus - M. J. Madison-Villar; Cheng Sun; Nelson C. Lau; Matthew L. Settles; Rachel Lockridge Mueller (Journal of Molecular Evolution, 2017)

West African monsoon decadal variability and surface-related forcings: second West African Monsoon Modeling and Evaluation Project Experiment (WAMME II) - Yongkang Xue; Fernando De Sales; William K.-M. Lau; Aaron Boone; Kyu-Myong Kim; Carlos R. Mechoso; Guiling Wang; Fred Kucharski; Kathleen Schiro; Masahiro Hosaka; Suosuo Li; Leonard M. Druyan; et al. (Climate Dynamics, 2016)

Time Course Field Analysis of COMT-Downregulated Switchgrass: Lignification, Recalcitrance, and Rust Susceptibility - Holly L. Baxter; Mitra Mazarei; Chunxiang Fu; Qunkang Cheng; Geoffrey B. Turner; Robert W. Sykes; Mark T. Windham; Mark F. Davis; Richard A. Dixon; Zeng-Yu Wang; C. Neal Stewart (BioEnergy Research, 2016)

Prevalence of bacterial resistance within an eco-agricultural system in Hangzhou, China - Like Xu; Yanyun Qian; Chao Su; Weixiao Cheng; Jianan Li; Mark L. Wahlqvist; Hong Chen (Environmental Science and Pollution Research, 2016)

Small RNAs from a Big Genome: The piRNA Pathway and Transposable Elements in the Salamander Species Desmognathus fuscus - M. J. Madison-Villar; Cheng Sun; Nelson C. Lau; Matthew L. Settles; Rachel Lockridge Mueller (Journal of Molecular Evolution, 2016)

Mycorrhizal fungi and roots are complementary in foraging within nutrient patches - Lei Cheng; Weile Chen; Thomas S. Adams; Xing Wei; Le Li; Michael Luke McCormack; Jared L. DeForest; Roger T. Koide; David M. Eissenstat (Ecology, 2016)
The roots of the majority of tree species are associated with either arbuscular mycorrhizal (AM) or ectomycorrhizal (EM) fungi. The absorptive roots of tree species also vary widely in their diameter. The linkages between root thickness, mycorrhiza type and nutrient foraging are poorly understood. We conducted a large root ingrowth experiment in the field to investigate how absorptive roots of varying thickness and their associated fungi (AM vs. EM) exploit different nutrient patches (inorganic and organic) in a common garden. In nutrient‐rich patches, thin‐root tree species more effectively proliferated absorptive roots than thick‐root tree species, whereas thick‐root tree species proliferated more mycorrhizal fungal biomass than thin‐root tree species. Moreover, nutrient patches enriched with organic materials resulted in greater root and mycorrhizal fungal proliferation compared to those enriched with inorganic nutrients. Irrespective of root morphology, AM tree species had higher root foraging precision than mycorrhizal hyphae foraging precision within organic patches, whereas EM tree species exhibited the opposite. Our findings that roots and mycorrhizal fungi are complementary in foraging within nutrient patches provide new insights into species coexistence and element cycling in terrestrial ecosystems.

Effects of Palygorskite Inclusion on the Growth Performance, Meat Quality, Antioxidant Ability, and Mineral Element Content of Broilers - Y. F. Cheng; Y. P. Chen; X. H. Li; W. L. Yang; C. Wen; Y. M. Zhou (Biological Trace Element Research, 2016)

Identifying microRNAs targeting Wnt/β-catenin pathway in end-stage idiopathic pulmonary arterial hypertension - Danchen Wu; C. Conover Talbot; Qun Liu; Zhi-Cheng Jing; Rachel L. Damico; Rubin Tuder; Kathleen C. Barnes; Paul M. Hassoun; Li Gao (Journal of Molecular Medicine, 2016)

Increased rodenticide exposure rate and risk of toxicosis in barn owls (Tyto alba) from southwestern Canada and linkage with demographic but not genetic factors - Andrew C. Huang; John E. Elliott; Sofi Hindmarch; Sandi L. Lee; France Maisonneuve; Victoria Bowes; Kimberly M. Cheng; Kathy Martin (Ecotoxicology, 2016)

Toxicity and in vitro activity of HIV-1 latency-reversing agents in primary CNS cells - Lachlan R. Gray; Hung On; Emma Roberts; Hao K. Lu; Michael A. Moso; Jacqueline A. Raison; Catherine Papaioannou; Wan-Jung Cheng; Anne M. Ellett; Jonathan C. Jacobson; Damian F. J. Purcell; Steve L. Wesselingh; et al. (Journal of NeuroVirology, 2016)

Characterization of a New Wheat- Aegilops biuncialis 1M b (1B) Substitution Line with Good Quality-associated HMW Glutenin Subunit - J. P. Zhou; Y. Cheng; L. L. Zang; E. N. Yang; C. Liu; X. L. Zheng; K. J. Deng; Y. Q. Zhu; Y. Zhang (Cereal Research Communications, 2016)

Mitigation of multipath effect in GNSS short baseline positioning by the multipath hemispherical map - D. Dong; M. Wang; W. Chen; Z. Zeng; L. Song; Q. Zhang; M. Cai; Y. Cheng; J. Lv (Journal of Geodesy, 2016)

Characterization of carbapenem-resistant Escherichia coli and Klebsiella pneumoniae from a healthcare region in Hong Kong - P. L. Ho; Y. Y. Cheung; Y. Wang; W. U. Lo; E. L. Y. Lai; K. H. Chow; V. C. C. Cheng (European Journal of Clinical Microbiology & Infectious Diseases, 2016)

Validation of self-reported comorbidity status of breast cancer patients with medical records: the California Breast Cancer Survivorship Consortium (CBCSC) - Cheryl Vigen; Marilyn L. Kwan; Esther M. John; Scarlett Lin Gomez; Theresa H. M. Keegan; Yani Lu; Salma Shariff-Marco; Kristine R. Monroe; Allison W. Kurian; Iona Cheng; Bette J. Caan; Valerie S. Lee; et al. (Cancer Causes & Control, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Synoptic controls of outer mesoscale convective systems with high impact rainfall in western north pacific tropical cyclones - Buo-Fu Chen; Russell L. Elsberry; Cheng-Shang Lee (Asia-Pacific Journal of Atmospheric Sciences, 2016)

Modeling driving forces of avian diversity in a spatial configuration surrounded by farm ponds - Wei-Ta Fang; Bai-You Cheng; Shang-Shu Shih; Jui-Yu Chou; Marinus L. Otte (Paddy and Water Environment, 2016)

Three N-Glycosylation Sites of Human Acetylcholinesterase Shares Similar Glycan Composition - Miranda L. Xu; Wilson K. W. Luk; Kei M. Lau; Cathy W. C. Bi; Anthony W. M. Cheng; Amy G. W. Gong; Huangquan Lin; Karl W. K. Tsim (Journal of Molecular Neuroscience, 2015)

Use of fluoroquinolones is the single most important risk factor for the high bacterial load in patients with nasal and gastrointestinal colonization by multidrug-resistant Acinetobacter baumannii - V. C. C. Cheng; J. H. K. Chen; S. Y. C. So; S. C. Y. Wong; M. K. Yan; P. H. Chau; W. M. Lee; K. K. W. To; J. F. W. Chan; I. F. N. Hung; P. L. Ho; K. Y. Yuen (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

Speciation processes in putative island endemic sister bat species: false impressions from mitochondrial DNA and microsatellite data - Hao‐Chih Kuo; Shiang‐Fan Chen; Yin‐Ping Fang; James A. Cotton; Joe D. Parker; Gábor Csorba; Burton K. Lim; Judith L. Eger; Chia‐Hong Chen; Cheng‐Han Chou; Stephen J. Rossiter (Molecular Ecology, 2015)
Cases of geographically restricted co‐occurring sister taxa are rare and may point to potential divergence with gene flow. The two bat species Murina gracilis and Murina recondita are both endemic to Taiwan and are putative sister species. To test for nonallopatric divergence and gene flow in these taxa, we generated sequences using Sanger and next‐generation sequencing, and combined these with microsatellite data for coalescent‐based analyses. Mt DNA phylogenies supported the reciprocally monophyletic sister relationship between M. gracilis and M. recondita ; however, clustering of microsatellite genotypes revealed several cases of species admixture suggesting possible introgression. Sequencing of microsatellite flanking regions revealed that admixture signatures stemmed from microsatellite allele homoplasy rather than recent introgressive hybridization, and also uncovered an unexpected sister relationship between M. recondita and the continental species Murina eleryi , to the exclusion of M. gracilis . To dissect the basis of these conflicts between nc DNA and mt DNA , we analysed sequences from 10 anonymous nc DNA loci with * beast and isolation‐with‐migration and found two distinct clades of M. eleryi , one of which was sister to M. recondita . We conclude that Taiwan was colonized by the ancestor of M. gracilis first, followed by the ancestor of M. recondita after a period of allopatric divergence. After colonization, the mitochondrial genome of M. recondita was replaced by that of the resident M. gracilis . This study illustrates how apparent signatures of sympatric divergence can arise from complex histories of allopatric divergence, colonization and hybridization, thus highlighting the need for rigorous analyses to distinguish between such scenarios.

Reduced Expression of P2Y2 Receptor and Acetylcholinesterase at Neuromuscular Junction of P2Y1 Receptor Knock-out Mice - Miranda L. Xu; Cathy W.C. Bi; Lily K.W. Cheng; Shinghung Mak; Ping Yao; Wilson K.W. Luk; Kitty K.M. Lau; Anthony W.M. Cheng; Karl W.K. Tsim (Journal of Molecular Neuroscience, 2015)

Global representation of tropical cyclone-induced short-term ocean thermal changes using Argo data - L. Cheng; J. Zhu; R. L. Sriver (Ocean Science, 2015)
Argo floats are used to examine tropical cyclone (TC) induced ocean thermal changes on the global scale by comparing temperature profiles before and after TC passage. We present a footprint method that analyzes cross-track thermal responses along all storm tracks during the period 2004–2012. We combine the results into composite representations of the vertical structure of the average thermal response for two different categories: tropical storms/tropical depressions (TS/TD) and hurricanes. The two footprint composites are functions of three variables: cross-track distance, water depth and time relative to TC passage. We find that this footprint strategy captures the major features of the upper-ocean thermal response to TCs on timescales up to 20 days when compared against previous case study results using in situ measurements. On the global scale, TCs are responsible for 1.87 PW (11.05 W m−2) of heat transfer annually from the global ocean to the atmosphere during storm passage (0–3 days). Of this total, 1.05 ± 0.20 PW (4.80 ± 0.85 W m−2) is caused by TS/TD and 0.82 ± 0.21 PW (6.25 ± 1.5 W m−2) is caused by hurricanes. Our findings indicate that ocean heat loss by TCs may be a substantial missing piece of the global ocean heat budget. Changes in ocean heat content (OHC) after storm passage are estimated by analyzing the temperature anomalies during wake recovery following storm events (4–20 days after storm passage) relative to pre-storm conditions. Results indicate the global ocean experiences a 0.75 ± 0.25 PW (5.98 ± 2.1 W m−2) heat gain annually for hurricanes. In contrast, under TS/TD conditions, the ocean experiences 0.41 ± 0.21 PW (1.90 ± 0.96 W m−2) ocean heat loss, suggesting the overall oceanic thermal response is particularly sensitive to the intensity of the event. The ocean heat uptake caused by all storms during the restorative stage is 0.34 PW.

Effect of norbinaltorphimine on ∆9-tetrahydrocannabinol (THC)-induced taste avoidance in adolescent and adult Sprague-Dawley rats - Shaun M. Flax; Alison G. P. Wakeford; Kejun Cheng; Kenner C. Rice; Anthony L. Riley (Psychopharmacology, 2015)

Performance of the new automated Abbott RealTime MTB assay for rapid detection of Mycobacterium tuberculosis complex in respiratory specimens - J. H. K. Chen; K. K. K. She; T.-C. Kwong; O.-Y. Wong; G. K. H. Siu; C.-C. Leung; K.-C. Chang; C.-M. Tam; P.-L. Ho; V. C. C. Cheng; K.-Y. Yuen; W.-C. Yam (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

Historical and experimental evidence for enhanced concentration of artemesinin, a global anti-malarial treatment, with recent and projected increases in atmospheric carbon dioxide - C. Zhu; Q. Zeng; A. McMichael; K. L. Ebi; K. Ni; A. S. Khan; J. Zhu; G. Liu; X. Zhang; Lei Cheng; L.H. Ziska (Climatic Change, 2015)

A stepwise-cluster forecasting approach for monthly streamflows based on climate teleconnections - Y. R. Fan; W. Huang; G. H. Huang; Z. Li; Y. P. Li; X. Q. Wang; G. H. Cheng; L. Jin (Stochastic Environmental Research and Risk Assessment, 2015)

RETRACTED ARTICLE: Degradation of βII-Spectrin Protein by Calpain-2 and Caspase-3 Under Neurotoxic and Traumatic Brain Injury Conditions - Firas H. Kobeissy; Ming Cheng Liu; Zhihui Yang; Zhiqun Zhang; Wenrong Zheng; Olena Glushakova; Stefania Mondello; John Anagli; Ronald L. Hayes; Kevin K. W. Wang (Molecular Neurobiology, 2015)

Chromosomal genomics facilitates fine mapping of a Russian wheat aphid resistance gene - Helena Staňková; Miroslav Valárik; Nora L. V. Lapitan; Paul J. Berkman; Jacqueline Batley; David Edwards; Ming-Cheng Luo; Zuzana Tulpová; Marie Kubaláková; Nils Stein; Jaroslav Doležel; Hana Šimková (Theoretical and Applied Genetics, 2015)

Containment of Clostridium difficile infection without reduction in antimicrobial use in Hong Kong - V. C. C. Cheng; P. H. Chau; S. Y. C. So; J. H. K. Chen; R. W. S. Poon; S. C. Y. Wong; I. F. N. Hung; W. M. Lee; J. W. M. Tai; P. L. Ho; W. C. Yam; K. Y. Yuen (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

Assessing the genetic diversity and resistance to Cucumber mosaic virus and Tobacco etch virus of tobacco cultivars in China - W. Chen; Z. P. Luo; W. T. Liu; H. Liu; D. F. Ma; J. H. Snyder; X. Li; T. Huang; J. L. Cheng; X. Xie; Y. F. Wu (Australasian Plant Pathology, 2015)

Testing local and global stressor impacts on a coastal foundation species using an ecologically realistic framework - Brian S. Cheng; Jillian M. Bible; Andrew L. Chang; Matthew C. Ferner; Kerstin Wasson; Chela J. Zabin; Marilyn Latta; Anna Deck; Anne E. Todgham; Edwin D. Grosholz (Global Change Biology, 2015)
Despite the abundance of literature on organismal responses to multiple environmental stressors, most studies have not matched the timing of experimental manipulations with the temporal pattern of stressors in nature. We test the interactive effects of diel‐cycling hypoxia with both warming and decreased salinities using ecologically realistic exposures. Surprisingly, we found no evidence of negative synergistic effects on Olympia oyster growth; rather, we found only additive and opposing effects of hypoxia (detrimental) and warming (beneficial). We suspect that diel‐cycling provided a temporal refuge that allowed physiological compensation. We also tested for latent effects of warming and hypoxia to low‐salinity tolerance using a seasonal delay between stressor events. However, we did not find a latent effect, rather a threshold survival response to low salinity that was independent of early life‐history exposure to warming or hypoxia. The absence of synergism is likely the result of stressor treatments that mirror the natural timing of environmental stressors. We provide environmental context for laboratory experimental data by examining field time series environmental data from four North American west coast estuaries and find heterogeneous environmental signals that characterize each estuary, suggesting that the potential stressor exposure to oysters will drastically differ over moderate spatial scales. This heterogeneity implies that efforts to conserve and restore oysters will require an adaptive approach that incorporates knowledge of local conditions. We conclude that studies of multiple environmental stressors can be greatly improved by integrating ecologically realistic exposure and timing of stressors found in nature with organismal life‐history traits.

The RIG-I-like helicase receptor MDA5 (IFIH1) is involved in the host defense against Candida infections - M. Jaeger; R. van der Lee; S.-C. Cheng; M. D. Johnson; V. Kumar; A. Ng; T. S. Plantinga; S. P. Smeekens; M. Oosting; X. Wang; W. Barchet; K. Fitzgerald; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

Functional link between muscarinic receptors and large-conductance Ca2+-activated K+ channels in freshly isolated human detrusor smooth muscle cells - Shankar P. Parajuli; Kiril L. Hristov; Qiuping Cheng; John Malysz; Eric S. Rovner; Georgi V. Petkov (Pflügers Archiv - European Journal of Physiology, 2015)

Testing the mutant selection window hypothesis in vitro and in vivo with Staphylococcus aureus exposed to fosfomycin - Q. Mei; Y. Ye; Y.-L. Zhu; J. Cheng; X. Chang; Y.-Y. Liu; H.-R. Li; J.-B. Li (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

Control of hospital endemicity of multiple-drug-resistant Acinetobacter baumannii ST457 with directly observed hand hygiene - V. C. C. Cheng; J. H. K. Chen; R. W. S. Poon; W. M. Lee; S. Y. C. So; S. C. Y. Wong; P. H. Chau; C. C. Y. Yip; S. S. Y. Wong; J. F. W. Chan; I. F. N. Hung; P. L. Ho; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

Mapping QTLs of caudal fin length in common carp ( Cyprinus carpio L.) - C Lu; Y Zhang; X Zheng; X Zhang; C Li; Y Kuang; D Cao; L Cheng; G Qiu; X Sun (New Zealand Journal of Marine and Freshwater Research, 2015)
Common carp ( Cyprinus carpio L.) exhibits significant morphological variability in the shape and size of the caudal fin. In this study, we used 190 progeny from two F 1 parents to identify and map quantitative trait loci (QTLs) that influence caudal fin length ( CFL ) and the ratio ( RCS ) between caudal fin length and standard length ( SL ) based on a microsatellite genetic map of common carp. A total of 15 QTLs were detected in seven different linkage groups. One significant and eight suggestive QTLs affecting CFL were identified on LG8, LG14, LG29, LG32 and LG44, which explained 8.0%–22.1% of the phenotypic variation; six suggestive QTLs affecting RCS were detected on LG8, LG32, LG46 and LG48, which explained 7.0%–15.4% of the phenotypic variation. The QTLs for caudal fin length detected in this study may serve as a starting point for identification of genes involved in caudal fin development in common carp.

Development and characterization of two monoclonal antibodies against grouper iridovirus 55L and 97L proteins - S‐L Hu; C‐J Liou; Y‐H Cheng; J‐C Yiu; P P Chiou; Y‐S Lai (Journal of Fish Diseases, 2015)
Grouper iridovirus (GIV) is one of the most important viral pathogens in grouper, particularly at the fry and fingerling stages. The study of GIV pathogenicity has been hampered by the lack of proper immunological reagents to study the expression and function of viral proteins in the infected cells. In this study, two mouse monoclonal antibodies ( mA bs) against GIV 55L and 97L proteins were produced. Enzyme‐linked immunosorbent assay (ELISA) and Western blotting were used to screen these hybridomas, resulting in the identification of two high‐affinity mA bs named GIV55L‐ mA b‐2 and GIV97L‐ mA b‐3, respectively. Both mA bs belong to the IgG1 isotype and were effective in detecting their respective target viral protein. Reverse‐transcription polymerase chain reaction (RT‐PCR) and Western blot analyses of GIV‐infected GK cells revealed that GIV 97L is an immediate early gene, whereas GIV 55L a late one. The localization of 55L and 97L in GIV‐infected cells was further characterized by immunofluorescence microscopy with the mA bs. The 55L protein mainly aggregated in the cytoplasm while 97L distributed in both the nucleus and cytoplasm of the infected cells. These studies demonstrate the validity of the two mA bs as immunodiagnostic and research reagents.

Candidate locus analysis of the TERT–CLPTM1L cancer risk region on chromosome 5p15 identifies multiple independent variants associated with endometrial cancer risk - Luis G. Carvajal-Carmona; Tracy A. O’Mara; Jodie N. Painter; Felicity A. Lose; Joe Dennis; Kyriaki Michailidou; Jonathan P. Tyrer; Shahana Ahmed; Kaltin Ferguson; Catherine S. Healey; Karen Pooley; Jonathan Beesley; et al. (Human Genetics, 2015)

Genome-wide association study for refractive astigmatism reveals genetic co-determination with spherical equivalent refractive error: the CREAM consortium - Qing Li; Robert Wojciechowski; Claire L. Simpson; Pirro G. Hysi; Virginie J. M. Verhoeven; Mohammad Kamran Ikram; René Höhn; Veronique Vitart; Alex W. Hewitt; Konrad Oexle; Kari-Matti Mäkelä; Stuart MacGregor; et al. (Human Genetics, 2015)

Effects of Five Naturally Occurring Sugars on the Longevity, Oogenesis, and Nutrient Accumulation Pattern in Adult Females of the Synovigenic Parasitoid Neochrysocharis formosa (Hymenoptera: Eulophidae) - W Wang; S-L Lu; W-X Liu; L-S Cheng; Y-B Zhang; F-H Wan (Neotropical Entomology, 2014)

Ornamental Marine Species Culture in the Coral Triangle: Seahorse Demonstration Project in the Spermonde Islands, Sulawesi, Indonesia - Susan L. Williams; Noel Janetski; Jessica Abbott; Sven Blankenhorn; Brian Cheng; R. Eliot Crafton; Sarah O. Hameed; Saipul Rapi; Dale Trockel (Environmental Management, 2014)

A Solution for Flood Control in Urban Area: Using Street Block and Raft Foundation Space Operation Model - Y. C. Liu; C. L. Cheng (Water Resources Management, 2014)

Desert ants (Melophorus bagoti) navigating with robustness to distortions of the natural panorama - S. Schwarz; E. Julle-Daniere; L. Morin; P. Schultheiss; A. Wystrach; J. Ives; K. Cheng (Insectes Sociaux, 2014)

Structural integrity affects nitrogen removal activity of granules in semi-continuous reactors - Cesar R. Mota; Melanie A. Head; Jon C. Williams; Lucy Eland; Jay J. Cheng; Francis L. de los Reyes (Biodegradation, 2014)

Molecular mapping of genes Yr64 and Yr65 for stripe rust resistance in hexaploid derivatives of durum wheat accessions PI 331260 and PI 480016 - P. Cheng; L. S. Xu; M. N. Wang; D. R. See; X. M. Chen (Theoretical and Applied Genetics, 2014)

The hidden history of the snowshoe hare, L epus americanus : extensive mitochondrial DNA introgression inferred from multilocus genetic variation - José Melo‐Ferreira; Fernando A. Seixas; Ellen Cheng; L. Scott Mills; Paulo C. Alves (Molecular Ecology, 2014)
Hybridization drives the evolutionary trajectory of many species or local populations, and assessing the geographic extent and genetic impact of interspecific gene flow may provide invaluable clues to understand population divergence or the adaptive relevance of admixture. In N orth A merica, hares ( L epus spp.) are key species for ecosystem dynamics and their evolutionary history may have been affected by hybridization. Here we reconstructed the speciation history of the three most widespread hares in N orth A merica – the snowshoe hare ( L epus americanus ), the white‐tailed jackrabbit ( L . townsendii ) and the black‐tailed jackrabbit ( L . californicus ) – by analysing sequence variation at eight nuclear markers and one mitochondrial DNA (mt DNA ) locus (6240 bp; 94 specimens). A multilocus–multispecies coalescent‐based phylogeny suggests that L . americanus diverged ~2.7 Ma and that L . californicus and L . townsendii split more recently (~1.2 Ma). Within L . americanus, a deep history of cryptic divergence (~2.0 Ma) was inferred, which coincides with major speciation events in other N orth A merican species. While the isolation‐with‐migration model suggested that nuclear gene flow was generally rare or absent among species or major genetic groups, coalescent simulations of mt DNA divergence revealed historical mt DNA introgression from L . californicus into the P acific N orthwest populations of L . americanus . This finding marks a history of past reticulation between these species, which may have affected other parts of the genome and influence the adaptive potential of hares during climate change.

Conservation implications of the evolutionary history and genetic diversity hotspots of the snowshoe hare - Ellen Cheng; Karen E. Hodges; José Melo‐Ferreira; Paulo C. Alves; L. Scott Mills (Molecular Ecology, 2014)
With climate warming, the ranges of many boreal species are expected to shift northward and to fragment in southern peripheral ranges. To understand the conservation implications of losing southern populations, we examined range‐wide genetic diversity of the snowshoe hare ( Lepus americanus ), an important prey species that drives boreal ecosystem dynamics. We analysed microsatellite (8 loci) and mitochondrial DNA sequence (cytochrome b and control region) variation in almost 1000 snowshoe hares. A hierarchical structure analysis of the microsatellite data suggests initial subdivision in two groups, Boreal and southwestern. The southwestern group further splits into Greater Pacific Northwest and U.S. Rockies. The genealogical information retrieved from mt DNA is congruent with the three highly differentiated and divergent groups of snowshoe hares. These groups can correspond with evolutionarily significant units that might have evolved in separate refugia south and east of the Pleistocene ice sheets. Genetic diversity was highest at mid‐latitudes of the species' range, and genetic uniqueness was greatest in southern populations, consistent with substructuring inferred from both mt DNA and microsatellite analyses at finer levels of analysis. Surprisingly, snowshoe hares in the Greater Pacific Northwest mt DNA lineage were more closely related to black‐tailed jackrabbits (Lepus californicus ) than to other snowshoe hares, which may result from secondary introgression or shared ancestral polymorphism. Given the genetic distinctiveness of southern populations and minimal gene flow with their northern neighbours, fragmentation and loss of southern boreal habitats could mean loss of many unique alleles and reduced evolutionary potential.

Genome‐wide single‐generation signatures of local selection in the panmictic E uropean eel - J. M. Pujolar; M. W. Jacobsen; T. D. Als; J. Frydenberg; K. Munch; B. Jónsson; J. B. Jian; L. Cheng; G. E. Maes; L. Bernatchez; M. M. Hansen (Molecular Ecology, 2014)
Next‐generation sequencing and the collection of genome‐wide data allow identifying adaptive variation and footprints of directional selection. Using a large SNP data set from 259 RAD ‐sequenced E uropean eel individuals (glass eels) from eight locations between 34 and 64 o N, we examined the patterns of genome‐wide genetic diversity across locations. We tested for local selection by searching for increased population differentiation using F ST ‐based outlier tests and by testing for significant associations between allele frequencies and environmental variables. The overall low genetic differentiation found ( F ST = 0.0007) indicates that most of the genome is homogenized by gene flow, providing further evidence for genomic panmixia in the E uropean eel. The lack of genetic substructuring was consistent at both nuclear and mitochondrial SNP s. Using an extensive number of diagnostic SNP s, results showed a low occurrence of hybrids between E uropean and A merican eel, mainly limited to Iceland (5.9%), although individuals with signatures of introgression several generations back in time were found in mainland Europe. Despite panmixia, a small set of SNP s showed high genetic differentiation consistent with single‐generation signatures of spatially varying selection acting on glass eels. After screening 50 354 SNP s, a total of 754 potentially locally selected SNP s were identified. Candidate genes for local selection constituted a wide array of functions, including calcium signalling, neuroactive ligand–receptor interaction and circadian rhythm. Remarkably, one of the candidate genes identified is PERIOD , possibly related to differences in local photoperiod associated with the >30° difference in latitude between locations. Genes under selection were spread across the genome, and there were no large regions of increased differentiation as expected when selection occurs within just a single generation due to panmixia. This supports the conclusion that most of the genome is homogenized by gene flow that removes any effects of diversifying selection from each new generation.

Atmospheric emission inventory of cadmium from anthropogenic sources - K. Cheng; H. Z. Tian; D. Zhao; L. Lu; Y. Wang; J. Chen; X. G. Liu; W. X. Jia; Z. Huang (International Journal of Environmental Science and Technology, 2014)

Effects of Parkinson’s disease on optic flow perception for heading direction during navigation - Cheng-Chieh Lin; Robert C. Wagenaar; Daniel Young; Elliot L. Saltzman; Xiaolin Ren; Sandy Neargarder; Alice Cronin-Golomb (Experimental Brain Research, 2014)

A Biophysically Based Finite-State Machine Model for Analyzing Gastric Experimental Entrainment and Pacing Recordings - Shameer Sathar; Mark L. Trew; Peng Du; Greg O’Grady; Leo K. Cheng (Annals of Biomedical Engineering, 2014)

Water, sediment, and nutrient runoff from urban lawns established on disturbed subsoil or topsoil and managed with inorganic or organic fertilizers - Zhiqiang Cheng; Edward L. McCoy; Parwinder S. Grewal (Urban Ecosystems, 2014)

Influence of Unloading Rate on the Strainburst Characteristics of Beishan Granite Under True-Triaxial Unloading Conditions - X. G. Zhao; J. Wang; M. Cai; C. Cheng; L. K. Ma; R. Su; F. Zhao; D. J. Li (Rock Mechanics and Rock Engineering, 2014)

Peginterferon plus Chinese herbal therapy is associated with a higher virological response than only peginterferon therapy in chronic hepatitis C - D. Cheng; E. Liu; Y. Li; R. Liu; L. Bai; Y. Chen; Y. Wang; Y. Chu; M. Wu; G. Cheng; S. Zhao (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Trends in the susceptibility of methicillin-resistant Staphylococcus aureus to nine antimicrobial agents, including ceftobiprole, nemonoxacin, and tyrothricin: results from the Tigecycline In Vitro Surveillance in Taiwan (TIST) study, 2006–2010 - Y.-H. Chen; C.-Y. Liu; W.-C. Ko; C.-H. Liao; P.-L. Lu; C.-H. Huang; C.-T. Lu; Y.-C. Chuang; S.-M. Tsao; Y.-S. Chen; Y.-C. Liu; W.-Y. Chen; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Potential role of winter rainfall in explaining increased moisture in the Mediterranean and Middle East during periods of maximum orbitally-forced insolation seasonality - J. E. Kutzbach; G. Chen; H. Cheng; R. L. Edwards; Z. Liu (Climate Dynamics, 2014)

Optimism and Challenge for Science‐Based Conservation of Migratory Species in and out of U.S. National Parks - JOEL BERGER; STEVEN L. CAIN; ELLEN CHENG; PETER DRATCH; KEVIN ELLISON; JOHN FRANCIS; HERBERT C. FROST; SCOTT GENDE; CRAIG GROVES; WILLIAM A. KARESH; ELAINE LESLIE; GARY MACHLIS; et al. (Conservation Biology, 2014)
Public agencies sometimes seek outside guidance when capacity to achieve their mission is limited. Through a cooperative agreement and collaborations with the U.S. National Park Service (NPS), we developed recommendations for a conservation program for migratory species. Although NPS manages ∼36 million hectares of land and water in 401 units, there is no centralized program to conserve wild animals reliant on NPS units that also migrate hundreds to thousands of kilometers beyond parks. Migrations are imperiled by habitat destruction, unsustainable harvest, climate change, and other impediments. A successful program to counter these challenges requires public support, national and international outreach, and flourishing migrant populations. We recommended two initial steps. First, in the short term, launch or build on a suite of projects for high‐profile migratory species that can serve as proof to demonstrate the centrality of NPS units to conservation at different scales. Second, over the longer term, build new capacity to conserve migratory species. Capacity building will entail increasing the limited knowledge among park staff about how and where species or populations migrate, conditions that enable migration, and identifying species’ needs and resolving them both within and beyond parks. Building capacity will also require ensuring that park superintendents and staff at all levels support conservation beyond statutory borders. Until additional diverse stakeholders and a broader American public realize what can be lost and do more to protect it and engage more with land management agencies to implement actions that facilitate conservation, long distance migrations are increasingly likely to become phenomena of the past. Optimismo y Retos para la Conservación Científicamente Basada de Especies Migratorias Dentro y Fuera de Parques Nacionales de E.U.A.

No evidence of interaction between known lipid-associated genetic variants and smoking in the multi-ethnic PAGE population - Logan Dumitrescu; Cara L. Carty; Nora Franceschini; Lucia A. Hindorff; Shelley A. Cole; Petra Bůžková; Fredrick R. Schumacher; Charles B. Eaton; Robert J. Goodloe; David J. Duggan; Jeff Haessler; Barbara Cochran; et al. (Human Genetics, 2013)

The association between pro-inflammatory cytokines, regional cerebral metabolism, and cognitive complaints following adjuvant chemotherapy for breast cancer - K. L. Pomykala; P. A. Ganz; J. E. Bower; L. Kwan; S. A. Castellon; S. Mallam; I. Cheng; R. Ahn; E. C. Breen; M. R. Irwin; D. H. S. Silverman (Brain Imaging and Behavior, 2013)

“Megavirales”, a proposed new order for eukaryotic nucleocytoplasmic large DNA viruses - Philippe Colson; Xavier De Lamballerie; Natalya Yutin; Sassan Asgari; Yves Bigot; Dennis K. Bideshi; Xiao-Wen Cheng; Brian A. Federici; James L. Van Etten; Eugene V. Koonin; Bernard La Scola; Didier Raoult (Archives of Virology, 2013)

White spot syndrome virus epizootic in cultured P acific white shrimp L itopenaeus vannamei (Boone) in T aiwan - L Cheng; W‐H Lin; P‐C Wang; M‐A Tsai; J‐P Hsu; S‐C Chen (Journal of Fish Diseases, 2013)
White spot syndrome virus ( WSSV ) has caused significant losses in shrimp farms worldwide. Between 2004 and 2006, Pacific white shrimp L itopenaeus vannamei (Boone) were collected from 220 farms in T aiwan to determine the prevalence and impact of WSSV infection on the shrimp farm industry. Polymerase chain reaction ( PCR ) analysis detected WSSV in shrimp from 26% of farms. Juvenile shrimp farms had the highest infection levels (38%; 19/50 farms) and brooder shrimp farms had the lowest (5%; one of 20 farms). The average extent of infection at each farm was as follows for WSSV ‐positive farms: post‐larvae farms, 71%; juvenile farms, 61%; subadult farms, 62%; adult farms, 49%; and brooder farms, 40%. Characteristic white spots, hypertrophied nuclei and basophilic viral inclusion bodies were found in the epithelia of gills and tail fans, appendages, cephalothorax and hepatopancreas, and virions of WSSV were observed. Of shrimp that had WSSV lesions, 100% had lesions on the cephalothorax, 96% in gills and tail fans, 91% on appendages and 17% in the hepatopancreas. WSSV was also detected in copepoda and crustaceans from the shrimp farms. Sequence comparison using the pms146 gene fragment of WSSV showed that isolates from the farms had 99.7–100% nucleotide sequence identity with four strains in the G en B ank database – China ( AF332093 ), T aiwan ( AF440570 and U50923 ) and Thailand ( AF369029 ). This is the first broad study of WSSV infection in L . vannamei in T aiwan.

The California Breast Cancer Survivorship Consortium (CBCSC): prognostic factors associated with racial/ethnic differences in breast cancer survival - Anna H. Wu; Scarlett Lin Gomez; Cheryl Vigen; Marilyn L. Kwan; Theresa H. M. Keegan; Yani Lu; Salma Shariff-Marco; Kristine R. Monroe; Allison W. Kurian; Iona Cheng; Bette J. Caan; Valerie S. Lee; et al. (Cancer Causes & Control, 2013)

An empirical comparison of character‐based and coalescent‐based approaches to species delimitation in a young avian complex - Bailey D. McKay; Herman L. Mays; Yuchun Wu; Hui Li; Cheng‐te Yao; Isao Nishiumi; Fasheng Zou (Molecular Ecology, 2013)
The process of discovering species is a fundamental responsibility of systematics. Recently, there has been a growing interest in coalescent‐based methods of species delimitation aimed at objectively identifying species early in the divergence process. However, few empirical studies have compared these new methods with character‐based approaches for discovering species. In this study, we applied both a character‐based and a coalescent‐based approaches to delimit species in a closely related avian complex, the light‐vented/Taiwan bulbul ( P ycnonotus sinensis / P ycnonotus taivanus ). Population aggregation analyses of plumage, mitochondrial and 13 nuclear intron character data sets produced conflicting species hypotheses with plumage data suggesting three species, mitochondrial data suggesting two species, and nuclear intron data suggesting one species. Such conflict is expected among recently diverged species, and by integrating all sources of data, we delimited three species verified with independently congruent character evidence as well as a more weakly supported fourth species identified by a single character. Attempts to validate species hypothesis using B ayesian P hylogenetics and P hylogeography ( BPP ), a coalescent‐based method of species delimitation, revealed several issues that can seemingly affect statistical support for species recognition. We found that θ priors had a dramatic impact on speciation probabilities, with lower values consistently favouring splitting and higher values consistently favouring lumping. More resolved guide trees also resulted in overall higher speciation probabilities. Finally, we found suggestive evidence that BPP is sensitive to the divergent effects of nonrandom mating caused by intraspecific processes such as isolation‐with‐distance, and therefore, BPP may not be a conservative method for delimiting independently evolving population lineages. Based on these concerns, we questioned the reliability of BPP results and based our conclusions about species limits exclusively on character data.

Characterization of a novel cell line from the caudal fin of koi carp Cyprinus carpio - S.‐L. Lin; Y.‐H. Cheng; C.‐M. Wen; S.‐N. Chen (Journal of Fish Biology, 2013)
A continuous cell line ( KF ‐101) derived from the caudal fin of the koi carp Cyprinus carpio was established and characterized. The KF ‐101 cell line multiplied abundantly in Leibovitz's L‐15 medium containing 10% foetal bovine serum at 25° C, and was subcultured for >90 passages over a period of 3 years. Immunocytochemistry revealed that the KF ‐101 cells contain keratin, junction proteins connexin‐43 and occludin, and ectodermal stem‐cell marker Pax‐6, but not vimentin. Furthermore, the KF ‐101 cells reacted with anti‐human DARPP ‐32 and anti‐human GATA ‐4 antibodies, and the labelling was regulated according to the cell cycle. The labels of the DARPP ‐32 and GATA ‐4 antibodies in the KF ‐101 cells were the suggested phosphatase‐1 inhibitor‐1 and GATA ‐3, respectively. In addition, the KF ‐101 cells were susceptible to koi herpesvirus but were resistant to eel herpesvirus, iridovirus, grouper nodavirus and chum salmon ( Oncorhynchus keta ) virus. The results indicate that the KF ‐101 cells are suitable materials for investigating biological and virological development.

Biotic resistance in marine environments - David L. Kimbro; Brian S. Cheng; Edwin D. Grosholz (Ecology Letters, 2013)
Biological invasions depend in part on the resistance of native communities. Meta‐analyses of terrestrial experiments demonstrate that native primary producers and herbivores generally resist invasions of primary producers, and that resistance through competition strengthens with native producer diversity. To test the generality of these findings, we conducted a meta‐analysis of marine experiments. We found that native marine producers generally failed to resist producer invasions through competition unless the native community was diverse, and this diversity effect was weaker in marine than in terrestrial systems. In contrast, native consumers equally resisted invasive producers in both ecosystems. Most marine experiments, however, tested invasive consumers and these invasions were resisted more strongly than were producer invasions. Given these differences between ecosystems and between marine trophic levels, we used a model‐selection approach to assess if factors other than the resistance mechanism (i.e. competition vs. consumption) are more important for predicting marine biotic resistance. These results suggest that understanding marine biotic resistance depends on latitude, habitat and invader taxon, in addition to distinguishing between competition with and consumption by native species. By examining biotic resistance within and across ecosystems, our work provides a more complete understanding of the factors that underlie biological invasions.

New species and distinctive geographical divergences of the genus Sparassis (Basidiomycota): evidence from morphological and molecular data - Qi Zhao; Bang Feng; Zhu L. Yang; Yu-Cheng Dai; Zheng Wang; B. Tolgor (Mycological Progress, 2013)

Levels, seasonal variations, and health risks assessment of ambient air pollutants in the residential areas - W. C. Zhao; J. P. Cheng; Z. Y. Yu; Q. L. Tang; F. Cheng; Y. W. Yin; W. H. Wang (International Journal of Environmental Science and Technology, 2013)

A physical map of the Chinese chestnut (Castanea mollissima) genome and its integration with the genetic map - Guang-Chen Fang; Barbara P. Blackmon; Margaret E. Staton; C. Dana Nelson; Thomas L. Kubisiak; Bode A. Olukolu; David Henry; Tatyana Zhebentyayeva; Christopher A. Saski; Chun-Huai Cheng; Megan Monsanto; Stephen Ficklin; et al. (Tree Genetics & Genomes, 2013)

Highly Stabilized Curcumin Nanoparticles Tested in an In Vitro Blood–Brain Barrier Model and in Alzheimer’s Disease Tg2576 Mice - Kwok Kin Cheng; Chin Fung Yeung; Shuk Wai Ho; Shing Fung Chow; Albert H. L. Chow; Larry Baum (The AAPS Journal, 2013)

Pyrrolizidine Alkaloid Composition Influences Cinnabar Moth Oviposition Preferences in Jacobaea Hybrids - Dandan Cheng; Eddy van der Meijden; Patrick P. J. Mulder; Klaas Vrieling; Peter G. L. Klinkhamer (Journal of Chemical Ecology, 2013)

Molecular mapping of Yr53, a new gene for stripe rust resistance in durum wheat accession PI 480148 and its transfer to common wheat - L. S. Xu; M. N. Wang; P. Cheng; Z. S. Kang; S. H. Hulbert; X. M. Chen (Theoretical and Applied Genetics, 2013)

Electrospun Formulations Containing Crystalline Active Pharmaceutical Ingredients - Blair Kathryn Brettmann; Kamyu Cheng; Allan S. Myerson; Bernhardt L. Trout (Pharmaceutical Research, 2013)

Role of Neurotrophins in the Development and Function of Neural Circuits That Regulate Energy Homeostasis - Samira Fargali; Masato Sadahiro; Cheng Jiang; Amy L. Frick; Tricia Indall; Valeria Cogliani; Jelle Welagen; Wei-Jye Lin; Stephen R. Salton (Journal of Molecular Neuroscience, 2012)

Semivolatile organic compounds removal and health risk reduction in drinking water treatment biofilters applying different backwashing strategies - Y. Chen; X. X. Zhang; B. Wu; B. Liu; L. Xiao; A. Li; S. Cheng (International Journal of Environmental Science and Technology, 2012)

Serum 25-hydroxyvitamin D, vitamin A, and lung cancer mortality in the US population: a potential nutrient–nutrient interaction - Ting-Yuan David Cheng; Marian L. Neuhouser (Cancer Causes & Control, 2012)

Plant-mediated decisions by an herbivore affect oviposition pattern and subsequent egg parasitism - Livy Williams; Yu Cheng Zhu; Gordon L. Snodgrass; Verónica Manrique (Arthropod-Plant Interactions, 2012)

Acute effects of plyometric jumping and intermittent running on serum bone markers in young males - Che-Fu Lin; Tsang-hai Huang; Kuo-Cheng Tu; Linda L. Lin; Yi-Hsuan Tu; Rong-Sen Yang (European Journal of Applied Physiology, 2012)

Molecular diversity of bacteria in Yunnan yellow cattle (Bos taurs) from Nujiang region, China - J. Leng; Y. M. Cheng; C. Y. Zhang; R. J. Zhu; S. L. Yang; X. Gou; W. D. Deng; H. M. Mao (Molecular Biology Reports, 2012)

A preliminary study on the molecular evolution of the two routes of intrauterine transmission of HBV - H. Sun; X. Tang; B. Wang; J. Zhang; H. Cheng; H. Su; F. Li; K. Men; S. Wang; L. Zhao; J. Xu; X. Yu; et al. (Archives of Virology, 2012)

Quantitative PK–PD Model-Based Translational Pharmacology of a Novel Kappa Opioid Receptor Antagonist Between Rats and Humans - Cheng Chang; Wonkyung Byon; Yifeng Lu; Leslie K. Jacobsen; Lori L. Badura; Aarti Sawant-Basak; Emily Miller; Jing Liu; Sarah Grimwood; Ellen Q. Wang; Tristan S. Maurer (The AAPS Journal, 2011)

GPS radio occultation measurements on ionospheric electron density from low Earth orbit - L.-C. Tsai; Kai-Chien Cheng; C. H. Liu (Journal of Geodesy, 2011)

The effect of the expression of virulence-associated DEAD-box RNA helicase mRNA on the imbalance of Th1-Th2 cytokines in the CSF of patients with Cryptococcus neoformans meningitis - L. Jiang; N. Lin; Z. Cheng; B. Yang; Q. Ou (European Journal of Clinical Microbiology & Infectious Diseases, 2011)

Stress-induced reinstatement of alcohol-seeking in rats is selectively suppressed by the neurokinin 1 (NK1) antagonist L822429 - Jesse R. Schank; Charles L. Pickens; Kelly E. Rowe; Kejun Cheng; Annika Thorsell; Kenner C. Rice; Yavin Shaham; Markus Heilig (Psychopharmacology, 2011)

Clostridium difficile isolates with increased sporulation: emergence of PCR ribotype 002 in Hong Kong - V. C. C. Cheng; W. C. Yam; O. T. C. Lam; J. L. Y. Tsang; E. Y. F. Tse; G. K. H. Siu; J. F. W. Chan; H. Tse; K. K. W. To; J. W. M. Tai; P. L. Ho; K. Y. Yuen (European Journal of Clinical Microbiology & Infectious Diseases, 2011)

Sensitivity analysis of climatic parameters for sky classification - D. H. W. Li; H. L. Tang; K. L. Cheung; E. W. M. Lee; C. C. K. Cheng (Theoretical and Applied Climatology, 2011)

The Relationship between Structurally Different Pyrrolizidine Alkaloids and Western Flower Thrips Resistance in F2 Hybrids of Jacobaea vulgaris and Jacobaea aquatica - Dandan Cheng; Heather Kirk; Klaas Vrieling; Patrick P. J. Mulder; Peter G. L. Klinkhamer (Journal of Chemical Ecology, 2011)

Evaluation of the Diurnal Cycle in the Atmospheric Boundary Layer Over Land as Represented by a Variety of Single-Column Models: The Second GABLS Experiment - G. Svensson; A. A. M. Holtslag; V. Kumar; T. Mauritsen; G. J. Steeneveld; W. M. Angevine; E. Bazile; A. Beljaars; E. I. F. de Bruijn; A. Cheng; L. Conangla; J. Cuxart; et al. (Boundary-Layer Meteorology, 2011)

Hemodynamic Changes Quantified in Abdominal Aortic Aneurysms with Increasing Exercise Intensity Using MR Exercise Imaging and Image-Based Computational Fluid Dynamics - Ga-Young Suh; Andrea S. Les; Adam S. Tenforde; Shawn C. Shadden; Ryan L. Spilker; Janice J. Yeung; Christopher P. Cheng; Robert J. Herfkens; Ronald L. Dalman; Charles A. Taylor (Annals of Biomedical Engineering, 2011)

EHPC 2010: sharing knowledge on environmental health for risk mitigation - T. E. Ford; A. L. Bass; S. Cheng; G. N. Cherr; B. Cole; E. Fairbairn; J.-D. Gu; R. S. Halbrook; F. E. Löffler; E. L. Madsen; N. A. McGinn (Ecotoxicology, 2011)

Advances in understanding the “Perfect Monsoon-influenced Typhoon”: Summary from International Conference on Typhoon Morakot (2009) - Cheng-Shang Lee; Chun-Chieh Wu; Tai-Chi Chen Wang; Russell L. Elsberry (Asia-Pacific Journal of Atmospheric Sciences, 2011)

Phase-resetting curve determines how BK currents affect neuronal firing - Cheng Ly; Tamar Melman; Alison L. Barth; G. Bard Ermentrout (Journal of Computational Neuroscience, 2011)

Loss of one Tgfbr2 allele in fibroblasts promotes metastasis in MMTV: polyoma middle T transgenic and transplant mouse models of mammary tumor progression - Wei Bin Fang; Iman Jokar; Anna Chytil; Harold L. Moses; Ty Abel; Nikki Cheng (Clinical & Experimental Metastasis, 2011)

Effect of dietary HUFA on tissue fatty acid composition and reproductive performance of Chinese mitten crab Eriocheir sinensis (H. Milne-Edwards) broodstock - L. Y. Sui; H. X. Sun; X. G. Wu; M. Wille; Y. X. Cheng; P. Sorgeloos (Aquaculture International, 2011)

The effect of hybridization on secondary metabolites and herbivore resistance: implications for the evolution of chemical diversity in plants - Dandan Cheng; Klaas Vrieling; Peter G. L. Klinkhamer (Phytochemistry Reviews, 2011)

Genomic sequence of an avian paramyxovirus type 1 strain isolated from Muscovy duck (Cairina moschata) in China - S.-H. Shi; Yu Huang; S.-J. Cui; L.-F. Cheng; G.-H. Fu; X. Li; Z. Chen; C.-X. Peng; F. Lin; J.-S. Lin; Jing-Liang Su (Archives of Virology, 2011)

Quantification of Particle Residence Time in Abdominal Aortic Aneurysms Using Magnetic Resonance Imaging and Computational Fluid Dynamics - Ga-Young Suh; Andrea S. Les; Adam S. Tenforde; Shawn C. Shadden; Ryan L. Spilker; Janice J. Yeung; Christopher P. Cheng; Robert J. Herfkens; Ronald L. Dalman; Charles A. Taylor (Annals of Biomedical Engineering, 2011)

Expression of GDF-9, BMP-15 and their receptors in mammalian ovary follicles - R. Z. Sun; L. Lei; L. Cheng; Z. F. Jin; S. J. Zu; Z. Y. Shan; Z. D. Wang; J. X. Zhang; Z. H. Liu (Journal of Molecular Histology, 2010)

A multi-modeling approach to evaluating climate and land use change impacts in a Great Lakes River Basin - M. J. Wiley; D. W. Hyndman; B. C. Pijanowski; A. D. Kendall; C. Riseng; E. S. Rutherford; S. T. Cheng; M. L. Carlson; J. A. Tyler; R. J. Stevenson; P. J. Steen; P. L. Richards; et al. (Hydrobiologia, 2010)

Oriented Markov Random Field Based Dendritic Spine Segmentation for Fluorescence Microscopy Images - Jie Cheng; Xiaobo Zhou; Eric L. Miller; Veronica A. Alvarez; Bernardo L. Sabatini; Stephen T. C. Wong (Neuroinformatics, 2010)

A Model of Slow Wave Propagation and Entrainment Along the Stomach - Martin L. Buist; Alberto Corrias; Yong Cheng Poh (Annals of Biomedical Engineering, 2010)

Hydrogen sulfide protects soybean seedlings against drought-induced oxidative stress - Hua Zhang; Hao Jiao; Cheng-Xi Jiang; Song-Hua Wang; Zhao-Jun Wei; Jian-Ping Luo; Russell L. Jones (Acta Physiologiae Plantarum, 2010)

Cellular Expression of INK4a Gene in Cells of Bladder Cancer Associated with Human Papilloma Virus-16 - G. M. Volgareva; L. E. Zavalishina; D. A. Golovina; Yu. Yu. Andreeva; V. D. Ermilova; O. B. Trofimova; D. A. Kuevda; O. Yu. Shipulina; V. A. Glazunova; Shuling Cheng; L. S. Pavlova; N. L. Cheban; et al. (Bulletin of Experimental Biology and Medicine, 2010)

The influence of muscle length on the fatigue-related reduction in joint range of motion of the human dorsiflexors - Arthur J. Cheng; Andrew W. Davidson; Charles L. Rice (European Journal of Applied Physiology, 2010)

Probing Cell Structure Responses Through a Shear and Stretching Mechanical Stimulation Technique - Robert L. Steward; Chao-Min Cheng; Danny L. Wang; Philip R. LeDuc (Cell Biochemistry and Biophysics, 2010)

Falling-Edge, Variable Threshold (FEVT) Method for the Automated Detection of Gastric Slow Wave Events in High-Resolution Serosal Electrode Recordings - Jonathan C. Erickson; Gregory O’Grady; Peng Du; Chibuike Obioha; Wenlian Qiao; William O. Richards; L. Alan Bradshaw; Andrew J. Pullan; Leo K. Cheng (Annals of Biomedical Engineering, 2010)

Atmospheric CO 2 enrichment facilitates cation release from soil - L. Cheng; J. Zhu; G. Chen; X. Zheng; N.‐H. Oh; T. W. Rufty; D. deB. Richter; S. Hu (Ecology Letters, 2010)
Ecology Letters (2010) 13: 284–291 Abstract Atmospheric CO 2 enrichment generally stimulates plant photosynthesis and nutrient uptake, modifying the local and global cycling of bioactive elements. Although nutrient cations affect the long‐term productivity and carbon balance of terrestrial ecosystems, little is known about the effect of CO 2 enrichment on cation availability in soil. In this study, we present evidence for a novel mechanism of CO 2 ‐enhancement of cation release from soil in rice agricultural systems. Elevated CO 2 increased organic C allocation belowground and net H + excretion from roots, and stimulated root and microbial respiration, reducing soil redox potential and increasing Fe 2+ and Mn 2+ in soil solutions. Increased H + , Fe 2+ , and Mn 2+ promoted Ca 2+ and Mg 2+ release from soil cation exchange sites. These results indicate that over the short term, elevated CO 2 may stimulate cation release from soil and enhance plant growth. Over the long‐term, however, CO 2 ‐induced cation release may facilitate cation losses and soil acidification, negatively feeding back to the productivity of terrestrial ecosystems.

Rejecting strictly allopatric speciation on a continental island: prolonged postdivergence gene flow between Taiwan ( Leucodioptron taewanus , Passeriformes Timaliidae) and Chinese ( L. canorum canorum ) hwameis - JING-WEN LI; CAROL K. L. YEUNG; PI-WEN TSAI; RONG-CHIEN LIN; CHIA-FEN YEH; CHENG-TE YAO; LIANXIAN HAN; LE MANH HUNG; PING DING; QISHAN WANG; SHOU-HSIEN LI (Molecular Ecology, 2010)

Establishment, characterization, virus susceptibility and transfection of cell lines from cobia, Rachycentron canadum (L.), brain and fin - T‐C Cheng; Y‐S Lai; I‐Y Lin; C‐P Wu; S‐L Chang; T‐I Chen; M‐S Su (Journal of Fish Diseases, 2010)
Establishment and characterization of two cobia, Rachycentron canadum, cell lines derived from cobia brain (CB) and cobia fin (CF) are described. Caudal fin and brain from juvenile cobia were dissociated for 30 and 10 min, respectively, in phosphate‐buffered saline containing 0.25% trypsin at 25 °C. The optimal culture condition for both dissociated cells (primary cell culture) was at 28 °C in Leibovitz‐15 medium containing 10% foetal bovine serum. The cells have been sub‐cultured at a ratio of 1:2 for more than 160 passages over a period of 3 years. Origin of the cultured cells was verified by comparison of their sequences of mitochondrial cytochrome oxidase subunit I genes ( cox I ) with the cox 1 sequence from cobia muscle tissue. The cell lines showed polyploidy. No mycoplasma contamination was detected. Susceptibility to grouper iridovirus was observed for the CB cell line but not the CF cell line. Both cell lines expressed green fluorescent protein after being transfected with green fluorescent reporter gene driven by the cytomegalovirus promoter.

Direct somatic embryogenesis from pericycle cells of broccoli (Brassica oleracea L. var. italica) root explants - J. L. Yang; E. S. Seong; M. J. Kim; B. K. Ghimire; W. H. Kang; Chang Yeon Yu; Cheng Hao Li (Plant Cell, Tissue and Organ Culture (PCTOC), 2010)

Phylogenetic analysis of 16S rRNA gene sequences reveals rumen bacterial diversity in Yaks (Bos grunniens) - L. Y. Yang; J. Chen; X. L. Cheng; D. M. Xi; S. L. Yang; W. D. Deng; H. M. Mao (Molecular Biology Reports, 2010)

Characterization of Gastric Electrical Activity Using Magnetic Field Measurements: A Simulation Study - J. H. K. Kim; L. A. Bradshaw; A. J. Pullan; L. K. Cheng (Annals of Biomedical Engineering, 2010)

Phenotypic divergence during the invasion of Phyla canescens in Australia and France: evidence for selection‐driven evolution - Cheng‐Yuan Xu; Mic H. Julien; Mohammad Fatemi; Christophe Girod; Rieks D. Van Klinken; Caroline L. Gross; Stephen J. Novak (Ecology Letters, 2010)
Rapid adaptive evolution has been advocated as a mechanism that promotes invasion. Demonstrating adaptive evolution in invasive species requires rigorous analysis of phenotypic shifts driven by selection. Here, we document selection‐driven evolution of Phyla canescens , an Argentine weed, in two invaded regions (Australia and France). Invasive populations possessed similar or higher diversity than native populations, and displayed mixed lineages from different sources, suggesting that genetic bottlenecks in both countries might have been alleviated by multiple introductions. Compared to native populations, Australian populations displayed more investment in sexual reproduction, whereas French populations possessed enhanced vegetative reproduction and growth. We partitioned evolutionary forces (selection vs. stochastic events) using two independent methods. Results of both analyses suggest that the pattern of molecular and phenotypic variability among regions was consistent with selection‐driven evolution, rather than stochastic events. Our findings indicate that selection has shaped the evolution of P . canescens in two different invaded regions. Ecology Letters (2010) 13: 32–44

Antimicrobial stewardship program directed at broad-spectrum intravenous antibiotics prescription in a tertiary hospital - V. C. C. Cheng; K. K. W. To; I. W. S. Li; B. S. F. Tang; J. F. W. Chan; S. Kwan; R. Mak; J. Tai; P. Ching; P. L. Ho; W. H. Seto (European Journal of Clinical Microbiology & Infectious Diseases, 2009)

Multiple alphaII-spectrin breakdown products distinguish calpain and caspase dominated necrotic and apoptotic cell death pathways - Zhiqun Zhang; Stephen F. Larner; Ming Cheng Liu; Wenrong Zheng; Ronald L. Hayes; Kevin K. W. Wang (Apoptosis, 2009)

Effects of grape xylem sap and cell wall constituents on in vitro growth, biofilm formation and cellular aggregation of Xylella fastidiosa - Davis W. Cheng; Hong Lin; M. Andrew Walker; Drake C. Stenger; Edwin L. Civerolo (European Journal of Plant Pathology, 2009)

Comparative responses in rare minnow exposed to 17β-estradiol during different life stages - T. Liao; Q. L. Guo; S. W. Jin; W. Cheng; Y. Xu (Fish Physiology and Biochemistry, 2009)

Isolation and characterization of 23 microsatellite loci in the black-faced spoonbill (Platalea minor) and amplification in other Ciconiiformes waterbirds - Carol K. L. Yeung; Yu-Cheng Hsu; Cheng-Te Yao; Shou-Hsien Li (Conservation Genetics, 2009)

First Molecular Detection of Group A Rotaviruses in Drinking Water Sources in Beijing, China - X. Q. He; L. Cheng; D. Y. Zhang; W. Li; X. M. Xie; M. Ma; Z. J. Wang (Bulletin of Environmental Contamination and Toxicology, 2009)

High-resolution Mapping of In Vivo Gastrointestinal Slow Wave Activity Using Flexible Printed Circuit Board Electrodes: Methodology and Validation - Peng Du; G. O’Grady; J. U. Egbuji; W. J. Lammers; D. Budgett; P. Nielsen; J. A. Windsor; A. J. Pullan; L. K. Cheng (Annals of Biomedical Engineering, 2009)

Effect of dietary soybean lecithin on reproductive performance of Chinese mitten crab Eriocheir sinensis (H. Milne-Edwards) Broodstock - L. Y. Sui; X. G. Wu; M. Wille; Y. X. Cheng; P. Sorgeloos (Aquaculture International, 2009)

Polychlorinated Biphenyls Residues in the Soil in Linfen, China - S. Fu; H. Cheng; Y. Liu; L. Zhang; Z. Yang; K. Li; X. Xia; X. Xu (Bulletin of Environmental Contamination and Toxicology, 2008)

Genetic analysis of photoperiod sensitivity in a tropical by temperate maize recombinant inbred population using molecular markers - C. L. Wang; F. F. Cheng; Z. H. Sun; J. H. Tang; L. C. Wu; L. X. Ku; Y. H. Chen (Theoretical and Applied Genetics, 2008)

Antioxidative activities and the total phenolic contents of tonic Chinese Medicinal Herbs - D.-J. Guo; H.-L. Cheng; S.-W. Chan; P. H.-F. Yu (Inflammopharmacology, 2008)

Ly49h is necessary for genetic resistance to murine cytomegalovirus - Tammy P. Cheng; Anthony R. French; Beatrice F. M. Plougastel; Jeanette T. Pingel; Michael M. Orihuela; Mark L. Buller; Wayne M. Yokoyama (Immunogenetics, 2008)

Loss of apical monocilia on collecting duct principal cells impairs ATP secretion across the apical cell surface and ATP-dependent and flow-induced calcium signals - Michael B. Hovater; Dragos Olteanu; Elizabeth L. Hanson; Nai-Lin Cheng; Brian Siroky; Attila Fintha; Peter Komlosi; Wen Liu; Lisa M. Satlin; P. Darwin Bell; Bradley K. Yoder; Erik M. Schwiebert (Purinergic Signalling, 2008)

Inhibitory effect of triptolide on interleukin-18 and its receptor in rheumatoid arthritis synovial fibroblasts - Y. Lu; W.-J. Wang; J.-H. Leng; L.-F. Cheng; L. Feng; H.-P. Yao (Inflammation Research, 2008)

Screening of a high fibrinolytic enzyme producing strain and characterization of the fibrinolytic enzyme produced from Bacillus subtilis LD-8547 - Shi H. Wang; Cheng Zhang; Yan L. Yang; Miao Diao; Ming F. Bai (World Journal of Microbiology and Biotechnology, 2008)

Transcriptional analysis of a major capsid protein gene from Spodoptera exigua ascovirus 5a - T. Z. Salem; C. M. Turney; L. Wang; J. Xue; X.-F. Wan; X.-W. Cheng (Archives of Virology, 2008)

Leaf phenology and seasonal variation of photosynthesis of invasive Berberis thunbergii (Japanese barberry) and two co-occurring native understory shrubs in a northeastern United States deciduous forest - Cheng-Yuan Xu; Kevin L. Griffin; W. S. F. Schuster (Oecologia, 2007)

Climate simulations for 1880–2003 with GISS modelE - J. Hansen; M. Sato; R. Ruedy; P. Kharecha; A. Lacis; R. Miller; L. Nazarenko; K. Lo; G. A. Schmidt; G. Russell; I. Aleinov; S. Bauer; et al. (Climate Dynamics, 2007)

Efficacy and safety of atomoxetine for attention-deficit/hyperactivity disorder in children and adolescents—meta-analysis and meta-regression analysis - Jackie Y. W. Cheng; Ronald Y. L. Chen; John S. N. Ko; Emil M. L. Ng (Psychopharmacology, 2007)

Seasonal variation of temperature response of respiration in invasive Berberis thunbergii (Japanese barberry) and two co-occurring native understory shrubs in a northeastern US deciduous forest - Cheng-Yuan Xu; W. S. F. Schuster; Kevin L. Griffin (Oecologia, 2007)

Investigation of rice transgene flow in compass sectors by using male sterile line as a pollen detector - Q. H. Yuan; L. Shi; F. Wang; B. Cao; Q. Qian; X. M. Lei; Y. L. Liao; W. G. Liu; L. Cheng; S. R. Jia (Theoretical and Applied Genetics, 2007)

Distribution of convection associated with tropical cyclones making landfall along the South China coast - K. S. Liu; J. C. L. Chan; W. C. Cheng; S. L. Tai; P. W. Wong (Meteorology and Atmospheric Physics, 2007)

Antiviral activity of arbidol against influenza A virus, respiratory syncytial virus, rhinovirus, coxsackie virus and adenovirus in vitro and in vivo - L. Shi; H. Xiong; J. He; H. Deng; Q. Li; Q. Zhong; W. Hou; L. Cheng; H. Xiao; Z. Yang (Archives of Virology, 2007)

Habit formation and the loss of control of an internal clock: inverse relationship between the level of baseline training and the clock-speed enhancing effects of methamphetamine - Ruey-Kuang Cheng; Oshri L. Hakak; Warren H. Meck (Psychopharmacology, 2007)

Comparative genomics reveals functional transcriptional control sequences in the Prop1 gene - Robert D. Ward; Shannon W. Davis; MinChul Cho; Constance Esposito; Robert H. Lyons; Jan-Fang Cheng; Edward M. Rubin; Simon J. Rhodes; Lori T. Raetzman; Timothy P. L. Smith; Sally A. Camper (Mammalian Genome, 2007)

Urinary levels of RANTES and M-CSF are predictors of lupus nephritis flare - S. Tian; J. Li; L. Wang; T. Liu; H. Liu; G. Cheng; D. Liu; Y. Deng; R. Gou; Y. Wan; J. Jia; C. Chen (Inflammation Research, 2007)

Application of LIDAR Technique and MM5-CMAQ Modeling Approach for the Assessment of Winter PM10 Air Pollution: A Case Study in Beijing, China - D. S. Chen; S. Y. Cheng; J. B. Li; T. Chen; X. Y. Zhao; X. R. Guo; H. L. Hu; T. Yu (Water, Air, & Soil Pollution, 2007)

Electro-mechanical stability of surface EMG sensors - S. H. Roy; G. De Luca; M. S. Cheng; A. Johansson; L. D. Gilmore; C. J. De Luca (Medical & Biological Engineering & Computing, 2007)

Fine mapping of the Pc locus of Sorghum bicolor, a gene controlling the reaction to a fungal pathogen and its host-selective toxin - Ervin D. Nagy; Tso-Ching Lee; Wusirika Ramakrishna; Zijun Xu; Patricia E. Klein; Phillip SanMiguel; Chiu-Ping Cheng; Jingling Li; Katrien M. Devos; Keith Schertz; Larry Dunkle; Jeffrey L. Bennetzen (Theoretical and Applied Genetics, 2007)

The two giant sister species of the Southern Ocean, Dissostichus eleginoides and Dissostichus mawsoni, differ in karyotype and chromosomal pattern of ribosomal RNA genes - L. Ghigliotti; F. Mazzei; C. Ozouf-Costaz; C. Bonillo; R. Williams; C.-H. C. Cheng; E. Pisano (Polar Biology, 2007)

Developmental regulation of SSeCKS expression in rat brain - L. Chen; J. Qin; C. Cheng; H. Liu; J. Qian; L. Sun; F. Xiao; S. Shi; S. Niu; A. Shen (Journal of Molecular Neuroscience, 2007)

Src suppressed C kinase substrate regulates the lipopolysaccharide-induced TNF-α biosynthesis in rat astrocytes - L. -l. Sun; C. Cheng; H. -o. Liu; C. -c. Shen; F. Xiao; J. Qin; J. -l. Yang; A. -g. Shen (Journal of Molecular Neuroscience, 2007)

Influence of DOC on MS-2 Bacteriophage Transport in a Sandy Soil - Li Cheng; Alexandra S. Chetochine; Ian L. Pepper; Mark L. Brusseau (Water, Air, & Soil Pollution, 2007)

Two new chemical constituents from Daphne odora Thunb. var. marginata - W. Zhang; W. D. Zhang; R. H. Liu; Y. H. Shen; C. Zhang; H. S. Cheng; P. Fu; L. Shan (Natural Product Research, 2006)

Analysis of candidate genes on chromosome 2 in oral cleft case-parent trios from three populations - T. H. Beaty; J. B. Hetmanski; M. D. Fallin; J. W. Park; J. W. Sull; I. McIntosh; K. Y. Liang; C. A. VanderKolk; R. J. Redett; S. A. Boyadjiev; E. W. Jabs; S. S. Chong; et al. (Human Genetics, 2006)

Novel aminoglycosides increase SMN levels in spinal muscular atrophy fibroblasts - Virginia B. Mattis; Ravi Rai; Jinhua Wang; Cheng-Wei T. Chang; Tristan Coady; Christian L. Lorson (Human Genetics, 2006)

Activation of mitogen-activated protein kinases is essential for hydrogen peroxide -induced apoptosis in retinal pigment epithelial cells - T.-C. Ho; Y.-C. Yang; H.-C. Cheng; A.-C. Wu; S.-L. Chen; H.-K. Chen; Y.-P. Tsao (Apoptosis, 2006)

Comparative analysis of whole saliva proteomes for the screening of biomarkers for oral lichen planus - L. -L. Yang; X. -Q. Liu; W. Liu; B. Cheng; M. -T. Li (Inflammation Research, 2006)

Phthalate Ester Pollution in Urban Soil of Beijing, People's Republic of China - X. H. Li; L. L. Ma; X. F. Liu; S. Fu; H. X. Cheng; X. B. Xu (Bulletin of Environmental Contamination and Toxicology, 2006)

Computational Simulations of the Human Magneto- and Electroenterogram - A. S. Lin; M. L. Buist; L. K. Cheng; N. P. Smith; A. J. Pullan (Annals of Biomedical Engineering, 2006)

Variations in Indoor PM10 Concentrations in Sixteen Homes in Guiyang City, People's Republic of China - Y. L. Cheng; M. Yan; J. L. Li; Z. R. Liu; Y. H. Bai; W. Tian; D. G. Wu; Q. Cheng (Bulletin of Environmental Contamination and Toxicology, 2006)

Estimating the underwater light field from remote sensing of ocean color - Cheng-Chien Liu; Richard L. Miller; Kendall L. Carder; Zhongping Lee; Eurico J. D’Sa; James E. Ivey (Journal of Oceanography, 2006)

QTL analysis for rice grain length and fine mapping of an identified QTL with stable and major effects - X. Y. Wan; J. M. Wan; L. Jiang; J. K. Wang; H. Q. Zhai; J. F. Weng; H. L. Wang; C. L. Lei; J. L. Wang; X. Zhang; Z. J. Cheng; X. P. Guo (Theoretical and Applied Genetics, 2006)

Metabolic energy utilization during development of Antarctic naked dragonfish (Gymnodraco acuticeps) - Clive W. Evans; Leonard Pace; Paul A. Cziko; Adam G. Marsh; Chi-Hing Christina Cheng; Arthur L. DeVries (Polar Biology, 2006)

Beta-propeller phytases in the aquatic environment - Chiwai Cheng; Boon L. Lim (Archives of Microbiology, 2006)

Single-Column Model Intercomparison for a Stably Stratified Atmospheric Boundary Layer - J. Cuxart; A. A. M. Holtslag; R. J. Beare; E. Bazile; A. Beljaars; A. Cheng; L. Conangla; M. Ek; F. Freedman; R. Hamdi; A. Kerstein; H. Kitagawa; et al. (Boundary-Layer Meteorology, 2006)

Solubility and Stability of Calcium Arsenates at 25∘C - Y. N. Zhu; X. H. Zhang; Q. L. Xie; D. Q. Wang; G. W. Cheng (Water, Air, & Soil Pollution, 2006)

MULTIPLE INITIAL CULTURE CONDITIONS ENHANCE THE ESTABLISHMENT OF CELL LINES FROM PRIMARY OVARIAN CANCER SPECIMENS - CARA C. BERTOZZI; CHENG-YI CHANG; SONYA JAIRAJ; XIAOCHUAN SHAN; JIA HUANG; BARBARA L. WEBER; CHRISTINA S. CHU; RICHARD G. CARROLL (In Vitro Cellular & Developmental Biology - Animal, 2006)

Multiple Initial Culture Conditions Enhance the Establishment of Cell Lines from Primary Ovarian Cancer Specimens - Cara C. Bertozzi; Cheng-Yi Chang; Sonya Jairaj; Xiaochuan Shan; Jia Huang; Babara L. Weber; Christina S. Chu; Richard G. Carroll (In Vitro Cellular & Developmental Biology - Animal, 2006)

A catalog of nonsynonymous polymorphism on mouse Chromosome 16 - Jeffrey M. Kidd; Karrie C. Trevarthen; David L. Tefft; Ze Cheng; Michaele Mooney; Mark D. Adams (Mammalian Genome, 2005)

Endonuclease-like activity of heme proteins - Willy B. Tan; Wunhuey Cheng; Andrew Webber; Akhilesh Bhambhani; Michael R. Duff; Challa V. Kumar; George L. McLendon (JBIC Journal of Biological Inorganic Chemistry, 2005)

Rapid construction of a patient-specific torso model from 3D ultrasound for non-invasive imaging of cardiac electrophysiology - L. K. Cheng; G. B. Sands; R. L. French; S. J. Withy; S. P. Wong; M. E. Legget; W. M. Smith; A. J. Pullan (Medical & Biological Engineering & Computing, 2005)

The relationship between HPV16 and expression of CD44v6, nm23H1 in esophageal squamous cell carcinoma - W.-K. Liu; Y.-L. Chu; F. Zhang; P. Chen; F. Cheng; H. Wang; Y.-Y. Jia; T.-Y. Ma (Archives of Virology, 2005)

Use of convalescent plasma therapy in SARS patients in Hong Kong - Y. Cheng; R. Wong; Y. O. Y. Soo; W. S. Wong; C. K. Lee; M. H. L. Ng; P. Chan; K. C. Wong; C. B. Leung; G. Cheng (European Journal of Clinical Microbiology & Infectious Diseases, 2005)

Functional and regulatory analysis of the Arabidopsis thaliana CAX2 cation transporter - Jon K. Pittman; Toshiro Shigaki; Joy L. Marshall; Jay L. Morris; Ning-Hui Cheng; Kendal D. Hirschi (Plant Molecular Biology, 2004)

Novel β-carotene ketolases from non-photosynthetic bacteria for canthaxanthin synthesis - L. Tao; Q. Cheng (Molecular Genetics and Genomics, 2004)

Quaternary ecological and geomorphic changes associated with rainfall events in presently semi‐arid northeastern Brazil - Augusto S. Auler; Xianfeng Wang; R. Lawrence Edwards; Hai Cheng; Patrícia S. Cristalli; Peter L. Smart; David A. Richards (Journal of Quaternary Science, 2004)
Several geomorphic features and palaeobiotic remains in now semi‐arid northeastern Brazil indicate major palaeoenvironmental changes during past periods of increased rainfall. 230 Th mass spectrometric ages of speleothems and travertines have allowed the determination of the timing and duration of wetter than present conditions. The data demonstrate that wet events have occurred throughout much of the Pleistocene, present dry conditions having been established at the end of the Younger Dryas. A markedly different fauna comprising megafaunal elements not adapted to the present low arboreal scrubland caatinga vegetation existed in the area. Palaeobotanical remains embedded in travertine indicate forested vegetation at these wetter intervals, suggesting that the caatinga was then replaced or mixed with a semi‐deciduous forest. Due to the abundance of travertine sites containing fossil botanical remains in northeastern Brazil, it is believed that forest expansion occurred over large areas of the now semi‐arid zone, showing that the long hypothesised forested links between biodiversity‐rich Amazon and Atlantic rainforests may indeed have existed during these moister phases. Copyright © 2004 John Wiley & Sons, Ltd.

Increased Production and Excretion of Urea in the Kuruma Shrimp (Marsupenaeus japonicus) Exposed to Combined Environments of Increased Ammonia and Nitrite - S.-Y. Cheng; W. C. Lee; L. W. Shieh; J.-C. Chen (Archives of Environmental Contamination and Toxicology, 2004)

An Integrated Feasibility Study on Designing Remediation Systems for Petroleum-Contaminated Sites - L. Liu; R.X. Hao; S.Y. Cheng; H.C. Guo (Water, Air, & Soil Pollution, 2004)

Lymphocyte surge as a marker for immunorestitution disease due to Pneumocystis jiroveci pneumonia in HIV-negative immunosuppressed hosts - V. C. C. Cheng; I. F. N. Hung; A. K. L. Wu; B. S. F. Tang; C. M. Chu; K. Y. Yuen (European Journal of Clinical Microbiology & Infectious Diseases, 2004)

Effect of organophosphorus hydrolysing enzymes on obidoxime-induced reactivation of organophosphate-inhibited human acetylcholinesterase - S. Herkenhoff; L. Szinicz; V. K. Rastogi; T.-C. Cheng; J. J. DeFrank; F. Worek (Archives of Toxicology, 2004)

Asymmetrically acting lycopene β-cyclases (CrtLm) from non-photosynthetic bacteria - L. Tao; S. Picataggio; P. E. Rouvière; Q. Cheng (Molecular Genetics and Genomics, 2004)

Effects of Pesticides and Their Hydrolysates on Catalase Activity in Soil - L. Shiyin; N. Lixiao; P. Panying; S. Cheng; W. Liansheng (Bulletin of Environmental Contamination and Toxicology, 2004)

Effects of Four Metals on the Degradation of Purified Terephthalic Acid Wastewater by Phanerochaete chrysosporium and Strain Fhhh - J. Yan; S. P. Cheng; X. X. Zhang; L. Shi; C. J. Zhu (Bulletin of Environmental Contamination and Toxicology, 2004)

Factors influencing Agrobacterium-mediated transformation of monocotyledonous species - Ming Cheng; Brenda A. Lowe; T. Michael Spencer; Xudong Ye; Charles L. Armstrong (In Vitro Cellular & Developmental Biology - Plant, 2004)

Augmented responses to morphine and cocaine in mice with a 12-lipoxygenase gene disruption - Carrie L. Walters; Bao-Cheng Wang; Misty Godfrey; Duxin Sun; Colin D. Funk; Julie A. Blendy (Psychopharmacology, 2003)

Effect of Addition of Sodium Hydroxide and Calcium Nitrate on Polycyclic Aromatic Hydrocarbon Emission from Benzene Incineration - S. Y. Cheng; Y. L. Wei; C. J. Wu (Bulletin of Environmental Contamination and Toxicology, 2003)

Peripartum Tuberculosis as a Form of Immunorestitution Disease - V. C. C. Cheng; P. C. Y. Woo; S. K. P. Lau; C. H. Y. Cheung; R. W. H. Yung; L. Y. C. Yam; K. Y. Yuen (European Journal of Clinical Microbiology & Infectious Diseases, 2003)

Patterns of variation in flowering and seed set of meadowfoam - Canhong Cheng; Ian L. Gordon (Euphytica, 2003)

Use of Chitosan Membrane from the Carapace of the Soldier Crab Mictyris brevidactylus for Biosensor Construction - Bo-Chuan Hsieh; Tzong-Jih Cheng; Tzu-Yu Wang; Richie L. C. Chen (Marine Biotechnology, 2003)

Characterization and Temporal Variation of Asian Dust Aerosol from a Site in the Northern Chinese Deserts - X. Y. Zhang; S. L. Gong; R. Arimoto; Z. X. Shen; F. M. Mei; D. Wang; Y. Cheng (Journal of Atmospheric Chemistry, 2003)

Inhibitor of apoptosis proteins and ovarian dysfunction in galactosemic rats - K. W. Lai; L. Y. L. Cheng; A. L. M. Cheung; W. S. O (Cell and Tissue Research, 2003)

Hibiscus protocatechuic acid inhibits lipopolysaccharide-induced rat hepatic damage - Lin W.-L.; Hsieh Y.-J.; Chou F.-P.; Wang C.-J.; Cheng M.-T.; Tseng T.-H. (Archives of Toxicology, 2003)

Illumination and turbidity effects on observing faceted bottom elements with uniform Lambertian albedos - Kendall L. Carder,; Cheng-Chien Liu,; Zhongping Lee,; David C. English,; James Patten,; F. Robert Chen,; James E. Ivey; Davis Curtiss O. (Limnology and Oceanography, 2003)
Aircraft images were collected near Lee Stocking Island (LSI), Bahamas, with wavelike features for bright sand bottoms during times when solar zenith angles were large. The image contrast between leading and trailing wave facets approached a 10–15% difference because of algae accumulations in wave troughs or topographic variations of the bottom. Reflectance contrast for blue light was greater than for red and green wavelengths when algae or detritus was present in the troughs. However, the contrast at green and red wavelengths was greater than at blue wavelengths when caused by the interplay between bottom topography and oblique illumination. A three‐dimensional backwards Monte Carlo (BMC) model was developed to evaluate the effect of oblique illumination on wavelike topographic features for various values of water clarity and bottom albedo. An inverse optical modeling approach, previously developed for flat, horizontally homogeneous bottoms, was applied to the BMC results. Bathymetric estimates for bright facets tilted 10° toward the sun were slightly smaller than actual depths, whereas shaded facet depth estimates were too high by about 5%. Larger errors were associated with albedo retrievals, where shaded facets produced albedo estimates up to 15% lower than actual values. Errors increased with tilt angles up to 20° but decreased with sea and sky turbidity. Averaging sunlit and shaded pixels before running the inverse model reduced the uncertainty of bathymetric and albedo estimates to about 2 and 5%, respectively, comparable to previous field evaluations of the inversion model.

Lactococcus garvieae , a cause of disease in grey mullet, Mugil cephalus L., in Taiwan - S‐C Chen; L‐L Liaw; H‐Y Su; S‐C Ko; C‐Y Wu; H‐C Chaung; Y‐H Tsai; K‐L Yang; Y‐C Chen; T‐H Chen; G‐R Lin; S‐Y Cheng; et al. (Journal of Fish Diseases, 2002)

Influences of structures on urban ventilation: A numerical experiment - Liu Huizhi; Sang Jianguo; Zhang Boyin; Johnny C. L. Chan; Andrew Y. S. Cheng; Liu Heping (Advances in Atmospheric Sciences, 2002)

Genetic variation and population differentiation of Michelia formosana (Magnoliaceae) based on cpDNA variation and RAPD fingerprints: relevance to post-Pleistocene recolonization - S.-Y. Lu; K.-H. Hong; S.-L. Liu; Y.-P. Cheng; W.-L. Wu; T.-Y. Chiang (Journal of Plant Research, 2002)

RFLP-facilitated investigation of the quantitative resistance of rice to brown planthopper (Nilaparvata lugens) - X. F. Xu; H. W. Mei; L. J. Luo; X. N. Cheng; Z. K. Li (Theoretical and Applied Genetics, 2002)

Expression of afibrobacter succinogenes 1,3-1,4-β-glucanase in Potato (Solanum tuberosum) - John D. Armstrong; G. Douglas Inglis; Lawrence M. Kawchuk; Tim A. McAllister; Fran Leggett; Dermot R. Lynch; L. Brent Selinger; K. J. Cheng (American Journal of Potato Research, 2002)

Development of the Fragment Constant Method for Estimating the Partition Coefficients of Nonionic Organic Mixtures - Z. Lin, H. Yu, S. Gao, J. Cheng, L. Wa (Archives of Environmental Contamination and Toxicology, 2001)

Noninvasive Electrical Imaging of the Heart: Theory and Model Development - A. J. Pullan; L. K. Cheng; M. P. Nash; C. P. Bradley; D. J. Paterson (Annals of Biomedical Engineering, 2001)

Establishment of a gene transfer system for Pseudozyma flocculosa, an antagonistic fungus of powdery mildew fungi - Y. Cheng; F. Belzile; P. Tanguay; L. Bernier; R. Bélanger (Molecular Genetics and Genomics, 2001)

Synoptic patterns in relation to ozone concentrations in west-central Taiwan - W.-L. Cheng; J.-L. Pai; B.-J. Tsuang; C.-L. Chen (Meteorology and Atmospheric Physics, 2001)

Corrosion Properties of Nanocrystalline Co–Cr Coatings - D. Cheng; V. L. Tellkamp; C. J. Lavernia; E. J. Lavernia (Annals of Biomedical Engineering, 2001)

Effects of Azinphos-Methyl on American Robins Breeding in Fruit Orchards - H. Gill, L. K. Wilson, K. M. Cheng, S. (Bulletin of Environmental Contamination and Toxicology, 2000)

Effects of Azinphos-Methyl on American Robins Breeding in Fruit Orchards - H. Gill; L. K. Wilson; K. M. Cheng; S. Trudeau; J. E. Elliott (Bulletin of Environmental Contamination and Toxicology, 2000)

Modulation of insulin signaling by protein tyrosine phosphatases - Mounib Elchebly; Alan Cheng; Michel L. Tremblay (Journal of Molecular Medicine, 2000)

Chromosome assignments of the rice field eel Sox9 and Sox17 genes - X. Huang; R. Zhou; L. Liu; H. Cheng; Y. Guo; Q. Yu (Aquaculture International, 2000)

B chromosome in a rice aneuploid variation - Z. K. Cheng; H. X. Yu; H. H. Yan; M. H. Gu; L. H. Zhu (Theoretical and Applied Genetics, 2000)

Cellulitis Complicating Lymphoedema - P. C. Y. Woo; P. N. L. Lum; S. S. Y. Wong; V. C. C. Cheng; K. Y. Yuen (European Journal of Clinical Microbiology & Infectious Diseases, 2000)

Mitochondrial DNA sequence variation and phylogeography of oceanic insects (Hemiptera: Gerridae: Halobates spp.) - N. M. Andersen; L. Cheng; J. Damgaard; F. A. H. Sperling (Marine Biology, 2000)

Field evaluation of a passive sampler for the exposure assessment of 2-methoxyethanol - T.-S. Shih; C.-Y. Chen; R.-I. Cheng; L.-J. Wu (International Archives of Occupational and Environmental Health, 2000)

Abstracts of presentations on selected topics at the XIVth international plant protection congress (IPPC) July 25–30, 1999 - R. Hull; H. A. Kuiper; Maryvon Y. Noordam; Marjorie A. Hoy; Jenny S. Cory; A. C. Fereres; P. Gonzalez; F. Meins; Y. Elkind; Benedicte Charrier; P. Meyer; M. Metzlaff; et al. (Phytoparasitica, 1999)

A three-dimensional definition for the flexion/extension and abduction/adduction angles - P. L. Cheng; M. Pearcy (Medical & Biological Engineering & Computing, 1999)

Meal Composition Effects on the Oral Bioavailability of Indinavir in HIV-Infected Patients - Peggy L. Carver; David Fleisher; Simon Y. Zhou; Daniel Kaul; Powel Kazanjian; Cheng Li (Pharmaceutical Research, 1999)

Immunolocalization of the petunia floral binding proteins 7 and 11 during seed development in wild-type and expression mutants ofPetunia hybrida - P. E. Wittich; R. F. de Heer; X. -F. Cheng; H. Kieft; L. Colombo; G. C. Angenent; A. A. M. van Lammeren (Protoplasma, 1999)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Overexpression of Human Intestinal Oligopeptide Transporter in Mammalian Cells via Adenoviral Transduction - Cheng-Pang Hsu; John M. Hilfinger; Elke Walter; Hans P. Merkle; Blake J. Roessler; Gordon L. Amidon (Pharmaceutical Research, 1998)

Beta Cyclodextrins Enhance Adenoviral-Mediated Gene Delivery to the Intestine - Maria A. Croyle; Blake J. Roessler; Cheng-Pang Hsu; Rong Sun; Gordon L. Amidon (Pharmaceutical Research, 1998)

Mapping quantitative trait loci for binary traits using a heterogeneous residual variance model: an application to Marek's disease susceptibility in chickens - Shizhong Xu; Nissim Yonash; Roger L. Vallejo; Hans H. Cheng (Genetica, 1998)

Genetic Evaluation of a Demographic Bottleneck in the Greater Prairie Chicken - Juan L. Bouzat; Hans H. Cheng; Harris A. Lewin; Ronald L. Westemeier; Jeffrey D. Brawn; Ken N. Paige (Conservation Biology, 1998)

Genetic Evaluation of a Demographic Bottleneck in the Greater Prairie Chicken - Juan L. Bouzat; Hans H. Cheng; Harris A. Lewin; Ronald L. Westemeier; Jeffrey D. Brawn; Ken N. Paige (Conservation Biology, 1998)
Although the theoretical relationship between population size, fitness, and genetic variation is well established, only a few studies have provided direct evidence that ties a decline in both genetic variation and fitness to a demographic bottleneck for a natural system. We report on a genetic comparison of four populations of the Greater Prairie Chicken ( Tympanuchus cupido ) with different demographic histories. Specifically, we compared a population from Illinois that has suffered an extreme demographic contraction and an associated decline in population fitness (measured in terms of hatchability rates) with populations from Kansas, Nebraska, and Minnesota with no known history of bottlenecks or associated declines in fitness. Using the polymerase chain reaction, we amplified six microsatellite loci from which levels of heterozygosity, allelic diversity, and geographic differentiation ( F ST and R ST ) of the studied populations were estimated. Results of this analysis showed that the Illinois Prairie Chicken had the lowest estimate of mean heterozygosity per locus and approximately two‐thirds the allelic diversity, sharing 95–100% of all their alleles with each of the other populations. This finding suggests that the Illinois Prairie Chicken originally had higher levels of genetic diversity that were subsequently lost through an extreme demographic contraction. To our knowledge this is the first example of loss of genetic diversity being associated with a decrease in population fitness as a result of a known demographic bottleneck in a wild bird species. Evaluación Genética de un Cuello de Botella Demográfico en la Gran Gallineta de la Pradera Aunque la relación teórica entre el tamaño poblacional, la aptitud biológica y la variabilidad genética ha sido bien establecida, son pocos lo astudios que han proporcionado evidencia directa que asocie una disminución de la variación genética y de la aptitud biológica con un cuello de botella demografico en sistemas naturales. Reportamos una comparación genética de cuatro poblaciones de la gran gallineta de la pradera ( Tympanucus cupido ) que tuvieron historias demográficas diferentes. Específicamente comparamos una población de Illinois, la cual ha sufrido una contracción demográfica extrema asociada con decrementos en la aptitud biológica poblacional (medida en términos de tasas de eclosión), con poblaciones de Kansas, Nebraska y Minnesota, las cuales no presentan una historia de cuello de botella poblacional ni decrementos en la aptitud bioloógica. Mediante el uso de la reacción en cadena de la polimerasa (PCR) amplificamos seis marcadores de microsatélites con los cuales estimamos niveles de heterocigósis, diversidad alélica y diferenciación geográfica ( F ST y R ST ) en las poblaciones estudiadas. La gran gallineta de la pradera en Illinois presenta el menor valor de heterocigosidad promedio por locus y aproximademente 2/3 de la diversidad alélica, compartiendo 95–100% de sus alelos con cada una de las otras poblaciones. Estos resultados sugieren que la población de Illinois presentaba originalmente niveles mayores de variabilidad genética, los cuales fueron perdidos consecuentemente a través de un contracción demográfica extrema. A nuestro entender, este estudio representa el primer ejemplo en el que se asocia la pérdida de la diversidad genética en una especie de ave silvestre con la disminución en la aptitud poblacional y como resultado de un cuello de botella demográfico conocido.

Oceanic diffusion and the pelagic insects Halobates spp. (Gerridae: Hemiptera) - T. Ikawa; A. Okubo; H. Okabe; L. Cheng (Marine Biology, 1998)

SKF 38393 enhances odor detection performance - R. L. Doty; Cheng Li; Ritu Bagla; William Huang; Cheryl Pfeiffer; Gary M. Brosvic; Judith M. Risser (Psychopharmacology, 1998)

Effects of early discordant binocular vision on the postnatal development of parvocellular neurons in the monkey lateral geniculate nucleus - Y. Sasaki; H. Cheng; Earl L. Smith III.; Y. Chino (Experimental Brain Research, 1998)

Identification and purification of a spinach chloroplast DNA-binding protein that interacts specifically with the plastid psaA - psaB - rps14 promoter region - M. C. Cheng; S. P. Wu; L. F. O. Chen; S. C. G. Chen (Planta, 1997)

Identification of Anguilla japonica and A. mavmovata elvers by allozyme electrophoresis - S. C. Lee; S. C. M. Tsoi; H. L. Cheng; J. T. Chang (Journal of Fish Biology, 1997)
In Taiwanese waters, the morphologically similar elvers of Anguilla japonica and A. marmorata can be distinguished easily at the following loci examined: CK‐D *, LDH‐B *, sMDH‐A * and sMDH‐B *. Among these, CK‐D * and LDH‐B * have fixed allelic differences which can be used as a synoptic key for easy discrimination of the elvers of these two species.

Coordination of copper with aspirin enhances its anti-platelet aggregation activity - L. Weiping; Y. K. Yang; H. Z. Xiong; X. Z. Cheng; Z. H. Chen; Z. Q. Shen; L. Li (Inflammopharmacology, 1997)

Expression and inheritance of foreign genes in transgenic peanut plants generated by Agrobacterium-mediated transformation - M. Cheng; R. L. Jarret; Z. Li; J. W. Demski (Plant Cell Reports, 1997)

Expression and inheritance of foreign genes in transgenic peanut plants generated byAgrobacterium-mediated transformation - M. Cheng; Z. Li; J. W. Demski; R. L. Jarret (Plant Cell Reports, 1997)

Tenidap inhibits 5-lipoxygenase product formation in vitro, but this activity is not observed in three animal models - T. J. Carty; F. J. Sweeney; R. J. Griffiths; J. D. Eskra; M. J. Ernest; J. S. Pillar; J. D. Cheng; L. D. Loose; P. A. Joseph; P. P. Pazoles; P. F. Moore; A. Nagahisa; et al. (Inflammation Research, 1997)

Lipid peroxidation in rats administrated with mercuric chloride - Y. L. Huang; S. L. Cheng; T. H. Lin (Biological Trace Element Research, 1996)

Distribution of specific apolipoproteins determined by immunoblotting of baboon lipoproteins resolved by polyacrylamide gradient gel electrophoresis - David L. Rainwater; Candace M. Kammerer; Min-Lee Cheng; Mary L. Sparks; John L. VandeBerg (Biochemical Genetics, 1992)

Distribution of specific apolipoproteins determined by immunoblotting of baboon lipoproteins resolved by polyacrylamide gradient gel electrophoresis - David L. Rainwater; Candace M. Kammerer; Min-Lee Cheng; Mary L. Sparks; John L. VandeBerg (Biochemical Genetics, 1992)

Method for quantitating cholesterol in subfractions of serum lipoproteins separated by gradient gel electrophoresis - M. -L. Cheng; C. M. Kammerer; W. F. Lowe; B. Dyke; J. L. VandeBerg (Biochemical Genetics, 1988)

Method for quantitating cholesterol in subfractions of serum lipoproteins separated by gradient gel electrophoresis - M. -L. Cheng; C. M. Kammerer; W. F. Lowe; B. Dyke; J. L. VandeBerg (Biochemical Genetics, 1988)

Cryopreservation of erythrocytes in small aliquots for isozyme electrophoresis - M. -L. Cheng; J. L. VandeBerg (Biochemical Genetics, 1987)

Developmental toxicity of Guthion in rats and mice - Robert D. Short; Jan L. Minor; Cheng-Chun Lee; Neil Chernoff; Ronald L. Baron (Archives of Toxicology, 1980)